Data challenges in large-scale transient groundwater modeling using machine learning - Yueling Ma; Danielle Tijerina-Kreuzer; Amy Defnet; Andrew Bennett; Peter Melchior; Laura E Condon; Reed M Maxwell (Advances in Water Resources, 2026)

Zircon geochronology of the Gordonbrook Serpentinite: A fragment of mantle wedge within the New England Orogen, eastern Australia - George G.F. Murray; Solomon Buckman; Allen P. Nutman; Wanchese M. Saktura; Jonathan C. Aitchison; Vickie C. Bennett; Zhen Yan; Changlei Fu (Lithos, 2026)

Curiosity meets the Gediz Vallis Ridge: Remnants of a late-stage debris-flow dominated fan in Gale Crater - A.B. Bryk; W.E. Dietrich; K.A. Bennett; V.K. Fox; C.M. Fedo; A.R. Vasavada; A.A. Fraeman; M.P. Lamb; S. Le Mouélic; G. Caravaca; J.M. Davis; J.A. Grant; et al. (Icarus, 2026)

Fetal exposure to persistent organic pollutants and childhood autism risk - Lauren M. Petrick; Priyanthi S. Dassanayake; Chris Gennings; Haibin Guan; Blessing Akintunde; Mauro Martinez; Pratima Regmi; Irva Hertz-Picciotto; Manish Arora; Deborah H. Bennett (Environmental Research, 2026)

Prenatal exposure to organophosphate ester flame retardants and plasticizers and maternal immune responses in three ECHO cohorts - Jiwon Oh; Judy Van de Water; Thomas G. O'Connor; Kristin Scheible; Anne P. Starling; Dana M. Dabelea; Raina N. Fichorova; Rebecca J. Schmidt; Irva Hertz-Picciotto; Deborah H. Bennett (Environmental Research, 2026)

Occurrence, temporal variation, and meteorological drivers of airborne fungal spores in Laoag City, northern Philippines - Angelli M. Llorando; Reuel M. Bennett; Maureen B. Sabit (Environmental Monitoring and Assessment, 2026)

Watershed Continuum Monitoring Approach: combining multiple water quality patterns along stream and river flowpaths to track sources, pathways, and processing of pollutants - Sujay S. Kaushal; Ashley E. Mon; Stanley B. Grant; Paul M. Mayer; Aaron J. Porter; Andrew J. Sekellick; Jason H. Chase; Shantanu V. Bhide; John D. Jastram; Tamara A. Newcomer-Johnson; Sydney A. Shelton; Alexis M. Yaculak; et al. (Ecological Engineering, 2026)

Fraction-specific pathways of sulfur cycling in agroecosystems with highly weathered soils - Wenxiang Zhou; Brigid A. McKenna; Timothy I. McLaren; Ram C. Dalal; Joshua Bennett-Jones; Peter M. Kopittke (Agriculture, Ecosystems & Environment, 2026)

Thermal tolerance and acclimation limits in bull trout ( Salvelinus confluentus ) alevin - Brendan Maldonado; Travis Durhack; Andrew Chapelsky; Sarah E. Glowa; Analisa Lazaro‐Côté; Raven M. Bennett; Timothy Bartley; Neil J. Mochnacz (Journal of Fish Biology, 2026)
The critical thermal maximum ( CT max ) of bull trout ( Salvelinus confluentus ) alevin was measured after 3 weeks of acclimation to 4–21°C. CT max increased from 24.3 at 4°C to 26.7 at 9°C, plateaued between 9 and 12°C (26.9°C), and declined to 25.9°C at 15°C. Acclimation mortality increased above 12°C, reaching 53.7% at 15°C, and no fish survived at 18–21°C. Condition factor declined at ≥12°C. Results indicate bull trout alevin have limited acclimation capacity beyond 12°C and suggest high vulnerability to lethal stress in streams where temperatures exceed this threshold.

Gestational exposure to organophosphate ester flame retardants and child growth in weight, height, and body mass index at age 2-10 years: the Environmental influences on Child Health Outcomes Program - Anne P. Starling; Xuan Li; Jennifer L. Ames; Emily S. Barrett; Theresa M. Bastain; Claudia Buss; Dana Dabelea; Anne L. Dunlop; Assiamira Ferrara; Monique M. Hedderson; Julie Herbstman; Kurunthachalam Kannan; et al. (Environmental Research, 2026)

Country readiness for Sargassum valorisation in the Caribbean - M. Bennett; A. March; H. Li; P. Lallemand; J.P. Maréchal; P. Failler (Environmental Development, 2026)

Supporting frontline workers in the biodiversity crisis by empowering and enabling practitioners to embrace conservation evidence - Steven J. Cooke; Kevin A. Adeli; Trina Rytwinski; Andrew N. Kadykalo; Jennifer F. Provencher; Vivian M. Nguyen; Joseph R. Bennett; Christina M. Davy; Rachel T. Buxton; Dalal E. L. Hanna; Nathan Young; Jesse C. Vermaire; et al. (Socio-Ecological Practice Research, 2026)

Assessing Potential Data Sources for Landscape-scale Terrestrial Biodiversity Indicators - Tom Bradfer-Lawrence; Meriel Harrison; Adham Ashton-Butt; Sophie Bennett; Robin J. Boyd; Ella Browning; Graeme Buchanan; Adam Fraser; Sian E. Green; Robert Hawkes; Becky E. Heath; Pen-Yuan Hsing; et al. (Environmental Management, 2026)

Novel symbioses between reef fishes and serpulid polychaetes in the Caribbean Sea - Morgan F. Bennett-Smith; Elizabeth McNamee; Samantha Masih; Timothy Lis; Mason Murchison; Allison Cinelli; Toshith Bhaumik; Catheline Y. M. Froehlich; Anna DeLoach; Ned DeLoach; Ninon Martinez; Peter M. Buston; et al. (Symbiosis, 2026)

Corporations and financial institutions driving coastal conflicts involving Indigenous Peoples - Sebastian Villasante; Julia Tovar Verba; Veronica Relano; Sílvia Gómez; José Bakit; Nathan J. Bennett; Anthony Charles; Rafael Calderón-Contreras; Andrés M. Cisneros-Montemayor; Bernardo M. Flores; Lucas A. Garibaldi; Maria Grazia Pennino; et al. (Ambio, 2026)
Socio-environmental conflicts associated with large-scale economic projects in Indigenous territories are well documented, but conflicts in coastal areas remain largely unexplored, despite the crucial differences between inland and coastal ecosystems. While the empirical literature about socio-environmental conflicts in Indigenous territories in coastal areas is growing, the role of financial institutions and corporations in these conflicts is often overlooked. This study addresses this gap by examining the financial institutions and corporations associated with more than 400 reported socio-environmental conflicts affecting Indigenous Peoples in coastal areas worldwide. Our results show that most financial institutions supporting projects linked to conflicts are based in West Europe and North America, with North American financial institutions linked to multiple projects. The energy sector accounts for the highest number of socio-environmental conflicts, particularly those involving corporations operating across continents. Many European and North American corporations operate mostly in Africa, but also globally. Corporations with overseas operations are associated with a higher intensity of conflicts. These findings highlight the need to scrutinize financial investments and corporate practices driving socio-environmental conflicts in coastal Indigenous territories, where human rights are often at risk. The lack of due diligence and accountability in applying environmental and social safeguards weakens protections for both ecosystems and Indigenous communities. Strengthening the enforcement of national and international laws on environmental sustainability, human rights and Indigenous rights is therefore essential for coastal development projects.

A critical review of potential modifiers of air pollutant associations with dementia and related outcomes - JeongWon Han; Yina Li; Sangji Lee; Katie M. Lynch; Erin E. Bennett; Qi Ying; Eun Sug Park; Richard L. Smith; James D. Stewart; Eric A. Whitsel; Melinda C. Power; Xiaohui Xu (NeuroToxicology, 2026)

Lung cancer risk in relation to indicative radon atlas metrics in Northern Ireland: a population-based case–control study using secondary data - Claire M. Delargy; Helen G. Coleman; Quentin G. Crowley; Damien Bennett; Javier Elio; Deirdre Fitzpatrick; Helen Mitchell; Sara M. Wallace; Rawan A. N. Alhattab; Angela Scott; Bernadette McGuinness; Ruth F. Hunter; et al. (Environmental Geochemistry and Health, 2026)
Radon is an established lung carcinogen, but more research is needed to inform whether area-based measures of radon exposure reflect underlying cancer risk. This study, the first of its kind in the UK, aimed to investigate the association between a nationwide indicative radon atlas and lung cancer risk in Northern Ireland, a region in which lung cancer screening programmes are under design. A population-based case–control study was conducted. Primary lung cancer cases ( n = 1,687) from the Northern Ireland Cancer Registry diagnosed in 2006 and 2014 were compared with 8,094 non-lung cancer controls from a large cohort. Radon exposure data were extracted from the Indicative Atlas of Radon, which categorises 1 km 2 areas by the percentage of households exceeding 200 Bq/m 3 . Exposure data were linked to participants by postcode. Logistic regression models adjusted for age, sex, smoking status, deprivation and PM 2.5 exposure were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for lung cancer. Individuals residing in high radon exposure areas (Atlas Class 6) had a greater than two-fold lung cancer risk (adjusted OR: 2.24, 95% CI: 1.25, 3.92) compared to residents in all other areas. This association was revealed after adjusting for PM 2.5 . This study supports the utility of an indicative radon atlas in reflecting underlying population lung cancer risk associated with radon, while highlighting constraints inherent to atlas-based exposure classification and secondary data.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Succinate-driven cardiac mitochondrial respiration aligns with whole-animal hypoxia-tolerance in African mole-rats - Daniel Munro; Daniel W. Hart; Nigel C. Bennett; Barry Van Jaarvsveld; Maiah E. M. Devereaux; Kevin L. Campbell; Rajaa Sebaa; Emmanuel Van Dermeeren; Mary-Ellen Harper; Pierre U. Blier; Matthew E. Pamenter (Mammalian Biology, 2026)

Nutrient Transfer Dynamics of Anadromous Alewives (Alosa pseudoharengus) in Freshwater Spawning and Nursery Habitats - Robert E. Vincent; John M. Logan; John J. Sheppard; Michael Power; Stephen T. Hurley; Kevin Bennett (Estuaries and Coasts, 2026)
River herring (alewife, Alosa pseudoharengus and blueback herring, A . aestivalis ) can act as vectors of nutrient transfer between marine and freshwater environments. Adult river herring can transfer marine-derived nutrients to freshwater ecosystems during spawning migrations through excretions and direct consumption of adults, eggs, and early phase juveniles by freshwater scavengers and predators. Adults and juveniles can transfer nutrients derived during freshwater residency back to the marine environment following emigration and the same excretion and consumption mechanisms. Potential nutrient transfers were assessed by applying carbon, nitrogen, and sulfur stable isotope analyses to a collection of juvenile and adult alewives, baseline food web components, and freshwater fish predators in three ponds in southeastern Massachusetts USA. Out-migrating adult alewife tissue stable isotope values were lower for both carbon and sulfur but higher for nitrogen than in-migrating conspecifics reflecting incorporation of freshwater-derived nutrients. Most juvenile alewife stable isotope values were at steady state with freshwater food webs at the time of sampling reflecting additional export of freshwater-derived nutrients with their eventual emigration to the marine environment. Stable isotope-based detection of marine-derived nutrients in freshwater predators was limited to catadromous elvers ( Anguilla rostrata ), anadromous white perch ( Morone americana ), and semi-anadromous yellow perch ( Perca flavescens ) with no marine-derived nutrients detected in resident freshwater fish predators. However, juvenile alewives were observed in stomachs of smallmouth ( Micropterus dolomieu ) and largemouth bass ( M . nigricans ). Results further inform current alewife ecosystem-level interactions with the marine and freshwater environments that they occupy during different life history phases for the many coastal watersheds in New England.

Herbarium Specimens Reveal Long‐Term Decline in Pollination Services Since the 1970s - Bofeng Song; Heidi Zimmer; Mark Clements; Demetra Rakosy; Tiffany M. Knight; Joanne M. Bennett (Global Change Biology, 2026)
Anthropogenic change has resulted in pollinator declines and altered plant–pollinator interactions. This may alter pollination services, reducing the reproductive success of plants. Yet few datasets allow us to track changes in pollination services over time. Herbaria provide a unique opportunity to assess pollination services across broad spatial and temporal scales enabling the examination of associated spatiotemporal anthropogenic drivers of change. We quantified changes in pollination services to the orchid genus Caladenia over the past century, a period of rapid land‐use intensification and climate change in Australia. Examining 10,494 Caladenia flowers preserved at the Australian National Herbarium showed a reduction in pollination services totaling > 60% over the whole study period, with rapid declines occurring post 1970. Declines in pollination services occurred across species pollinated by different taxa and with varying threat status. Sexually deceptive species showed more pronounced declines in pollination services than food‐deceptive species, whereas no decline was detected in the self‐compatible species. Land‐use intensity and rising temperatures were significant predictors of changes in pollination service. Our findings provide rare evidence of declines in pollination services and demonstrate the value of herbarium collections in understanding global change.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Flame retardant biomarker changes with furniture replacement after flammability standard update - Kathleen R. Attfield; Kimberly Berger; Robin E. Dodson; Deborah H. Bennett; Kathryn M. Rodgers; Rebecca Moran; Tasha Stoiber; Yunzhu Wang; Songmei Gao; Sabrina Crispo Smith; June-Soo Park; Arlene Blum; et al. (Environmental Pollution, 2026)

Spatial and temporal variations in the distribution of eastern Australian post-orogenic granites and related mineral deposits: metallogenic and tectonic significance - D. L. Huston; Y. Cheng; S. L. Jones; D. C. Champion; M. D. Norman; M. W. Agnew; A. Cross; V. C. Bennett; R. A. Creaser (Australian Journal of Earth Sciences, 2026)

Beyond the surface: Stratification and turnover control microplastic dynamics in a seasonally ice-covered sentinel lake - Brittany Welsh; Erin Bennett; Andrew M. Paterson; Huaxia Yao; Ken Drouillard; Julian Aherne (Journal of Hazardous Materials, 2026)

Functional group composition of soil organic carbon varies between soil organic matter fractions but not with long-term cropping or soil depth - Wenxiang ZHOU; Brigid A. MCKENNA; Joshua BENNETT-JONES; Timothy I. MCLAREN; Ram C. DALAL; Peter M. KOPITTKE (Pedosphere, 2025)

Association of midlife air pollution and road proximity exposure with 29-year cognitive decline - Melinda C. Power; Ziwei Song; Annie Chen; Katie M. Lynch; Naa Adoley Parker-Allotey; Erin E. Bennett; Xiaohui Xu; Eric A. Whitsel; Richard L. Smith; James D. Stewart; Eun Sug Park; Qi Ying; et al. (NeuroToxicology, 2025)

Epistatic effects of IGHG and FCGRIIB genes on the development of Alzheimer’s disease in African Americans - Janardan P. Pandey; Paul J. Nietert; Aryan M. Namboodiri; David A. Bennett; Lisa L. Barnes (Immunogenetics, 2025)
Genome-wide association studies (GWAS) of Alzheimer’s disease (AD) have identified a large number of susceptibility genes, but most of AD heritability remains unexplained, implying the existence of additional genes. Furthermore, the majority of the GWAS have been conducted in people of European descent, and the genes important for AD susceptibility in people of African descent have been underexplored. In this hypothesis-generating prospective cohort study, we genotyped 191 African Americans (AAs) from three longitudinal cohorts on aging for the IgG3 allotype GM6, which is expressed exclusively in people of African descent, and assessed its interaction with IGHG , FCGRIIB , and HLA-DRB1 genes. Cox proportional hazards modeling showed that GM6 by itself was not significantly associated with AD development. However, there was evidence of epistatic interaction: The risk of developing AD associated with GM6 positivity was significantly different ( p = 0.0098) in non-GM17/GM17 participants compared with GM 17/GM17 participants. Specifically, in non-GM17/GM17 participants, the risk of AD was over fourfold higher in GM6-positive participants compared with GM 6-negative participants (HR = 4.63). Similarly, risk of developing AD associated with GM6 positivity was marginally different in non-FCGRIIB TT participants compared with FCGRIIB TT participants. In non-FCGRIIB TT participants, the risk of developing AD was over twofold higher in GM6-positive participants compared with GM6-negative participants (HR = 2.44). This is the first report suggesting that immunoglobulin GM allotypes might play a role in AD etiology among AAs; however, since this was largely a hypothesis-generating study, replication in larger cohorts would be required to confirm this finding.

Accounting for human–nature linkages in area‐based conservation monitoring through social–ecological indicator bundles - Natalie C. Ban; Mark H. Carr; Emily M. Rubidge; Anne Salomon; Joachim Claudet; Arielle Levine; Lindsay Aylesworth; Luisa Ramirez; Jenn M. Burt; Mark Andrachuk; Natascia Tamburello; Rebecca Martone; et al. (Conservation Biology, 2025)
As the coverage of area‐based conservation increases across the globe, it is critical to improve understanding of the social and ecological outcomes of such measures and the pathways to their outcomes. A social–ecological systems approach to monitoring and evaluation is increasingly advocated; yet, applications remain scarce. We sought to facilitate operationalization of this approach through prioritization of indicators when resources are scarce and to improve capture of social–ecological interactions. We convened a working group of practitioners and academics to explore linked social and ecological interactions through a case study of marine protected areas (MPAs). We used causal models (implemented through causal loop diagrams) in participatory and future‐oriented approaches to identify interactions among key nodes of the system that can be a focus of monitoring. These nodes and their interactions provided insight into linked indicators of key system components, for example, biomass, compliance, perceived legitimacy, catches, and perceived fairness. We called these indicator bundles . Indicator bundles can be applied to analyze causal modeling diagrams, identify essential elements to monitor, and inform analytical and reporting protocols. The bundles can also help identify key leverage points for adaptive management to improve outcomes of existing interventions. This approach can inform monitoring and evaluation and, ultimately, the design and adaptive management of conservation areas that maximize social and ecological benefits and minimize negative trade‐offs.

Pre- and post-move exposure to air pollution and neighborhood socioeconomic status - Chelsea Liu; Erin E. Bennett; Katie M. Lynch; Xiaohui Xu; Eun Sug Park; Qi Ying; Richard L. Smith; James D. Stewart; Eric A. Whitsel; Joel D. Kaufman; Emma K. Stapp; Melinda C. Power (Science of The Total Environment, 2025)

Correction: Positive and negative impacts of electrical infrastructure on animal biodiversity: A systematic review - Adam J. Bennett; David M. Watson; Maggie J. Watson (Oecologia, 2025)

High take of mobulid rays in East Java, Indonesia: landing trends and socio-economic context - Betty J. L. Laglbauer; Muhammad G. Salim; Fahmi; Selvia Oktaviyani; Irianies C. Gozali; Firmansyah Tawang; Hasan S. Rizal; Vidlia P. Rosady; Didik Rudianto; Isabel Ender; Jorge M. R. Fontes; Pedro Afonso; et al. (Environmental Biology of Fishes, 2025)

Influences and interactions of vessel noise and environmental variables on Silver Perch (Bairdiella chrysoura) and seatrout (Cynoscion spp.) spawning choruses in estuaries of the northern Gulf of Mexico - Kelly S. Boyle; T. Erin Cox; Amanda M. Kirkland; Bennett H. Price (Marine Pollution Bulletin, 2025)

Temporal dynamics of the summer soundscape near oil platforms of the shallow continental shelf off Louisiana - Kelly S. Boyle; T. Erin Cox; Amanda M. Kirkland; Bennett H. Price (Marine Environmental Research, 2025)

Conservation planning for environmental water to climate refugia in the manageable Murray–Darling Basin - Joanne M. Bennett; Simon Linke; Shane Brooks; Alex Bush; James Hitchcock; Carmel Pollino; Ross M. Thompson (Journal of Environmental Management, 2025)

Corrigendum to “Exposure to endocrine disrupting chemicals including phthalates, phenols, and parabens in infancy: Associations with neurodevelopmental outcomes in the MARBLES study” [IJHEH 261 (2024) 114425] - Jennie Sotelo-Orozco; Antonia M. Calafat; Julianne Cook Botelho; Rebecca J. Schmidt; Irva Hertz-Picciotto; Deborah H. Bennett (International Journal of Hygiene and Environmental Health, 2025)

What is ‘good evidence’ for environmental decision making? Insights from professionals working at the science-policy interface - Elizabeth A. Nyboer; Andrew N. Kadykalo; Nathan Young; Vivian M. Nguyen; Trina Rytwinski; John-Francis Lane; Joseph R. Bennett; Nathan Harron; Susan M. Aitken; Graeme Auld; David Browne; Aerin L. Jacob; et al. (Environmental Science & Policy, 2025)

Interdisciplinary challenges for wildfire futures - T.A. Fairman; J. Aryal; P.J. Baker; A. Best; J. Cawson; H. Clarke; M.S. Fletcher; L. Gibbs; G. Foliente; L. Godden; M. Gibson; L. Kelly; et al. (Environmental Science & Policy, 2025)

Calibration of the FullCAM model for Australian native vegetation - David I. Forrester; Jacqueline R. England; Chiara Pasut; Keryn I. Paul; Lauren T. Bennett; Chris Eastaugh; Thomas Fairman; Melissa Fedrigo; Carl R. Gosper; Sabine Kasel; Tom Lewis; Crispen Marunda; et al. (Ecological Modelling, 2025)

Positive and negative impacts of electrical infrastructure on animal biodiversity: A systematic review - Adam J. Bennett; David M. Watson; Maggie J. Watson (Oecologia, 2025)
Electrical infrastructure networks are predicted to greatly expand in response to the expected 48% increase in global energy demand by 2040. While assessments of electrical infrastructure are abundant, mixed effects on animal diversity have been reported, warranting further evaluation to determine true effects. We conducted a systematic literature review covering individual, population, and community-level assessments to determine the impacts posed to animal biodiversity by electrical infrastructure and the measures to reduce impacts. Our results show that the literature around electrical infrastructure and animal biodiversity has grown exponentially since the start of the millennium and is biased towards birds and mammals in economically developed countries. We found the majority of reported impacts were negative, occurring primarily through barrier effects (collision) and use of linear features as a resource (electrocution), causing significant population impacts in select species. However, we also found that electrical infrastructure provided positive effects (increased habitat provisioning) to certain taxonomic groups (e.g. corvids, storks), which suggests the potential to encourage conservation efforts using appropriate mitigation on electrical infrastructure. We found the majority of current literature detailed mitigation measures focused on reducing collisions through line (51%) and tower alterations (30%), but often omitted the impacts of EMF, noise, and UV, indicating significant knowledge gaps. On a wider scale, we found that mortality from electrical infrastructure ranked lower than building collisions and predation from feral cats, but remained higher than other anthropogenic energy sources, indicating the potential to cause significant impacts to large-bodied bird species if not addressed.

Reducing non-revenue water in peri-urban Tanzania through an integrated data-driven approach: a pilot study in Dodoma - M. M. Kwikima; G. Bennett; F. K. Ahmada; A. Magina (International Journal of Energy and Water Resources, 2025)

Celebrating the fifth edition of the International Symposium on Fungal Stress – ISFUS, a decade after its 2014 debut - Alene Alder-Rangel; Amanda E.A. Rangel; Arturo Casadevall; Asiya Gusa; Chaoyang Xue; Charles M. Boone; Chris Todd Hittinger; Claudio A. Masuda; Consuelo Olivares-Yañez; Deborah Bell-Pedersen; Erica J. Washington; Gerhard Braus; et al. (Fungal Biology, 2025)

Decision-making and ecosystem service dimensions of managed dyke realignment in the complex coastal landscapes of the Bay of Fundy - Lara Cornejo; Elson Ian Nyl Ebreo Galang; Kate Sherren; Jeremy Lundholm; Danika van Proosdij; Will Balser; Elena Bennett; Tony M. Bowron; Kirsten Ellis; Jonathan Fowler; Jennifer Graham; Patrick James; et al. (Ocean & Coastal Management, 2025)

Genome-wide associations within diverse wild apple germplasm for postharvest blue mold resistance to Penicillium expansum - Lauren Whitt; John S. Bennett; Tamara D. Collum; Breyn Evans; Doug Raines; Ben Gutierrez; Wojciech J. Janisiewicz; Wayne M. Jurick; Christopher Gottschalk (Postharvest Biology and Technology, 2025)

Small shelly fauna biodiversity from reef-adjacent facies of the lower Cambrian Harkless Formation, Nevada - Casey C. Bennett; Clare Mate; Sarah M. Jacquet (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Hepatic B-cell lymphoma in a wild European badger (Meles meles): An unusual finding during tuberculosis surveillance in the United kingdom - S. Hilton; M. Bennett; A. Ortiz; C. Bianco (Journal of Comparative Pathology, 2025)

From concept to reality: the journey of establishing the Australian companion animal registry of cancers (ACARCinom) - C. Palmieri; P. Bennett; M. Bruce; M. Krockenberger; P. McLaren; T. Meiring; K. Mengersen; A. Peaston; A. Roach; G. Rossi; A. Stent; R. Soares-Magalhaes (Journal of Comparative Pathology, 2025)

Putting numbers to a metaphor: A Bayesian Belief Network with which to infer Soil Quality and Health - Kirsty L. Hassall; Joanna Zawadzka; Alice E. Milne; Ronald Corstanje; James A. Harris; A. Gordon Dailey; Aidan M. Keith; Margaret J. Glendining; S.P. McGrath; Lindsay C. Todman; Paul Alexander; Philippa Arnold; et al. (European Journal of Agronomy, 2025)

A Framework for Modelling Thermal Load Sensitivity Across Life - Pieter A. Arnold; Daniel W. A. Noble; Adrienne B. Nicotra; Michael R. Kearney; Enrico L. Rezende; Samuel C. Andrew; Verónica F. Briceño; Lauren B. Buckley; Keith A. Christian; Susana Clusella‐Trullas; Sonya R. Geange; Lydia K. Guja; et al. (Global Change Biology, 2025)
Forecasts of vulnerability to climate warming require an integrative understanding of how species are exposed to, are damaged by, and recover from thermal stress in natural environments. The sensitivity of species to temperature depends on the frequency, duration, and magnitude of thermal stress. Thus, there is a generally recognized need to move beyond physiological metrics based solely on critical thermal limits and integrate them with natural heat exposure regimes. Here we propose the thermal load sensitivity (TLS) framework, which integrates biophysical principles for quantifying exposure with physiological principles of the dynamics of damage and repair processes in driving sublethal impacts on organisms. Building upon the established thermal death time (TDT) model, which integrates both the magnitude and duration of stress, the TLS framework attempts to disentangle the accumulation of damage and subsequent repair processes that alter responses to thermal stress. With the aid of case studies and reproducible simulation examples, we discuss how the TLS framework can be applied to enhance our understanding of the ecology and evolution of heat stress responses. These include assessing thermal sensitivity across diverse taxonomic groups, throughout ontogeny, and for modular organisms, as well as integrating additional stressors in combination with temperature. We identify critical research opportunities, knowledge gaps, and novel ways of integrating physiological measures of thermal sensitivity to improve understanding and predictions of thermal vulnerability at various scales across life.

Evidence of novel symbiotic relationships between Christmas tree worms and coral reef blennies and gobies - Morgan F. Bennett-Smith; Catheline Y.M. Froehlich; Lili F. Vizer; Peter M. Buston (Symbiosis, 2025)

Addressing key issues and knowledge gaps in resilience science for agriculture - Shana M. Sundstrom; Tala Awada; Elena M. Bennett; Brandon Bestelmeyer; Jennifer Hodbod; Anna Pacheco; Sheri Spiegal; Craig R. Allen (Agricultural Systems, 2025)

Diversity and composition of oomycetes in different stages of leaf senescence: a culture-based case study on mangroves of the Philippine archipelago - Reuel M. Bennett; Nikki Heherson A. Dagamac; Bora Nam; Niño Andree Louis E. Caguimbal; Gina R. Dedeles; Marco Thines (Mycological Progress, 2025)
Saprotrophic oomycetes of mangroves are a poorly understood group of eukaryotic Straminipila . As recent phylogenetic analyses revealed, they seem rather diverse, with several recently discovered lineages. However, their prevalence, ecological preferences, and succession on substrates have hardly been studied aside from one early study with limited sampling. Thus, the aim of this study was to provide preliminary insights into these topics based on oomycetes isolated from mangrove leaf litter of various stages of decay, using a culture-based approach. Identification was based on sporulation characteristics and phylogenetic analysis of ITS (internal transcribed spacers of rDNA). A total of 547 axenic strains representing 15 taxa were isolated from a mangrove leaf litter sampled in different parts of the Philippines. Of these, five species were conspecific to known barcoded taxa, two were recently introduced taxa, and eight lineages represented undescribed oomycete species. Alpha diversity analysis revealed that the yellow–brown decay stage harbored the highest number of oomycete species, whereas the beta community analysis suggested that in terms of the number of isolated strains, the four stages of leaf decay suggest overlapping species richness. While some oomycetes could only be isolated a single time, others were highly prevalent and found in all locations sampled. This highlights that mangrove oomycetes are diverse both in terms of their ecological preferences and abundance patterns.

Qualitative and quantitative assessment of Sargassum valorisation solutions for the Caribbean - M. Bennett; A. March; H. Li; P. Lallemand; J.-P. Maréchal; P. Failler (Journal of Environmental Management, 2025)

Rapid dough making quality analysis of wheat flour using Fourier transform infrared spectroscopy and chemometrics - James M. Kelly; Björn Bohman; Dion Bennett; Nicolas L. Taylor (Food Chemistry, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

The power of caring touch: from survival to prosocial cooperation - Michael Griesser; Nigel C. Bennett; Judith M. Burkart; Daniel W. Hart; Natalie Uomini; Miyako H. Warrington (Trends in Ecology & Evolution, 2025)

Pediment formation and subsequent erosion in Gale crater: Clues to the climate history of Mars - A.B. Bryk; W.E. Dietrich; K.A. Bennett; V.K. Fox; C.M. Fedo; M.P. Lamb; E.S. Kite; L.M. Thompson; S.G. Banham; J. Schieber; J.A. Grant; A.R. Vasavada; et al. (Icarus, 2025)

An improved method for quantitatively measuring antifouling coating performance using a mussel single thread tensile adhesion test - Samuel M. Pennell; Thomas B. LeFevre; Jonathan Bennett; Wilaiwan Chouyyok; Joseph D. Daddona; Raymond S. Addleman; Curtis J. Larimer; George T. Bonheyo (Biofouling, 2025)

Measurement of urban vitality with time-lapsed street-view images and object-detection for scalable assessment of pedestrian-sidewalk dynamics - Ricky Nathvani; Alicia Cavanaugh; Esra Suel; Honor Bixby; Sierra N. Clark; Antje Barbara Metzler; James Nimo; Josephine Bedford Moses; Solomon Baah; Raphael E. Arku; Brian E. Robinson; Jill Baumgartner; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

An evidence map of research assessing the effects of timber harvesting on water quality, biotic and biodiversity indicators in running waters - D.E.L. Hanna; M. Harper; X. Giroux-Bougard; J.S. Richardson; T. Rytwinski; A. Bachhuber; E.J. Hudgins; S. Karimi; R. Schuster; A.D. Binley; R. Reedman; J.G. Vincent; et al. (Forest Ecology and Management, 2025)

Occurrence of mobulid rays in Northwest Madagascar - Stella Diamant; Caterina Bosio; Joshua Rambahiniarison; Chris Scarffe; Michel Strogoff; Jeremy J. Kiszka; Rhett Bennett; Tanguy Guillemain d’Echon; Elina Sourisseau; Léonce C. M. Fidiarisandratra; Salvatore Cerchio; Stephanie Venables; et al. (Environmental Biology of Fishes, 2025)
The waters around Nosy Be in northwest Madagascar are well-known for the occurrence of large planktivores, such as whale sharks ( Rhincodon typus ) and Omura’s whales ( Balaenoptera omurai ). Between 2016 and 2022, sighting data on mobulid rays were opportunistically collected during tourism activities. Additional sources, including citizen science submissions, tourism operator reports, and social media records, were used to compile sightings of three mobulid ray species. A total of 255 encounters were documented, with Mobula mobular ( n = 165) being the most common, followed by M. birostris ( n = 60) and M. kuhlii ( n = 30). Notably, the absence of confirmed M. alfredi records since 2015 suggests a potential local decline. This study highlights Nosy Be as a habitat for mobulid rays and emphasises the necessity for further species monitoring, ongoing identification of potential threats, and management initiatives aiming at reducing mortality from gillnet fishing.

Co-imagining future scenarios can enhance environmental actors’ empathy toward future generations and non-human life-forms - Elson Ian Nyl Ebreo Galang; Elena M. Bennett; Gordon Hickey; Julia Baird; Gillian Dale; Kate Sherren (Sustainability Science, 2025)

Participatory scenario planning: A social learning approach to build systems thinking and trust for sustainable environmental governance - Elson Ian Nyl Ebreo Galang; Elena M. Bennett; Gordon M. Hickey; Julia Baird; Blane Harvey; Kate Sherren (Environmental Science & Policy, 2025)

Divergent trajectories of Arctic change: Implications for future socio-economic patterns - Abbie Tingstad; Kristin Van Abel; Mia M. Bennett; Isabelle Winston; Lawson W. Brigham; Scott R. Stephenson; Margaret Wilcox; Stephanie Pezard (Ambio, 2025)
Climate change is causing rapid warming in the Arctic, which, alongside other physical, socio-economic, cultural, geopolitical, and technological factors, is driving change in the far north. This research presents a conceptual model summarizing Arctic change factors which in turn was used in the design of a Delphi exercise which leveraged a variety of experts to forecast trajectories in different parts of the Arctic. Based on these experts’ expectations for economic and governance outcomes by 2050, we find that our results illustrate the “many Arctics” concept or some of the ways in which the Arctic is heterogenous now, and perhaps becoming increasingly so in the future. Sub-regions of the Arctic differed in expert expectations about the future of resource extraction, tourism, Indigenous self-determination, and military activity, among other outcomes. This work also discusses the post-2022 geopolitical situation and some potential implications of “many Arctics” for policy and future governance.

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Systematic conservation prioritization with the prioritizr R package - Jeffrey O. Hanson; Richard Schuster; Matthew Strimas‐Mackey; Nina Morrell; Brandon P. M. Edwards; Peter Arcese; Joseph R. Bennett; Hugh P. Possingham (Conservation Biology, 2025)
Plans for expanding protected area systems (prioritizations) need to fulfill conservation objectives. They also need to account for other factors, such as economic feasibility and anthropogenic land‐use requirements. Although prioritizations are often generated with decision support tools, most tools have limitations that hinder their use for decision‐making. We outlined how the prioritizr R package ( https://prioritizr.net ) can be used for systematic conservation prioritization. This decision support tool provides a flexible interface to build conservation planning problems. It can leverage a variety of commercial (e.g., Gurobi) and open‐source (e.g., CBC and SYMPHONY) exact algorithm solvers to identify optimal solutions in a short period. It is also compatible with a variety of spatially explicit (e.g., ESRI Shapefile, GeoTIFF) and nonspatial tabular (e.g., Microsoft Excel Spreadsheet) data formats. Additionally, it provides functionality for evaluating prioritizations, such as assessing the relative importance of different places selected by a prioritization. To showcase the prioritizr R package, we applied it to a case study based in Washington state (United States) for which we developed a prioritization to improve protected area coverage of native avifauna. We accounted for land acquisition costs, existing protected areas, places that might not be suitable for protected area establishment, and spatial fragmentation. We also conducted a benchmark analysis to examine the performance of different solvers. The prioritization identified 12,400 km 2 of priority areas for increasing the percentage of species’ distributions covered by protected areas. Although open source and commercial solvers were able to quickly solve large‐scale conservation planning problems, commercial solvers were required for complex, large‐scale problems.. The prioritizr R package is available on the Comprehensive R Archive Network (CRAN). In addition to reserve selection, it can inform habitat restoration, connectivity enhancement, and ecosystem service provisioning. It has been used in numerous conservation planning exercises to inform best practices and aid real‐world decision‐making.

Gestational phthalate exposure and behavioral problems in preschool-aged children with increased likelihood of autism spectrum disorder - Jeong Weon Choi; Deborah H. Bennett; Antonia M. Calafat; Daniel J. Tancredi; Meghan Miller; Rebecca J. Schmidt; Hyeong-Moo Shin (International Journal of Hygiene and Environmental Health, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Stuck in the mangrove mud: The risk of trace element exposure to shore crabs in restored urban mangroves - Jasmine A. Rasmussen; William W. Bennett; Steve D. Melvin; Michael Sievers; Charlotte A. McAneney; Ainsley Leaning; Rod M. Connolly (Science of The Total Environment, 2024)

Systematic trends in the substitution mechanisms of minor elements in cassiterite - J. M. Bennett; A. I. S. Kemp; S. G. Hagemann; M. L. Fiorentini; M. P. Roberts (Australian Journal of Earth Sciences, 2024)

Holobiont Traits Shape Climate Change Responses in Cryptic Coral Lineages - Carsten G. B. Grupstra; Kirstin S. Meyer‐Kaiser; Matthew‐James Bennett; Maikani O. Andres; David J. Juszkiewicz; James E. Fifer; Jeric P. Da‐Anoy; Kelly Gomez‐Campo; Isabel Martinez‐Rugerio; Hannah E. Aichelman; Alexa K. Huzar; Annabel M. Hughes; et al. (Global Change Biology, 2024)
As ocean warming threatens reefs worldwide, identifying corals with adaptations to higher temperatures is critical for conservation. Genetically distinct but morphologically similar (i.e. cryptic) coral populations can be specialized to extreme habitats and thrive under stressful conditions. These corals often associate with locally beneficial microbiota (Symbiodiniaceae photobionts and bacteria), obscuring the main drivers of thermal tolerance. Here, we leverage a holobiont (massive Porites ) with high fidelity for C15 photobionts to investigate adaptive variation across classic (“typical” conditions) and extreme reefs characterized by higher temperatures and light attenuation. We uncovered three cryptic lineages that exhibit limited micro‐morphological variation; one lineage dominated classic reefs (L1), one had more even distributions (L2), and a third was restricted to extreme reefs (L3). L1 and L2 were more closely related to populations ~4300 km away, suggesting that some lineages are widespread. All corals harbored Cladocopium C15 photobionts; L1 and L2 shared a photobiont pool that differed in composition between reef types, yet L3 mostly harbored unique photobiont strains not found in the other lineages. Assemblages of bacterial partners differed among reef types in lineage‐specific ways, suggesting that lineages employ distinct microbiome regulation strategies. Analysis of light‐harvesting capacity and thermal tolerance revealed adaptive variation underpinning survival in distinct habitats: L1 had the highest light absorption efficiency and lowest thermal tolerance, suggesting that it is a classic reef specialist. L3 had the lowest light absorption efficiency and the highest thermal tolerance, showing that it is an extreme reef specialist. L2 had intermediate light absorption efficiency and thermal tolerance, suggesting that is a generalist lineage. These findings reveal diverging holobiont strategies to cope with extreme conditions. Resolving coral lineages is key to understanding variation in thermal tolerance among coral populations, can strengthen our understanding of coral evolution and symbiosis, and support global conservation and restoration efforts.

Genetic diversity of the largest African mole-rat genus, Bathyergus. One, two or four species? - R. Šumbera; M. Uhrová; G. Montoya-Sanhueza; A. Bryjová; N.C. Bennett; O. Mikula (Molecular Phylogenetics and Evolution, 2024)

Knowledge of and Willingness to Consume Insects as an Alternative Protein Source Among College Students in the Midwest - M. Miller; M. Bennett; V. Willard; O. Campos Ortiz; M. Hughes; J. Gibson; J. Klank; X. Wu (Journal of the Academy of Nutrition and Dietetics, 2024)

Testing a rapid assessment approach for estimating ecosystem service capacity in urban green alleys - Marie C. Dade; Isabella C. Richmond; Jesse T. Rieb; Erin T.H. Crockett; Kayleigh Hutt-Taylor; Serena Sinno; Karina Benessaiah; Catherine Destrempes; Jacqueline Hamilton; Fatemeh Izadi; L. Emily Kroft; Lingshan Li; et al. (Urban Forestry & Urban Greening, 2024)

A comparison of PM2.5 exposure estimates from different estimation methods and their associations with cognitive testing and brain MRI outcomes - Melinda C. Power; Katie M. Lynch; Erin E. Bennett; Qi Ying; Eun Sug Park; Xiaohui Xu; Richard L. Smith; James D. Stewart; Jeff D. Yanosky; Duanping Liao; Aaron van Donkelaar; Joel D. Kaufman; et al. (Environmental Research, 2024)

Neuropsychological Deficits in Disordered Screen Use Behaviours: A Systematic Review and Meta-analysis - Michoel L. Moshel; Wayne A. Warburton; Jennifer Batchelor; Joanne M. Bennett; Katherine Y. Ko (Neuropsychology Review, 2024)
Over the last few decades, excessive and disordered screen use has become more prevalent, prompting investigations into its associated consequences. The extent to which disordered screen use behaviours impact neuropsychological functioning has been reportedly mixed and at times inconsistent. This review sought to synthesise the literature and estimate the magnitude of overall cognitive impairment across a wide range of disordered screen use behaviours. We also sought to determine the cognitive domains most impacted, and whether the observed impairments were moderated by the classification of screen-related behaviours (i.e., Internet or gaming) or the format of cognitive test administration (i.e., paper-and-pencil or computerised). A systematic search of databases (Embase, PsycINFO, MEDLINE) identified 43 cross-sectional articles that assessed neuropsychological performance in disordered screen use populations, 34 of which were included in the meta-analysis. A random-effects meta-analysis revealed significant small/medium ( g = .38) cognitive deficits for individuals with disordered screen use behaviours relative to controls. The most affected cognitive domain with a significant medium effect size ( g = .50) was attention and focus followed by a significant reduction in executive functioning ( g = .31). The classification of disordered screen use behaviours into Internet or gaming categories or the format of cognitive testing did not moderate these deficits. Additionally, excluding disordered social media use in an exploratory analysis had little effect on the observed outcomes. This study highlights a number of methodological considerations that may have contributed to disparate findings and shows that disordered screen use can significantly impact cognitive performance. Recommendations for future research are also discussed. Data for this study can be found at https://osf.io/upeha/ .

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Exposure to endocrine disrupting chemicals including phthalates, phenols, and parabens in infancy: Associations with neurodevelopmental outcomes in the MARBLES study - Jennie Sotelo-Orozco; Antonia M. Calafat; Julianne Cook Botelho; Rebecca J. Schmidt; Irva Hertz-Picciotto; Deborah H. Bennett (International Journal of Hygiene and Environmental Health, 2024)

Perspectives: Five organizing themes for invasive forest insect and disease management in Canada and the United States - Emma J. Hudgins; Brian Leung; Chris J.K. MacQuarrie; Deborah G. McCullough; Abraham Francis; Gary M. Lovett; Qinfeng Guo; Kevin M. Potter; Catherine I. Cullingham; Frank H. Koch; Jordanna N. Bergman; Allison D. Binley; et al. (Forest Ecology and Management, 2024)

Emotional and functional well-being in long-term breast cancer survivorship - Yumeng Ren; Joanna Maselko; Xianming Tan; Andrew F. Olshan; Angela M. Stover; Antonia V. Bennett; Katherine E. Reeder-Hayes; Jessie K. Edwards; Bryce B. Reeve; Melissa A. Troester; Marc A. Emerson (Cancer Causes & Control, 2024)

Endangered giant kelp forests support similar fish and macroinvertebrate communities to sympatric stipitate kelp forests - Hunter Forbes; Elisabeth M. A. Strain; Scott Bennett; Scott D. Ling; Cayne Layton (Biodiversity and Conservation, 2024)
Kelp forests provide habitat for many species, but it remains uncertain whether specific kelp forest types support distinct biodiversity. Surface canopy-forming giant kelp ( Macrocystis pyrifera ) forests in Tasmania, Australia, have declined significantly due to climate change, and have been widely replaced by forests dominated by smaller stipitate kelps like Ecklonia radiata . However, there is limited knowledge of the community composition of Macrocystis forests and how this may differ from the stipitate kelp forest community. Underwater visual census surveys were conducted of the fishes and macroinvertebrates (> 2.5 cm length) in remnant Macrocystis forests in south-eastern Tasmania, and in adjacent stipitate kelp forests. 18 sites (9 of each forest type) were surveyed across two regions during the period of peak growth and canopy cover (i.e. winter-spring). Faunal community composition varied little between forest types, although Macrocystis forests supported more than double the abundance and biomass of mobile fishes, while cryptic fishes differed by forest type depending on region. Macroinvertebrate assemblages did not differ between forest types nor regions. Thus, for the taxa and time period examined, Tasmanian Macrocystis and stipitate kelp forests supported mostly similar faunal communities. Kelp forest communities showed spatial variation and were also likely influenced by a variety of other habitat characteristics, such as the relatively small patch sizes and/or ephemeral state of the remnant Macrocystis forests. Quantifying the community structure of these endangered communities informs the ecological changes that have occurred and will serve as an important reference for ongoing conservation and restoration activities.

Prenatal exposure to per- and polyfluoroalkyl substances and child behavioral problems - Jeong Weon Choi; Jiwon Oh; Deborah H. Bennett; Antonia M. Calafat; Rebecca J. Schmidt; Hyeong-Moo Shin (Environmental Research, 2024)

Modelling the spatial abundance of invasive deer and their impacts on vegetation at the landscape scale - Melissa Fedrigo; Ami Bennett; Stephen B. Stewart; David M. Forsyth; Joe Greet (Biological Invasions, 2024)
Deer populations and their impacts on forest ecosystems are increasing globally. Given the imperative and expense to mitigate impacts of invasive deer, we aimed to elucidate critical drivers of (i) deer density, (ii) deer impacts, and (iii) the relationship between them, to facilitate targeted management. We used quantile regression forests to model deer density (faecal pellet counts at 1948 locations) and impacts (browsing and other impacts on > 23,000 woody plants at 343 locations) across a mosaic of agricultural and forested ecosystems in Victoria, Australia (12,775 km 2 ). Climate, topography, vegetation cover, and distance to water features were included as model covariates. Modelled deer density ( r 2 = 0.71, MAE = 0.56 pellets/m 2 ) was most influenced by distance to waterbodies (> 10 ha, 31.2%), elevation (14.3%) and woody vegetation cover (12.9%). Modelled deer impact ( r 2 = 0.32, MAE = 6.9%) was most influenced by deer density (21.0%), mean annual precipitation (12.8%) and elevation (12.2%). Deer density was typically highest near large waterbodies, at low elevation, and with intermediate tree cover (40–70%). Impacts increased steadily with deer density up to ~ 2 pellets/m 2 . Our study demonstrates the importance of forest water and forest agricultural interfaces for both deer density and impacts. Deer are likely to be most abundant near waterbodies due to the availability of high-quality forage and water, and prefer lowland locations that have access to both open and forested habitats. Spatial models can be used to predict deer density and associated impacts to facilitate targeted invasive deer management.

Ants vs crabs: competition over seeds on a tropical island ecosystem - Richard M. Bennett-Vaz; Gabriel Arauz; Yosiat A. Vega-Rovira; Dumas Gálvez (Arthropod-Plant Interactions, 2024)

Composite substrates for coral larval settlement and reef restoration based on natural hydraulic lime and inorganic strontium and magnesium compounds - J. Yus; E.N. Nixon; J. Li; J. Noriega Gimenez; M-J. Bennett; D. Flores; K.L. Marhaver; L. Wegley Kelly; R.M. Espinosa-Marzal; A.J. Wagoner Johnson (Ecological Engineering, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

USDA’s Summer Meals During the COVID-19 Pandemic: A Mixed-Methods Examination of Participants and Non-Participants in 2021 - Brooke L. Bennett; Sarah L. McKee; Kara Burkholder; Sandra M. Chafouleas; Marlene B. Schwartz (Journal of the Academy of Nutrition and Dietetics, 2024)

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

Introducing Elinor for monitoring the governance and management of area‐based conservation - Shauna L. Mahajan; Samson Obiene; Lenice Ojwang; Nasser Olwero; Abel Valdivia; Adaoma Wosu; Emily Adrid; Dominic A. Andradi‐Brown; Gildas Andriamalala; Natalie C. Ban; Nathan J. Bennett; Jessica Blythe; et al. (Conservation Biology, 2024)
Monitoring the governance and management effectiveness of area‐based conservation has long been recognized as an important foundation for achieving national and global biodiversity goals and enabling adaptive management. However, there are still many barriers that prevent conservation actors, including those affected by governance and management systems from implementing conservation activities and programs and from gathering and using data on governance and management to inform decision‐making across spatial scales and through time. We explored current and past efforts to assess governance and management effectiveness and barriers actors face in using the resulting data and insights to inform conservation decision‐making. To help overcome these barriers, we developed Elinor, a free and open‐source monitoring tool that builds on the work of Nobel Prize winner Elinor Ostrom to facilitate the gathering, storing, sharing, analyzing, and use of data on environmental governance and management across spatial scales and for areas under different governance and management types. We consider the process of codesigning and piloting Elinor with conservation scientists and practitioners and the main components of the assessment and online data system. We also consider how Elinor complements existing approaches by addressing governance and management in a single assessment at a high level for different types of area‐based conservation, providing flexible options for data collection, and integrating a data system with an assessment that can support data use and sharing across different spatial scales, including global monitoring of the Global Biodiversity Framework. Although challenges will continue, the process of developing Elinor and the tool itself offer tangible solutions to barriers that prevent the systematic collection and use of governance and management data. With broader uptake, Elinor can play a valuable role in enabling more effective, inclusive, and durable area‐based conservation.

DeepN4: Learning N4ITK Bias Field Correction for T1-weighted Images - Praitayini Kanakaraj; Tianyuan Yao; Leon Y. Cai; Ho Hin Lee; Nancy R. Newlin; Michael E. Kim; Chenyu Gao; Kimberly R. Pechman; Derek Archer; Timothy Hohman; Angela Jefferson; Lori L. Beason-Held; et al. (Neuroinformatics, 2024)

Trends in flame retardant levels in upholstered furniture and children's consumer products after regulatory action in California - R. Gill; Q. Wang; S. Takaku-Pugh; E. Lytle; M. Wang; D.H. Bennett; J. Park; M. Petreas (Chemosphere, 2024)

Relational place-based solutions for environmental policy misalignments - Hannah M. Kobluk; Anne K. Salomon; Adam T. Ford; Andrew N. Kadykalo; Mateen A. Hessami; Pierre-Alexandre Labranche; Carmen Richter; Wendy J. Palen; ḥapinyuuk Tommy Happynook; Murray M. Humphries; Elena M. Bennett (Trends in Ecology & Evolution, 2024)

Wet and dry events influenced colonization of a mid-elevation Andean forest - R.A. Sales; C.N.H. McMichael; L.C. Peterson; A. Stanley; I. Bennett; T.E. Jones; A.S. Walker; M. Mulhearn; A. Nelson; C. Moore; M. O'Connor; W. Sinkler; et al. (Quaternary Science Reviews, 2024)

Structured decision making remains underused in ecological restoration despite opportunities - Morgan L. Piczak; Jessica A. Robichaud; Peter Morrison; Andrew M. Rous; Ingeborg M. Mulder; Cassandra J. Hill; Tanya S. Prystay; Hanna Rosner-Katz; Kelly F. Robinson; Joseph R. Bennett; Steven J. Cooke (Environment Systems and Decisions, 2024)

Single-molecule analysis of purified proteins and nuclear extracts: Insights from 8-oxoguanine glycosylase 1 - Matthew A. Schaich; Tyler M. Weaver; Vera Roginskaya; Bret D. Freudenthal; Bennett Van Houten (DNA Repair, 2024)

New Zealand rickettsia‐like organism and Tenacibaculum maritimum vaccine efficacy study - D. Jaramillo; B. P. Busby; M. Bestbier; P. Bennett; Z. Waddington (Journal of Fish Diseases, 2024)
A cohort of Chinook salmon juveniles was vaccinated, with an autogenous bivalent vaccine against New Zealand RLOs (NZ‐RLO1) and Tenacibaculum maritimum. A proportion of the cohort was not vaccinated to act as controls. At smoltification, the fish were challenged with NZ‐RLO1, NZ‐RLO2, or T. maritimum . We found that challenge with T. maritimum by immersion in (7.5 × 10 5 cfu/mL of water) did not yield any pathology. Challenge with RLOs produced clinical signs that were more or less severe depending on the challenge route, dose or vaccination status. Survival was significantly higher for vaccinated fish within the groups challenged with NZ‐RLO1 by intraperitoneal injection with a relative percent survival (RPS) of 48.84%. Survival was not significantly different between vaccinated and non‐vaccinated fish for groups challenged with NZ‐RLO2 by intraperitoneal injection or by NZ‐RLO1 by immersion. Yet, anecdotally the clinical disease presentation (manifesting as haemorrhagic, ulcerative skin lesions) was more severe for the non‐vaccinated fish. This study demonstrates that autogenous vaccine against NZ‐RLO is protective against severe disease and death by NZ‐RLO1 challenge which warrants implementation and further evaluation under field conditions. Yet, this study also highlights the importance of the route of administration and dose when evaluating pathogenicity and vaccine efficacy.

Sicklefin Chub (Macrhybopsis meeki) and Sturgeon Chub (M. gelida) Temporal and Spatial Patterns from Extant Population Monitoring and Habitat Data Spanning 23 Years - Mark L. Wildhaber; Benjamin M. West; Kendell R. Bennett; Jack H. May; Janice L. Albers; Nicholas S. Green (Fishes, 2024)
Sicklefin (Macrhybopsis meeki) and sturgeon chub (M. gelida) historically occurred throughout the Missouri River (MR), in some tributaries, and Mississippi River downstream of the MR. They have been species of U.S. state-level conservation concern and U.S. Endangered Species Act listing candidates since the 1990s. We applied analytical approaches from occupancy modeling to correlation to monitoring data spanning 23 years to assess relationships between occupancy and time, space, environmental factors, habitat, and other species. Sicklefin chub occupancy appeared higher in the early to mid-2000s and mid-to-late 2010s. A potential decline in occupancy occurred for sturgeon chub in the mid-to-late 2010s. Spatially, chub occupancy was depressed for 159 to 438 km downstream of MR dams. Among macrohabitats, inside bends had relatively high occupancy for both species; secondary connected channels had relatively high values for sturgeon chub. Co-occurrence was likely between sicklefin and sturgeon chub and between chubs and shovelnose sturgeon (Scaphirhybchus platorybchus) and channel catfish (Ictalurus punctatus). The observed co-occurrence of chubs and pallid sturgeon (Scaphirhynchus albus; PS) was potentially higher than expected for adult PS. For juvenile PS, co-occurrence was lower than expected in the Lower MR and potentially higher than expected in the Upper MR, warranting future research. Results from this research suggest management for the improvement of sicklefin and sturgeon chub populations may benefit other MR fish populations.

Effects of temperature and microbial disruption on juvenile kelp Ecklonia radiata and its associated bacterial community - Sebastian Vadillo Gonzalez; Catriona L. Hurd; Damon Britton; Eloise Bennett; Peter D. Steinberg; Ezequiel M. Marzinelli (Frontiers in Marine Science, 2024)
Ocean warming can affect the development and physiological responses of kelps, and under future climate change scenarios, increasing seawater temperatures pose a major threat to these habitat-forming species. However, little is known about the effects of warming on epiphytic bacterial communities and how an altered microbiome may interact with temperature stress, affecting the condition and survival of kelp, particularly of the potentially more vulnerable early life stages. Here, we tested the effects of thermal stress on the growth and physiological responses of juvenile kelp Ecklonia radiata in which their epiphytic bacterial community was experimentally disrupted using antimicrobials, simulating dysbiosis. We hypothesized that, under thermal stress (23°C, simulating a extreme scenario of ocean warming in Tasmania), kelp with a disrupted bacterial community would be more strongly affected than kelp with an undisrupted microbiome or kelp under ambient temperature (14°C) but with a disrupted microbiota. Thermal stress reduced growth, increased tissue bleaching and negatively affected net photosynthesis of kelp. In addition, a substantial change in the epiphytic bacterial community structure was also found under thermal stress conditions, with an increase in the abundance of potentially pathogenic bacterial groups. However, microbial disruption did not act synergistically with thermal stress to affect kelp juveniles. These results suggest that effects of elevated temperature on juvenile kelps is not microbially-mediated and that juveniles may be less susceptible to disruptions of their microbiome.

A horizon scan of global biological conservation issues for 2024 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Stuart H.M. Butchart; Holly M. Butterworth; Stewart J. Clarke; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jennifer James; et al. (Trends in Ecology & Evolution, 2024)

Exome-informed formulations of food proteins enhance body growth and feed conversion efficiency in ad libitum-fed mice - Tong Wu; Davaatseren Baatar; Anne E. O' Connor; Moira K. O'Bryan; Jessica M. Stringer; Karla J. Hutt; Minoli Malimige Aponso; Keyne Monro; Jiaqiang Luo; Yingchun Zhu; Andreas Ernst; Elyse O.K. Swindells; et al. (Food Research International, 2024)

Lovers, not fighters: docility influences reproductive fitness, but not survival, in male Cape ground squirrels, Xerus inauris - Miyako H. Warrington; Sienna Beaulieu; Riley Jellicoe; Sjoerd Vos; Nigel C. Bennett; Jane M. Waterman (Behavioral Ecology and Sociobiology, 2024)
Over their lifetime, individuals may use different behavioural strategies to maximize their fitness. Some behavioural traits may be consistent among individuals over time (i.e., ‘personality’ traits) resulting in an individual behavioural phenotype with different associated costs and benefits. Understanding how behavioural traits are linked to lifetime fitness requires tracking individuals over their lifetime. Here, we leverage a long-term study on a multi-year living species (maximum lifespan ~ 10 years) to examine how docility (an individual’s reaction to trapping and handling) may contribute to how males are able to maximize their lifetime fitness. Cape ground squirrels are burrowing mammals that live in social groups, and although males lack physical aggression and territoriality, they vary in docility. Males face high predation risk and high reproductive competition and employ either of two reproductive tactics (‘natal’ or ‘band’) which are not associated with different docility personalities. We found that although more docile individuals sired more offspring on an annual basis, docility did not affect an individual’s long-term (lifetime) reproductive output. Survival was not associated with docility or body condition, but annual survival was influenced by rainfall. Our findings suggest that although docility may represent a behavioural strategy to maximize fitness by possibly playing a role in female-male associations or female mate-choice, variations in docility within our study population is likely maintained by other environmental drivers. However, individual variations in behaviours may still contribute as part of the ‘tool kit’ individuals use to maximize their lifetime fitness.

Managing mineral phosphorus application with soil residual phosphorus reuse in Canada - Jiaxin Wang; Zhiming Qi; Elena M. Bennett (Global Change Biology, 2024)
With limited phosphorus (P) supplies, increasing P demand, and issues with P runoff and pollution, developing an ability to reuse the large amounts of residual P stored in agricultural soils is increasingly important. In this study, we investigated the potential for residual soil P to maintain crop yields while reducing P applications and losses in Canada. Using a P cycling model coupled with a soil P dynamics model, we analyzed soil P dynamics over 110 years across Canada's provinces. We found that using soil residual P may reduce mineral P demand as large as 132 Gg P year −1 (29%) in Canada, with the highest potential for reducing P applications in the Atlantic provinces, Quebec, Ontario, and British Columbia. Using residual soil P would result in a 21% increase in Canada's cropland P use efficiency. We expected that the Atlantic provinces and Quebec would have the greatest runoff P loss reduction with use of residual soil P, with the average P loss rate decreasing from 4.24 and 1.69 kg ha −1 to 3.45 and 1.38 kg ha −1 , respectively. Ontario, Manitoba, and British Columbia would experience relatively lower reductions in P loss through use of residual soil P, with the average runoff P loss rate decreasing from 0.44, 0.36, and 4.33 kg ha −1 to 0.19, 0.26, and 4.14 kg ha −1 , respectively. Our study highlights the importance of considering residual soil P as a valuable resource and its potential for reducing P pollution.

Global patterns and drivers of plant–soil microbe interactions - Feng Jiang; Jonathan A. Bennett; Kerri M. Crawford; Johannes Heinze; Xucai Pu; Ao Luo; Zhiheng Wang (Ecology Letters, 2024)
Plant–soil feedback (PSF) is an important mechanism determining plant community dynamics and structure. Understanding the geographic patterns and drivers of PSF is essential for understanding the mechanisms underlying geographic plant diversity patterns. We compiled a large dataset containing 5969 observations of PSF from 202 studies to demonstrate the global patterns and drivers of PSF for woody and non‐woody species. Overall, PSF was negative on average and was influenced by plant attributes and environmental settings. Woody species PSFs did not vary with latitude, but non‐woody PSFs were more negative at higher latitudes. PSF was consistently more positive with increasing aridity for both woody and non‐woody species, likely due to increased mutualistic microbes relative to soil‐borne pathogens. These findings were consistent between field and greenhouse experiments, suggesting that PSF variation can be driven by soil legacies from climates. Our findings call for caution to use PSF as an explanation of the latitudinal diversity gradient and highlight that aridity can influence plant community dynamics and structure across broad scales through mediating plant–soil microbe interactions.

Associations between area-level arsenic exposure and adverse birth outcomes: An Echo-wide cohort analysis - Jonathan V. Lewis; Emily A. Knapp; Shivani Bakre; Aisha S. Dickerson; Theresa M. Bastain; Casper Bendixsen; Deborah H. Bennett; Carlos A. Camargo; Andrea E. Cassidy-Bushrow; Elena Colicino; Viren D’Sa; Dana Dabelea; et al. (Environmental Research, 2023)

Effects of short-chain per- and polyfluoroalkyl substances (PFAS) on toxicologically relevant gene expression profiles in a liver-on-a-chip model - Megan E. Solan; Bennett Schackmuth; Erica D. Bruce; Sahar Pradhan; Christie M. Sayes; Ramon Lavado (Environmental Pollution, 2023)

Titanium and iron isotopic records of granitoid crust production in diverse Archean cratons - Zhe J. Zhang; Nicolas Dauphas; Aleisha C. Johnson; Sarah M. Aarons; Vickie C. Bennett; Allen P. Nutman; Scott MacLennan; Blair Schoene (Earth and Planetary Science Letters, 2023)

Lead exposure of mainland Australia's top avian predator - Jordan O. Hampton; Michael T. Lohr; Aaron J. Specht; Damien Nzabanita; Jasmin Hufschmid; Lee Berger; Kate McGinnis; Jane Melville; Emma Bennett; James M. Pay (Environmental Pollution, 2023)

The biology of an isolated Mashona mole-rat population from southern Malawi, with implications for the diversity and biogeography of the genus Fukomys - R. Šumbera; M. Uhrová; S. Begall; K. R. Caspar; D. Jerkovičová; P. Van Daele; W. N. Chitaukali; C. G. Faulkes; N. C. Bennett; C. Johannes; H. Burda; O. Mikula (Organisms Diversity & Evolution, 2023)
The Mashona mole-rat, Fukomys darlingi (Thomas, 1895), is a little studied social African mole-rat (Bathyergidae) from south-astern Africa. Here, we present an integrative study characterizing the genetic diversity of populations assigned to F. darlingi with special focus on animals from Nsanje, southern Malawi. These mole-rats show pronounced differences in body mass and general appearance compared to nominate F. darlingi from Zimbabwe and Mozambique, but their taxonomic status has so far remained unclear. A genetic analysis encompassing all major lineages of the genus Fukomys suggests that this population indeed represents a deeply nested lineage within the F. darlingi clade . The karyotype of the Nsanje mole-rats also corresponds to that of the nominate form, being 2n = 54. While both nuclear and mitochondrial data agree about the assignment of the Nsanje mole-rats to F. darlingi , our analyses revealed substantial mitonuclear discordance for other branches within the Fukomys phylogenetic tree. Nsanje mole-rats are significantly larger than nominate F. darlingi and their ontogeny and reproduction closely resemble similar-sized congeneric species rather than the nominate population. The somatic growth of the Nsanje form is the slowest of all African mole-rats. The maximum life span of F. darlingi is at least 19 years. The observed differences between nominate F. darlingi and mole-rats from Nsanje may be attributed mainly to their different body mass. Our study highlights the advantages of an integrative approach for understanding the diversity of African mole-rats and emphasizes the great intraspecific variability that may be encountered in these underground-dwelling rodents.

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

Blur remediation in NEAR MSI images - D.R. Golish; D.N. DellaGiustina; K.J. Becker; C.A. Bennett; M. Robinson; M.K. Crombie (Icarus, 2023)

A legal assessment of private land conservation in South America - Rocío López de la Lama; Nathan Bennett; Janette Bulkan; David Boyd; Kai M. A. Chan (Conservation Biology, 2023)
Privately protected areas (PPAs) are a potentially innovative conservation tool. Legal recognition is necessary for their success, especially where there are institutional challenges to nature conservation, such as in South America. Although PPAs have increased in South America since the early 2000s, there is a critical information gap pertaining to their legal frameworks. We analyzed the level of landowner commitment to and governmental support for PPAs across countries in South America that officially recognize PPAs. We analyzed the legal framework governing PPAs and reviewed literature on them. This process was done in English and Spanish. The information we gathered was validated by 16 conservation experts from 10 South American countries. Because Peru is 1 of only 2 South American countries where local communities create and manage PPAs, we studied Peruvian PPAs in more detail by examining official creation documents and interviewing 13 local conservation professionals. We found inadequate minimum duration of PPAs and vague guidelines for conducting economic activities within them and a lack of governmental support (e.g., financial and technical support) for PPAs. Support was limited to the exemption from rural property taxes, which are relatively low compared with countries outside South America. In Peru, PPAs run by individuals and communities needed different legal frameworks because they were created with different objectives and had different sizes and duration of commitments. The prompt improvement of legal frameworks across South America is necessary for PPAs to achieve their aim of being places for enduring nature conservation in the region.

Marine reserve use by a migratory coastal shark, Carcharias taurus - Ross G. Dwyer; Michaela Rathbone; Deborah L. Foote; Mike Bennett; Paul A. Butcher; Nicholas M. Otway; Brett M. Louden; Fabrice R.A. Jaine; Craig E. Franklin; Carley Kilpatrick (Biological Conservation, 2023)

Gravel grabs: The rocky foundations of Indigenous geologic power in the Arctic - Mia M. Bennett (Ambio, 2023)

Mapping the unjust global distribution of harmful fisheries subsidies - Daniel J. Skerritt; Anna Schuhbauer; Sebastian Villasante; Andrés M. Cisneros-Montemayor; Nathan J. Bennett; Tabitha G. Mallory; Vicky W.L. Lam; Robert I. Arthur; William W.L. Cheung; Louise S.L. Teh; Katina Roumbedakis; Maria L.D. Palomares; et al. (Marine Policy, 2023)

Attitudes, Knowledge, and Perceived Barriers Towards Cancer Pain Management Among Healthcare Professionals in Libya: a National Multicenter Survey - Salim M. Makhlouf; Shenaz Ahmed; Matthew Mulvey; Michael I. Bennett (Journal of Cancer Education, 2023)
Cancer pain presents in approximately 66% of patients in advanced stages. Although several guidelines and pharmacological options are available for cancer pain management (CPM), assessment and treatment of cancer pain remain inadequate globally, particularly in developing countries. Lack of knowledge and negative attitudes towards CPM among healthcare professionals (HCPs) are important barriers to CPM. This survey aimed to evaluate nurses’ and physicians’ knowledge, attitudes, and potential barriers regarding CPM in Libya. This cross-sectional survey involved a convenience sample of 152 oncology nurses and physicians working in six oncology settings in Libya. The response rate was 76%. The Barriers Questionnaire II (BQ-II) was used for data collection (higher scores signify greater attitudinal barriers and poorer knowledge). Data analysis was carried out using Statistical Package for Social Sciences (SPSS), version 26 software. An independent t -test (unadjusted estimate) indicated that Libyan nurses showed higher mean barrier scores (mean = 3.8, SD = 0.7) to CPM than physicians (mean = 2.9, SD = 0.8), p < 0.001. The six most common differences in attitudinal barriers between nurses and physicians were “opioid side effects,” “poor tolerance,” “strong patient endures pain,” “distract the physician,” “drug addiction,” and “opioids impair immune function,” p < 0.001. Multiple regression results (adjusted estimate) indicated that nurses had more barrier scores to CPM than physicians (B = − 0.530, p < 0.05), and participants with higher educational levels were associated with lower barrier scores to CPM (B = − 0.641, p < 0.05). Our results suggest that Libyan oncology HCPs hold perceived barriers, lack of knowledge, and negative attitudes towards CPM. Professional education and training in CPM, addressing phobia and myths on opioid usage, and the benefits and complications of using opioids are likely to result in reduced barriers to CPM in Libya.

Prenatal sound experience affects song preferences in male zebra finches - Andrew C. Katsis; Andrew T.D. Bennett; Katherine L. Buchanan; Sonia Kleindorfer; Mylene M. Mariette (Animal Behaviour, 2023)

PlantACT! – how to tackle the climate crisis - Heribert Hirt; Salim Al-Babili; Marilia Almeida-Trapp; Antoine Martin; Manuel Aranda; Dorothea Bartels; Malcolm Bennett; Ikram Blilou; Damian Boer; Alix Boulouis; Chris Bowler; Sophie Brunel-Muguet; et al. (Trends in Plant Science, 2023)

Thermal Tolerance of Juvenile New England Chain Catsharks, Scyliorhinus Retifer Garman, 1881 (Chondrichthyes, Carcharhiniformes, Scyliorhinidae) - Cynthia E. M. Lupton; Wayne A. Bennett (Thalassas: An International Journal of Marine Sciences, 2023)

Search for CP violation and measurement of branching fractions and decay asymmetry parameters for Λ c + → Λ h + and Λ c + → Σ 0 h + ( h = K , π ) - L.K. Li; W. Shan; K. Kinoshita; I. Adachi; H. Aihara; D.M. Asner; H. Atmacan; T. Aushev; V. Babu; S. Bahinipati; Sw. Banerjee; P. Behera; et al. (Science Bulletin, 2023)

Complex crop rotations improve organic nitrogen cycling - Lauren C. Breza; Maria Mooshammer; Timothy M. Bowles; Virginia L. Jin; Marty R. Schmer; Bennett Thompson; A. Stuart Grandy (Soil Biology and Biochemistry, 2023)

Investing in nature-based solutions: Cost profiles of collective-action watershed investment programs - Shiteng Kang; Timm Kroeger; Daniel Shemie; Marta Echavarria; Tamara Montalvo; Leah L. Bremer; Genevieve Bennett; Samuel Roiphe Barreto; Henrique Bracale; Claudia Calero; Aldo Cardenas; Julián Cardona; et al. (Ecosystem Services, 2023)

Angiotensin receptor blocker use is associated with upregulation of the memory-protective angiotensin type 4 receptor (AT4R) in the postmortem brains of individuals without cognitive impairment - Caglar Cosarderelioglu; Lolita S. Nidadavolu; Claudene J. George; Ruth Marx-Rattner; Laura Powell; Qian-Li Xue; Jing Tian; Esther S. Oh; Luigi Ferrucci; Pervin Dincer; David A. Bennett; Jeremy D. Walston; et al. (GeroScience, 2023)

High-resolution wave data for improving marine habitat suitability models - Chiara M. Bertelli; William G. Bennett; Harshinie Karunarathna; Dominic E. Reeve; Richard K. F. Unsworth; James C. Bull (Frontiers in Marine Science, 2023)
Habitat suitability modelling (HSM) is a tool that is increasingly being used to help guide decision making for conservation management. It can also be used to focus efforts of restoration in our oceans. To improve on model performance, the best available environmental data along with species distribution data are needed. Marine habitats tend to have ecological niches defined by physical environmental conditions and of particular importance for shallow water species is wave energy. In this study we examined the relative improvements to HSM outputs that could be achieved by producing high-resolution Delft-3D modelled wave height data to see if model predictions at a fine-scale can be improved. Seagrasses were used as an exemplar and comparisons at fine-scale showed considerable differences in the area predicted suitable for seagrass growth and greatly increased the importance of waves as a predictor variable when compared with open-source low resolution wave energy data.

Environmental (in)justice in the Anthropocene ocean - Nathan J. Bennett; Juan José Alava; Caroline E. Ferguson; Jessica Blythe; Elisa Morgera; David Boyd; Isabelle M. Côté (Marine Policy, 2023)

A global biological conservation horizon scan of issues for 2023 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Holly M. Butterworth; Mick N. Clout; Isabelle M. Côté; Jason Dinsdale; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice Hughes; et al. (Trends in Ecology & Evolution, 2023)

Polymorphism of the follicle stimulating hormone receptor does not impact reproductive performance or in-vitro embryo production in beef heifers - Alexandria P. Snider; Hannah K. Yake; Camryn D. Granger; Shelby L. Rosasco; Tara G. McDaneld; Warren M. Snelling; Chad C. Chase; Jeremy R. Miles; Clay A. Lents; Lacey K. Quail; Jerica J.J. Rich; Kaitlin M. Epperson; et al. (Theriogenology, 2023)

Vulnerable Waters are Essential to Watershed Resilience - Charles R. Lane; Irena F. Creed; Heather E. Golden; Scott G. Leibowitz; David M. Mushet; Mark C. Rains; Qiusheng Wu; Ellen D’Amico; Laurie C. Alexander; Genevieve A. Ali; Nandita B. Basu; Micah G. Bennett; et al. (Ecosystems, 2023)
Watershed resilience is the ability of a watershed to maintain its characteristic system state while concurrently resisting, adapting to, and reorganizing after hydrological (for example, drought, flooding) or biogeochemical (for example, excessive nutrient) disturbances. Vulnerable waters include non-floodplain wetlands and headwater streams, abundant watershed components representing the most distal extent of the freshwater aquatic network. Vulnerable waters are hydrologically dynamic and biogeochemically reactive aquatic systems, storing, processing, and releasing water and entrained (that is, dissolved and particulate) materials along expanding and contracting aquatic networks. The hydrological and biogeochemical functions emerging from these processes affect the magnitude, frequency, timing, duration, storage, and rate of change of material and energy fluxes among watershed components and to downstream waters, thereby maintaining watershed states and imparting watershed resilience. We present here a conceptual framework for understanding how vulnerable waters confer watershed resilience. We demonstrate how individual and cumulative vulnerable-water modifications (for example, reduced extent, altered connectivity) affect watershed-scale hydrological and biogeochemical disturbance response and recovery, which decreases watershed resilience and can trigger transitions across thresholds to alternative watershed states (for example, states conducive to increased flood frequency or nutrient concentrations). We subsequently describe how resilient watersheds require spatial heterogeneity and temporal variability in hydrological and biogeochemical interactions between terrestrial systems and down-gradient waters, which necessitates attention to the conservation and restoration of vulnerable waters and their downstream connectivity gradients. To conclude, we provide actionable principles for resilient watersheds and articulate research needs to further watershed resilience science and vulnerable-water management.

The P2X1 receptor as a therapeutic target - Felix M. Bennetts; Jesse I. Mobbs; Sabatino Ventura; David M. Thal (Purinergic Signalling, 2022)
Within the family of purinergic receptors, the P2X1 receptor is a ligand-gated ion channel that plays a role in urogenital, immune and cardiovascular function. Specifically, the P2X1 receptor has been implicated in controlling smooth muscle contractions of the vas deferens and therefore has emerged as an exciting drug target for male contraception. In addition, the P2X1 receptor contributes to smooth muscle contractions of the bladder and is a target to treat bladder dysfunction. Finally, platelets and neutrophils have populations of P2X1 receptors that could be targeted for thrombosis and inflammatory conditions. Drugs that specifically target the P2X1 receptor have been challenging to develop, and only recently have small molecule antagonists of the P2X1 receptor been available. However, these ligands need further biological validation for appropriate selectivity and drug-like properties before they will be suitable for use in preclinical models of disease. Although the atomic structure of the P2X1 receptor has yet to be determined, the recent discovery of several other P2X receptor structures and improvements in the field of structural biology suggests that this is now a distinct possibility. Such efforts may significantly improve drug discovery efforts at the P2X1 receptor.

Rank change and growth within social hierarchies of the orange clownfish, Amphiprion percula - L. M. Fitzgerald; H. B. Harrison; D. J. Coker; P. Sáenz-Agudelo; M. Srinivasan; J. E. Majoris; L. Boström Einarsson; B. Pujol; M. Bennett-Smith; S. R. Thorrold; S. Planes; G. P. Jones; et al. (Marine Biology, 2022)
Social hierarchies within groups define the distribution of resources and provide benefits that support the collective group or favor dominant members. The progression of individuals through social hierarchies is a valuable characteristic for quantifying population dynamics. On coral reefs, some clownfish maintain size-based hierarchical communities where individuals queue through social ranks. The cost of waiting in a lower-ranked position is outweighed by the reduced risk of eviction and mortality. The orange clownfish, Amphiprion percula , maintains stable social groups with subordinate individuals queuing to be part of the dominant breeding pair. Strong association with their host anemone, complex social interactions, and relatively low predation rates make them ideal model organisms to assess changes in group dynamics through time in their natural environment. Here, we investigate the rank changes and isometric growth rates of A. percula from 247 naturally occurring social groups in Kimbe Island, Papua New Guinea (5° 12′ 13.54″ S, 150° 22′ 32.69″ E). We used DNA profiling to assign and track individuals over eight years between 2011 and 2019. Over half of the individuals survived alongside two or three members of their original social group, with twelve breeding pairs persisting over the study period. Half of the surviving individuals increased in rank and experienced double the growth rate of those that maintained their rank. Examining rank change in a wild fish population provides new insights into the complex social hierarchies of reef fishes and their role in social evolution.

Infection‐competent monkeypox virus contamination identified in domestic settings following an imported case of monkeypox into the UK - Barry Atkinson; Christopher Burton; Thomas Pottage; Katy‐Anne Thompson; Didier Ngabo; Ant Crook; James Pitman; Sian Summers; Kuiama Lewandowski; Jenna Furneaux; Katherine Davies; Timothy Brooks; et al. (Environmental Microbiology, 2022)
An imported case of monkeypox was diagnosed in December 2019 in a traveller returning from Nigeria to the UK. Subsequently, environmental sampling was performed at two adjoining single‐room residences occupied by the patient and their sibling. Monkeypox virus DNA was identified in multiple locations throughout both properties, and monkeypox virus was isolated from several samples 3 days after the patient was last in these locations. Positive samples were identified following the use of both vacuum and surface sampling techniques; these methodologies allowed for environmental analysis of potentially contaminated porous and non‐porous surfaces via real‐time quantitative reverse transcriptase PCR analysis in addition to viral isolation to confirm the presence of infection‐competent virus. This report confirms the potential for infection‐competent monkeypox virus to be recovered in environmental settings associated with known positive cases and the necessity for rapid environmental assessment to reduce potential exposure to close contacts and the general public. The methods adopted in this investigation may be used for future confirmed cases of monkeypox in order to establish levels of contamination, confirm the presence of infection‐competent material and to identify locations requiring additional cleaning.

Nitrogen and Sulfur Deposition Reductions Projected to Partially Restore Forest Soil Conditions in the US Northeast, While Understory Composition Continues to Shift with Future Climate Change - Stephen D. LeDuc; Christopher M. Clark; Jennifer Phelan; Salim Belyazid; Micah G. Bennett; Katie Boaggio; John Buckley; Jamie Cajka; Phillip Jones (Water, Air, & Soil Pollution, 2022)

Emotion Recognition and Traumatic Brain Injury: a Systematic Review and Meta-Analysis - Jillian M. Murphy; Joanne M. Bennett; Xochitl de la Piedad Garcia; Megan L. Willis (Neuropsychology Review, 2022)

Earth stewardship: Shaping a sustainable future through interacting policy and norm shifts - F. Stuart Chapin; Elke U. Weber; Elena M. Bennett; Reinette Biggs; Jeroen van den Bergh; W. Neil Adger; Anne-Sophie Crépin; Stephen Polasky; Carl Folke; Marten Scheffer; Kathleen Segerson; John M. Anderies; et al. (Ambio, 2022)
Transformation toward a sustainable future requires an earth stewardship approach to shift society from its current goal of increasing material wealth to a vision of sustaining built, natural, human, and social capital—equitably distributed across society, within and among nations. Widespread concern about earth’s current trajectory and support for actions that would foster more sustainable pathways suggests potential social tipping points in public demand for an earth stewardship vision. Here, we draw on empirical studies and theory to show that movement toward a stewardship vision can be facilitated by changes in either policy incentives or social norms. Our novel contribution is to point out that both norms and incentives must change and can do so interactively. This can be facilitated through leverage points and complementarities across policy areas, based on values, system design, and agency. Potential catalysts include novel democratic institutions and engagement of non-governmental actors, such as businesses, civic leaders, and social movements as agents for redistribution of power. Because no single intervention will transform the world, a key challenge is to align actions to be synergistic, persistent, and scalable.

Aging and white matter microstructure and macrostructure: a longitudinal multi-site diffusion MRI study of 1218 participants - Kurt G. Schilling; Derek Archer; Fang-Cheng Yeh; Francois Rheault; Leon Y. Cai; Colin Hansen; Qi Yang; Karthik Ramdass; Andrea T. Shafer; Susan M. Resnick; Kimberly R. Pechman; Katherine A. Gifford; et al. (Brain Structure and Function, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Closing the knowledge‐action gap in conservation with open science - Dominique G. Roche; Rose E. O'Dea; Kecia A. Kerr; Trina Rytwinski; Richard Schuster; Vivian M. Nguyen; Nathan Young; Joseph R. Bennett; Steven J. Cooke (Conservation Biology, 2022)
The knowledge‐action gap in conservation science and practice occurs when research outputs do not result in actions to protect or restore biodiversity. Among the diverse and complex reasons for this gap, three barriers are fundamental: knowledge is often unavailable to practitioners and challenging to interpret or difficult to use or both. Problems of availability, interpretability, and useability are solvable with open science practices. We considered the benefits and challenges of three open science practices for use by conservation scientists and practitioners. First, open access publishing makes the scientific literature available to all. Second, open materials (detailed methods, data, code, and software) increase the transparency and use of research findings. Third, open education resources allow conservation scientists and practitioners to acquire the skills needed to use research outputs. The long‐term adoption of open science practices would help researchers and practitioners achieve conservation goals more quickly and efficiently and reduce inequities in information sharing. However, short‐term costs for individual researchers (insufficient institutional incentives to engage in open science and knowledge mobilization) remain a challenge. We caution against a passive approach to sharing that simply involves making information available. We advocate a proactive stance toward transparency, communication, collaboration, and capacity building that involves seeking out and engaging with potential users to maximize the environmental and societal impact of conservation science.

Seagrass Thermal Limits and Vulnerability to Future Warming - Núria Marbà; Gabriel Jordà; Scott Bennett; Carlos M. Duarte (Frontiers in Marine Science, 2022)
Seagrasses have experienced major losses globally mostly attributed to human impacts. Recently they are also associated with marine heat waves. The paucity of information on seagrass mortality thermal thresholds prevents the assessment of the risk of seagrass loss under marine heat waves. We conducted a synthesis of reported empirically- or experimentally-determined seagrass upper thermal limits (T limit ) and tested the hypothesis that they increase with increasing local annual temperature. We found that T limit increases 0.42± 0.07°C per°C increase in in situ annual temperature (R 2 = 0.52). By combining modelled seagrass T limit across global coastal areas with current and projected thermal regimes derived from an ocean reanalysis and global climate models (GCMs), we assessed the proximity of extant seagrass meadows to their T limit and the time required for T limit to be met under high (RCP8.5) and moderate (RCP4.5) emission scenarios of greenhouse gases. Seagrass meadows worldwide showed a modal difference of 5°C between present T max and seagrass T limit . This difference was lower than 3°C at the southern Red Sea, the Arabian Gulf, the Gulf of Mexico, revealing these are the areas most in risk of warming-derived seagrass die-off, and up to 24°C at high latitude regions. Seagrasses could meet their T limit regularly in summer within 50-60 years or 100 years under, respectively, RCP8.5 or RCP4.5 scenarios for the areas most at risk, to more than 200 years for the Arctic under both scenarios. This study shows that implementation of the goals under the Paris Agreement would safeguard much of global seagrass from heat-derived mass mortality and identifies regions where actions to remove local anthropogenic stresses would be particularly relevant to meet the Target 10 of the Aichi Targets of the Convention of the Biological Diversity.

A Scientific Synthesis of Marine Protected Areas in the United States: Status and Recommendations - Jenna Sullivan-Stack; Octavio Aburto-Oropeza; Cassandra M. Brooks; Reniel B. Cabral; Jennifer E. Caselle; Francis Chan; J. Emmett Duffy; Daniel C. Dunn; Alan M. Friedlander; Heather K. Fulton-Bennett; Steven D. Gaines; Leah R. Gerber; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs) are a key tool for achieving goals for biodiversity conservation and human well-being, including improving climate resilience and equitable access to nature. At a national level, they are central components in the U.S. commitment to conserve at least 30% of U.S. waters by 2030. By definition, the primary goal of an MPA is the long-term conservation of nature; however, not all MPAs provide the same ecological and social benefits. A U.S. system of MPAs that is equitable, well-managed, representative and connected, and includes areas at a level of protection that can deliver desired outcomes is best positioned to support national goals. We used a new MPA framework, The MPA Guide, to assess the level of protection and stage of establishment of the 50 largest U.S. MPAs, which make up 99.7% of the total U.S. MPA area (3.19 million km 2 ). Over 96% of this area, including 99% of that which is fully or highly protected against extractive or destructive human activities, is in the central Pacific ocean. Total MPA area in other regions is sparse – only 1.9% of the U.S. ocean excluding the central Pacific is protected in any kind of MPA (120,976 km 2 ). Over three quarters of the non-central Pacific MPA area is lightly or minimally protected against extractive or destructive human activities. These results highlight an urgent need to improve the quality, quantity, and representativeness of MPA protection in U.S. waters to bring benefits to human and marine communities. We identify and review the state of the science, including focal areas for achieving desired MPA outcomes and lessons learned from places where sound ecological and social design principles come together in MPAs that are set up to achieve national goals for equity, climate resilience, and biodiversity conservation. We recommend key opportunities for action specific to the U.S. context, including increasing funding, research, equity, and protection level for new and existing U.S. MPAs.

Estrogen Enhances Dendrite Spine Function and Recovers Deficits in Neuroplasticity in the prpTDP-43A315T Mouse Model of Amyotrophic Lateral Sclerosis - Emily E. Handley; Laura A. Reale; Jyoti A. Chuckowree; Marcus S. Dyer; Grace L. Barnett; Courtney M. Clark; William Bennett; Tracey C. Dickson; Catherine A. Blizzard (Molecular Neurobiology, 2022)
Amyotrophic lateral sclerosis (ALS) attacks the corticomotor system, with motor cortex function affected early in disease. Younger females have a lower relative risk of succumbing to ALS than males and older females, implicating a role for female sex hormones in disease progression. However, the mechanisms driving this dimorphic incidence are still largely unknown. We endeavoured to determine if estrogen mitigates disease progression and pathogenesis, focussing upon the dendritic spine as a site of action. Using two-photon live imaging we identify, in the prp TDP-43 A315T mouse model of ALS, that dendritic spines in the male motor cortex have a reduced capacity for remodelling than their wild-type controls. In contrast, females show higher capacity for remodelling, with peak plasticity corresponding to highest estrogen levels during the estrous cycle. Estrogen manipulation through ovariectomies and estrogen replacement with 17β estradiol in vivo was found to significantly alter spine density and mitigate disease severity. Collectively, these findings reveal that synpatic plasticity is reduced in ALS, which can be amelioriated with estrogen, in conjuction with improved disease outcomes.

Does bait type and bait container configuration influence the performance of remote underwater video systems in temperate freshwater lakes for assessing fish community structure? - D. M. Glassman; A. Chhor; J. C. Vermaire; J. R. Bennett; S. J. Cooke (Hydrobiologia, 2022)

Governance in the Face of Extreme Events: Lessons from Evolutionary Processes for Structuring Interventions, and the Need to Go Beyond - Simon A. Levin; John M. Anderies; Neil Adger; Scott Barrett; Elena M. Bennett; Juan Camilo Cardenas; Stephen R. Carpenter; Anne-Sophie Crépin; Paul Ehrlich; Joern Fischer; Carl Folke; Nils Kautsky; et al. (Ecosystems, 2022)

Image to attribute model for trees (ITAM-T): individual tree detection and classification in Alberta boreal forest for wildland fire fuel characterization - L. Bennett; B. Wilson; S. Selland; L. Qian; M. Wood; H. Zhao; J. Boisvert (International Journal of Remote Sensing, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Genome-wide analysis of mitochondrial DNA copy number reveals loci implicated in nucleotide metabolism, platelet activation, and megakaryocyte proliferation - R. J. Longchamps; S. Y. Yang; C. A. Castellani; W. Shi; J. Lane; M. L. Grove; T. M. Bartz; C. Sarnowski; C. Liu; K. Burrows; A. L. Guyatt; T. R. Gaunt; et al. (Human Genetics, 2022)
Mitochondrial DNA copy number (mtDNA-CN) measured from blood specimens is a minimally invasive marker of mitochondrial function that exhibits both inter-individual and intercellular variation. To identify genes involved in regulating mitochondrial function, we performed a genome-wide association study (GWAS) in 465,809 White individuals from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (UKB). We identified 133 SNPs with statistically significant, independent effects associated with mtDNA-CN across 100 loci. A combination of fine-mapping, variant annotation, and co-localization analyses was used to prioritize genes within each of the 133 independent sites. Putative causal genes were enriched for known mitochondrial DNA depletion syndromes ( p = 3.09 × 10 –15 ) and the gene ontology (GO) terms for mtDNA metabolism ( p = 1.43 × 10 –8 ) and mtDNA replication ( p = 1.2 × 10 –7 ). A clustering approach leveraged pleiotropy between mtDNA-CN associated SNPs and 41 mtDNA-CN associated phenotypes to identify functional domains, revealing three distinct groups, including platelet activation, megakaryocyte proliferation, and mtDNA metabolism. Finally, using mitochondrial SNPs, we establish causal relationships between mitochondrial function and a variety of blood cell-related traits, kidney function, liver function and overall ( p = 0.044) and non-cancer mortality ( p = 6.56 × 10 –4 ).

A framework for assessing coupling and de-coupling trajectories in river social-ecological systems - Cristina Quintas-Soriano; Jodi Brandt; Colden V. Baxter; Elena M. Bennett; Juan Miguel Requena-Mullor; Antonio J. Castro (Sustainability Science, 2022)
The degree of coupling between the social and ecological components of social-ecological systems is seen as fundamental to understanding their functioning, interactions and trajectories. Yet, there is limited work about how to empirically understand the degree of coupling between social and ecological systems, nor the processes by which the degree of coupling could change over time. Here, we introduce a conceptual framework for characterizing trajectories over time of coupling and de-coupling in social-ecological river systems. We analyze two conceptual scenarios describing coupling and de-coupling trajectories in a social-ecological system and define a series of key concepts for understanding social-ecological system trajectories. We tested these coupling and de-coupling trajectories theory by linking these concepts to empirical case examples of two river social-ecological systems in the western United States. Finally, we propose a quantitative approach with the potential for evaluating the level of social-ecological coupling and de-coupling trajectories in other SES contexts. This paper represents an advancing on the identification of specific actions that explain current SES trajectories and immediate actions to reinforce or shift the trajectory.

The ten steps to responsible Inland fisheries in practice: reflections from diverse regional case studies around the globe - Steven J. Cooke; Elizabeth Nyboer; Abigail Bennett; Abigail J. Lynch; Dana M. Infante; Ian G. Cowx; T. Douglas Beard; Devin Bartley; Craig P. Paukert; Andrea J. Reid; Simon Funge-Smith; Edith Gondwe; et al. (Reviews in Fish Biology and Fisheries, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Ethical considerations for research on small‐scale fisheries and blue crimes - Paula Satizábal; Philippe Le Billon; Dyhia Belhabib; Lina M. Saavedra‐Díaz; Isabela Figueroa; Gina Noriega; Nathan J. Bennett (Fish and Fisheries, 2021)
Crimes at sea—blue crimes—can have devastating impacts on small‐scale fishing communities. Increasing calls to address “blue crimes” demand more research to address the drivers, patterns, actors and impacts of criminal activities in society and the oceans. This research and policy agenda, however, is not without risks as it might impact individual small‐scale fishers and their communities, exacerbate existing inequalities and contribute to the criminalization of small‐scale fishing practices. This paper discusses the risks and ethical challenges faced by a blue crimes research agenda to improve rather than worsen the plight of small‐scale fishers. We identify eight inter‐related ethical considerations: (i) pay attention to context and forms of involvement, (ii) cultivate reciprocal relationships and collaborations, (iii) evaluate and minimize risks, (iv) integrate storytelling and careful listening, (v) challenge reductionism, (vi) represent people, places, and practices carefully, (vii) follow communication ethics and (viii) consider the legal and policy implications. In light of a review of the literature on blue crimes and small‐scale fisheries, we point to the need for ethically grounded research that is committed to reducing the associated burdens on small‐scale fishers and their communities.

Application of DNA mini-barcoding reveals illegal trade in endangered shark products in southern Africa - TA Asbury; R Bennett; AS Price; C da Silva; M Bürgener; JD Klein; SN Maduna; N Sidat; S Fernando; AE Bester-van der Merwe (African Journal of Marine Science, 2021)

Global assessment of marine and freshwater recreational fish reveals mismatch in climate change vulnerability and conservation effort - Elizabeth A. Nyboer; Hsien‐Yung Lin; Joseph R. Bennett; Joseph Gabriel; William Twardek; Auston D. Chhor; Lindsay Daly; Sarah Dolson; Eric Guitard; Peter Holder; Christina M. Mozzon; Alexandria Trahan; et al. (Global Change Biology, 2021)
Recreational fisheries contribute substantially to the sociocultural and economic well‐being of coastal and riparian regions worldwide, but climate change threatens their sustainability. Fishery managers require information on how climate change will impact key recreational species; however, the absence of a global assessment hinders both directed and widespread conservation efforts. In this study, we present the first global climate change vulnerability assessment of recreationally targeted fish species from marine and freshwater environments (including diadromous fishes). We use climate change projections and data on species’ physiological and ecological traits to quantify and map global climate vulnerability and analyze these patterns alongside the indices of socioeconomic value and conservation effort to determine where efforts are sufficient and where they might fall short. We found that over 20% of recreationally targeted fishes are vulnerable to climate change under a high emission scenario. Overall, marine fishes had the highest number of vulnerable species, concentrated in regions with sensitive habitat types (e.g., coral reefs). However, freshwater fishes had higher proportions of species at risk from climate change, with concentrations in northern Europe, Australia, and southern Africa. Mismatches in conservation effort and vulnerability were found within all regions and life‐history groups. A key pattern was that current conservation effort focused primarily on marine fishes of high socioeconomic value rather than on the freshwater and diadromous fishes that were predicted to be proportionately more vulnerable. While several marine regions were notably lacking in protection (e.g., Caribbean Sea, Banda Sea), only 19% of vulnerable marine species were without conservation effort. By contrast, 72% of freshwater fishes and 33% of diadromous fishes had no measures in place, despite their high vulnerability and cultural value. The spatial and taxonomic analyses presented here provide guidance for the future conservation and management of recreational fisheries as climate change progresses.

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Advancing Social Equity in and Through Marine Conservation - Nathan J. Bennett; Laure Katz; Whitney Yadao-Evans; Gabby N. Ahmadia; Scott Atkinson; Natalie C. Ban; Neil M. Dawson; Asha de Vos; Juno Fitzpatrick; David Gill; Mael Imirizaldu; Naia Lewis; et al. (Frontiers in Marine Science, 2021)
Substantial efforts and investments are being made to increase the scale and improve the effectiveness of marine conservation globally. Though it is mandated by international law and central to conservation policy, less attention has been given to how to operationalize social equity in and through the pursuit of marine conservation. In this article, we aim to bring greater attention to this topic through reviewing how social equity can be better integrated in marine conservation policy and practice. Advancing social equity in marine conservation requires directing attention to: recognition through acknowledgment and respect for diverse peoples and perspectives; fair distribution of impacts through maximizing benefits and minimizing burdens; procedures through fostering participation in decision-making and good governance; management through championing and supporting local involvement and leadership; the environment through ensuring the efficacy of conservation actions and adequacy of management to ensure benefits to nature and people; and the structural barriers to and institutional roots of inequity in conservation. We then discuss the role of various conservation organizations in advancing social equity in marine conservation and identify the capacities these organizations need to build. We urge the marine conservation community, including governments, non-governmental organizations and donors, to commit to the pursuit of socially equitable conservation.

The Politics of Ocean Governance Transformations - Jessica L. Blythe; Derek Armitage; Nathan J. Bennett; Jennifer J. Silver; Andrew M. Song (Frontiers in Marine Science, 2021)
Recently, oceans have become the focus of substantial global attention and diverse appeals for “transformation.” Calls to transform ocean governance are motivated by various objectives, including the need to secure the rights of marginalized coastal communities, to boost ocean-based economic development, and to reverse global biodiversity loss. This paper examines the politics of ocean governance transformations through an analysis of three ongoing cases: the FAO’s voluntary guidelines for small-scale fisheries; debt-for-“blue”-nature swaps in the Seychelles; and the United Nations’ negotiations for a high seas’ treaty. We find that transformations are not inevitable or apolitical. Rather, changes are driven by an array of actors with different objectives and varying degrees of power. Objectives are articulated and negotiated through interactions that may reassemble rights, access, and control; however, there is also the potential that existing conditions become further entrenched rather than transformed at all. In particular, our analysis suggests that: (1) efforts to transform are situated in contested, historical landscapes that bias the trajectory of transformation, (2) power dynamics shape whose agendas and narratives drive transformational change, and (3) transformations create uneven distributions of costs and benefits that can facilitate or stall progress toward intended goals. As competing interests over ocean spaces continue to grow in the coming decades, understanding the processes through which ocean governance transformations can occur—and making the politics of transformative change more explicit—will be critical for realizing equitable ocean governance.

Correction to: Temperate forest fragments maintain aboveground carbon stocks out to the forest edge despite changes in community composition - Carly Ziter; Elena M. Bennett; Andrew Gonzalez (Oecologia, 2021)

Pandora: 4-D White Matter Bundle Population-Based Atlases Derived from Diffusion MRI Fiber Tractography - Colin B Hansen; Qi Yang; Ilwoo Lyu; Francois Rheault; Cailey Kerley; Bramsh Qamar Chandio; Shreyas Fadnavis; Owen Williams; Andrea T. Shafer; Susan M. Resnick; David H. Zald; Laurie E Cutting; et al. (Neuroinformatics, 2021)

The Night Shift: Nest Closure and Guarding Behaviors in the Stingless Bee, Tetragonisca angustula - Meghan M. Bennett; Kaitlin M. Baudier (Journal of Insect Behavior, 2021)

Incidence and risk factors for respiratory tract bacterial colonization and infection in lung transplant recipients - L. Paglicci; V. Borgo; N. Lanzarone; M. Fabbiani; C. Cassol; MG. Cusi; M. Valassina; S. Scolletta; E. Bargagli; L. Marchetti; P. Paladini; L. Luzzi; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
To evaluate incidence of and risk factors for respiratory bacterial colonization and infections within 30 days from lung transplantation (LT). We retrospectively analyzed microbiological and clinical data from 94 patients transplanted for indications other than cystic fibrosis, focusing on the occurrence of bacterial respiratory colonization or infection during 1 month of follow-up after LT. Thirty-three percent of patients developed lower respiratory bacterial colonization. Bilateral LT and chronic heart diseases were independently associated to a higher risk of overall bacterial colonization. Peptic diseases conferred a higher risk of multi-drug resistant (MDR) colonization, while longer duration of aerosol prophylaxis was associated with a lower risk. Overall, 35% of lung recipients developed bacterial pneumonia. COPD (when compared to idiopathic pulmonary fibrosis, IPF) and higher BMI were associated to a lower risk of bacterial infection. A higher risk of MDR infection was observed in IPF and in patients with pre-transplant colonization and infections. The risk of post-LT respiratory infections could be stratified by considering several factors (indication for LT, type of LT, presence of certain comorbidities, and microbiologic assessment before LT). A wider use of early nebulized therapies could be useful to prevent MDR colonization, thus potentially lowering infectious risk.

Antibiotic susceptibility and molecular analysis of invasive Neisseria meningitidis recovered in the Republic of Ireland, 1996 to 2016 - Désirée E. Bennett; K. L. Meyler; M. T. Cafferkey; R. J. Cunney (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Hypoactivation in the precuneus and posterior cingulate cortex during ambiguous decision making in individuals with HIV - Shana A. Hall; Sheri L. Towe; M. Tauseef Nadeem; Andrea L. Hobkirk; Bennett W. Hartley; Rosa Li; Scott A. Huettel; Christina S. Meade (Journal of NeuroVirology, 2021)

Come together: calibration of tiger shark (Galeocerdo cuvier) microsatellite databases for investigating global population structure and assignment of historical specimens - M. Sort; A. Manuzzi; B. Jiménez-Mena; J. R. Ovenden; B. J. Holmes; A. M. Bernard; M. S. Shivji; D. Meldrup; M. B. Bennett; E. E. Nielsen (Conservation Genetics Resources, 2021)

Recognize fish as food in policy discourse and development funding - Abigail Bennett; Xavier Basurto; John Virdin; Xinyan Lin; Samantha J. Betances; Martin D. Smith; Edward H. Allison; Barbara A. Best; Kelly D. Brownell; Lisa M. Campbell; Christopher D. Golden; Elizabeth Havice; et al. (Ambio, 2021)
The international development community is off-track from meeting targets for alleviating global malnutrition. Meanwhile, there is growing consensus across scientific disciplines that fish plays a crucial role in food and nutrition security. However, this ‘fish as food’ perspective has yet to translate into policy and development funding priorities. We argue that the traditional framing of fish as a natural resource emphasizes economic development and biodiversity conservation objectives, whereas situating fish within a food systems perspective can lead to innovative policies and investments that promote nutrition-sensitive and socially equitable capture fisheries and aquaculture. This paper highlights four pillars of research needs and policy directions toward this end. Ultimately, recognizing and working to enhance the role of fish in alleviating hunger and malnutrition can provide an additional long-term development incentive, beyond revenue generation and biodiversity conservation, for governments, international development organizations, and society more broadly to invest in the sustainability of capture fisheries and aquaculture.

Climate‐driven impacts of exotic species on marine ecosystems - Scott Bennett; Julia Santana‐Garcon; Núria Marbà; Gabriel Jorda; Andrea Anton; Eugenia T. Apostolaki; Just Cebrian; Nathan R. Geraldi; Dorte Krause‐Jensen; Catherine E. Lovelock; Paulina Martinetto; John M. Pandolfi; et al. (Global Ecology and Biogeography, 2021)
Aim Temperature is fundamental to the physiological and ecological performance of marine organisms, but its role in modulating the magnitude of ecological impacts by exotic species remains unresolved. Here, we examine the relationship between thermal regimes in the range of origin of marine exotic species and sites of measured impact, after human‐induced introduction. We compare this relationship with the magnitude of impact exerted by exotic species on native ecosystems. Location Global. Time period 1977–2017 (meta‐analysis). Major taxa studied Marine exotic species. Methods Quantitative impacts of exotic species in marine ecosystems were obtained from a global database. The native range of origin of exotic species was used to estimate the realized thermal niche for each species and compared with the latitude and climatic conditions in recipient sites of recorded impact of exotic species. The difference in median temperatures between recipient sites and the thermal range of origin (i.e., thermal midpoint anomaly) was compared with the magnitude of effect sizes by exotic species on native species, communities and ecosystems. Results Recorded impacts occurred predominantly within the thermal niche of origin of exotic species, albeit with a tendency toward higher latitudes and slightly cooler conditions. The severity of impacts by exotic species on abundance of native taxa displayed a hump‐shaped relationship with temperature. Peak impacts were recorded in recipient sites that were 2.2°C cooler than the thermal midpoint of the range of origin of exotic species, and impacts decreased in magnitude toward higher and lower thermal anomalies. Main conclusions Our findings highlight how temperature and climatic context influence ecological impacts by exotic species in marine ecosystems and the implications for existing and novel species interactions under climate change.

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

Hippocampal activation and connectivity in the aging brain - Lori L. Beason-Held; Andrea T. Shafer; Joshua O. Goh; Bennett A. Landman; Christos Davatzikos; Brieana Viscomi; Jessica Ash; Melissa Kitner-Triolo; Luigi Ferrucci; Susan M. Resnick (Brain Imaging and Behavior, 2021)

Correction to: Addition of nectar sources affects a parasitoid community without improving pest suppression - Jacob H. Miall; Paul K. Abram; Naomi Cappuccino; Andrew M. R. Bennett; José L. Fernández-Triana; Gary A. P. Gibson; Peter G. Mason (Journal of Pest Science, 2021)

Addition of nectar sources affects a parasitoid community without improving pest suppression - Jacob H. Miall; Paul K. Abram; Naomi Cappuccino; Andrew M. R. Bennett; José L. Fernández-Triana; Gary A. P. Gibson; Peter G. Mason (Journal of Pest Science, 2021)

Assessing the impact of taxon resolution on network structure - David R. Hemprich‐Bennett; Hernani F. M. Oliveira; Steven C. Le Comber; Stephen J. Rossiter; Elizabeth L. Clare (Ecology, 2021)
Constructing ecological networks has become an indispensable approach in understanding how different taxa interact. However, the methods used to generate data in network research vary widely among studies, potentially limiting our ability to compare results meaningfully. In particular, methods of classifying nodes vary in their precision, likely altering the architecture of the network studied. For example, rather than being classified as Linnaean species, taxa are regularly assigned to morphospecies in observational studies, or to molecular operational taxonomic units (MOTUs) in molecular studies, with the latter defined based on an arbitrary threshold of sequence similarity. Although the use of MOTUs in ecological networks holds great potential, especially for allowing rapid construction of large data sets of interactions, it is unclear how the choice of clustering threshold can influence the conclusions obtained. To test the impact of taxonomic precision on network architecture, we obtained and analyzed 16 data sets of ecological interactions, inferred from metabarcoding and observations. Our comparisons of networks constructed under a range of sequence thresholds for assigning taxa demonstrate that even small changes in node resolution can cause wide variation in almost all key metric values. Moreover, relative values of commonly used metrics such as robustness were seen to fluctuate continuously with node resolution, thereby potentially causing error in conclusions drawn when comparing multiple networks. In observational networks, we found that changing node resolution could, in some cases, lead to substantial changes to measurements of network topology. Overall, our findings highlight the importance of classifying nodes to the greatest precision possible, and demonstrate the need for caution when comparing networks that differ with respect to node resolution, even where taxonomic groups and interaction types are similar. In such cases, we recommend that comparisons of networks should focus on relative differences rather than absolute values between the networks studied.

Early olfactory, but not gustatory processing, is affected by the selection of heritable cognitive phenotypes in honey bee - Meghan M. Bennett; Chelsea N. Cook; Brian H. Smith; Hong Lei (Journal of Comparative Physiology A, 2021)

Integrated metabolomics reveals altered lipid metabolism in adipose tissue in a model of extreme longevity - Justin Darcy; Yimin Fang; Samuel McFadden; Matthew D. Lynes; Luiz O. Leiria; Jonathan M. Dreyfuss; Valerie Bussburg; Vladimir Tolstikov; Bennett Greenwood; Niven R. Narain; Michael A. Kiebish; Andrzej Bartke; et al. (GeroScience, 2020)

The multiple process model of goal-directed aiming/reaching: insights on limb control from various special populations - Digby Elliott; James Lyons; Spencer J. Hayes; James J. Burkitt; Steve Hansen; Lawrence E. M. Grierson; Nathan C. Foster; James W. Roberts; Simon J. Bennett (Experimental Brain Research, 2020)

A cross‐scale assessment of productivity–diversity relationships - Dylan Craven; Masha T. van der Sande; Carsten Meyer; Katharina Gerstner; Joanne M. Bennett; Darren P. Giling; Jes Hines; Helen R. P. Phillips; Felix May; Katherine H. Bannar‐Martin; Jonathan M. Chase; Petr Keil (Global Ecology and Biogeography, 2020)
Aim Biodiversity and ecosystem productivity vary across the globe, and considerable effort has been made to describe their relationships. Biodiversity and ecosystem functioning research has traditionally focused on how experimentally controlled species richness affects net primary productivity ( S → NPP) at small spatial grains. In contrast, the influence of productivity on richness (NPP → S ) has been explored at many grains in naturally assembled communities. Mismatches in spatial scale between approaches have fuelled debate about the strength and direction of biodiversity–productivity relationships. Here, we examine the direction and strength of the influence of productivity on diversity (NPP → S ) and the influence of diversity on productivity ( S → NPP) and how these vary across spatial grains. Location Contiguous USA. Time period 1999–2015. Major taxa studied Woody species (angiosperms and gymnosperms). Methods Using data from North American forests at grains from local (672 m 2 ) to coarse spatial units (median area = 35,677 km 2 ), we assess relationships between diversity and productivity using structural equation and random forest models, while accounting for variation in climate, environmental heterogeneity, management and forest age. Results We show that relationships between S and NPP strengthen with spatial grain. Within each grain, S → NPP and NPP → S have similar magnitudes, meaning that processes underlying S → NPP and NPP → S either operate simultaneously or that one of them is real and the other is an artefact. At all spatial grains, S was one of the weakest predictors of forest productivity, which was largely driven by biomass, temperature and forest management and age. Main conclusions We conclude that spatial grain mediates relationships between biodiversity and productivity in real‐world ecosystems and that results supporting predictions from each approach (NPP → S and S → NPP) serve as an impetus for future studies testing underlying mechanisms. Productivity–diversity relationships emerge at multiple spatial grains, which should widen the focus of national and global policy and research to larger spatial grains.

Impacts of green infrastructure on flood risk perceptions in Hong Kong - Seung Kyum Kim; Paul Joosse; Mia M. Bennett; Terry van Gevelt (Climatic Change, 2020)

Age-based changes in kairomone response mediate task partitioning in stingless bee soldiers (Tetragonisca angustula) - Kaitlin M. Baudier; Meghan M. Bennett; Madeleine M. Ostwald; Sarah Hart; Theodore P. Pavlic; Jennifer H. Fewell (Behavioral Ecology and Sociobiology, 2020)

Climate change and adaptation to social-ecological change: the case of indigenous people and culture-based fisheries in Sri Lanka - Eranga K. Galappaththi; James D. Ford; Elena M. Bennett (Climatic Change, 2020)

Coral loss alters guarding and farming behavior of a Caribbean damselfish - Valentina Di Santo; Lois A. O’Boyle; Ryan K. Saylor; Theresa F. Dabruzzi; Marthe A. Covell; Katrina Kaack; Rachel Scharer; Katherine Seger; Nicholas Favazza; Christopher M. Pomory; Wayne A. Bennett (Marine Biology, 2020)
Coral loss is a major element of global ecological change in the oceans that may shape the behavior of keystone species such as habitat-attached animals. Farming damselfishes cultivate and aggressively protect algal garden within their territory, thereby shaping local fish assemblages and macro-algae diversity. Following the widespread loss of live branching coral throughout Florida and the Caribbean Sea, dusky damselfish ( Stegastes adustus ) have modified their territorial behavior. We compared antagonistic behavior, and size and algal species composition of territories of dusky damselfish on dead branching coral rubble and live boulder coral in the Dry Tortugas National Park, USA. Even though similar numbers of “intruders” entered each habitat type, dusky damselfish on rubble territories chased out significantly more fishes, had larger territories and more species of algae were present in their gardens. This study shows that dusky damselfish successfully occupy living and dead coral areas; however, there are potential trade-offs between defending a larger territory and cultivating fewer algal species.

The COVID-19 Pandemic, Small-Scale Fisheries and Coastal Fishing Communities - Nathan J. Bennett; Elena M. Finkbeiner; Natalie C. Ban; Dyhia Belhabib; Stacy D. Jupiter; John N. Kittinger; Sangeeta Mangubhai; Joeri Scholtens; David Gill; Patrick Christie (Coastal Management, 2020)

Central adiposity at diagnosis may reduce prostate cancer-specific mortality in African-Caribbean men with prostate cancer: 10-year follow-up of participants in a case–control study - Maria D. Jackson; Marshall K. Tulloch-Reid; Affette M. McCaw-Binns; William Aiken; Trevor S. Ferguson; Nadia R. Bennett; Leroy Harrison; Asha Badaloo; Donovan McGrowder; Annielle Grindley; Evelyn Walker; Simon G. Anderson (Cancer Causes & Control, 2020)

Climate and local environment structure asynchrony and the stability of primary production in grasslands - Benjamin Gilbert; Andrew S. MacDougall; Taku Kadoya; Munemitsu Akasaka; Joseph R. Bennett; Eric M. Lind; Habacuc Flores‐Moreno; Jennifer Firn; Yann Hautier; Elizabeth T. Borer; Eric W. Seabloom; Peter B. Adler; et al. (Global Ecology and Biogeography, 2020)
Aim Climate variability threatens to destabilize production in many ecosystems. Asynchronous species dynamics may buffer against such variability when a decrease in performance by some species is offset by an increase in performance of others. However, high climatic variability can eliminate species through stochastic extinctions or cause similar stress responses among species that reduce buffering. Local conditions, such as soil nutrients, can also alter production stability directly or by influencing asynchrony. We test these hypotheses using a globally distributed sampling experiment. Location Grasslands in North America, Europe and Australia. Time period Annual surveys over 5 year intervals occurring between 2007 and 2014. Major taxa studied Herbaceous plants. Methods We sampled annually the per species cover and aboveground community biomass [net primary productivity (NPP)], plus soil chemical properties, in 29 grasslands. We tested how soil conditions, combined with variability in precipitation and temperature, affect species richness, asynchrony and temporal stability of primary productivity. We used bivariate relationships and structural equation modelling to examine proximate and ultimate relationships. Results Climate variability strongly predicted asynchrony, whereas NPP stability was more related to soil conditions. Species richness was structured by both climate variability and soils and, in turn, increased asynchrony. Variability in temperature and precipitation caused a unimodal asynchrony response, with asynchrony being lowest at low and high climate variability. Climate impacted stability indirectly, through its effect on asynchrony, with stability increasing at higher asynchrony owing to lower inter‐annual variability in NPP. Soil conditions had no detectable effect on asynchrony but increased stability by increasing the mean NPP, especially when soil organic matter was high. Main conclusions We found globally consistent evidence that climate modulates species asynchrony but that the direct effect on stability is low relative to local soil conditions. Nonetheless, our observed unimodal responses to variability in temperature and precipitation suggest asynchrony thresholds, beyond which there are detectable destabilizing impacts of climate on primary productivity.

Managing Pain in People with Cancer—a Systematic Review of the Attitudes and Knowledge of Professionals, Patients, Caregivers and Public - Salim M. Makhlouf; Simon Pini; Shenaz Ahmed; Michael I. Bennett (Journal of Cancer Education, 2020)

Multidisciplinary perspectives on medication-related decision-making for people with advanced dementia living in long-term care: a critical incident analysis - Domenica Disalvo; Tim Luckett; Alexandra Bennett; Patricia M. Davidson; Meera Agar (European Journal of Clinical Pharmacology, 2020)

Evaluating conservation dogs in the search for rare species - Emma M. Bennett; Cindy E. Hauser; Joslin L. Moore (Conservation Biology, 2020)
Detecting rare species is important for both threatened species management and invasive species eradication programs. Conservation scent dogs provide an olfactory survey tool that has advantages over traditional visual and auditory survey techniques for some cryptic species. From the literature, we identified 5 measures important in evaluating the use of scent dogs: precision, sensitivity, effort, cost, and comparison with other techniques. We explored the scale at which performance is evaluated and examined when field testing under real working conditions is achievable. We also identified cost differences among studies. We examined 61 studies published in 1976–2018 that reported conservation dog performance, and considered the inconsistencies in the reporting of scent dog performance among these studies. The majority of studies reported some measure of performance; however, only 8 studies reported all 3 aspects necessary for performance evaluation: precision, sensitivity, and effort. Although effort was considered in 43 studies, inconsistent methods and incomplete reporting prevented meaningful evaluation of performance and comparison among studies. Differences in cost between similar studies were influenced by geographical location and how the dog and handler were sourced for the study. To develop consistent reporting for evaluation, we recommend adoption of sensitivity, precision, and effort as standard performance measures. We recommend reporting effort as the total area and total time spent searching and reporting sensitivity and precision as proportions of the sample size. Additionally, reporting of costs, survey objectives, dog training and experience, type of detection task, and human influences will provide better opportunities for comparison within and among studies.

Patient- and area-level predictors of prostate cancer among South Carolina veterans: a spatial analysis - Peter Georgantopoulos; Jan M. Eberth; Bo Cai; Christopher Emrich; Gowtham Rao; Charles L. Bennett; Kathlyn S. Haddock; James R. Hébert (Cancer Causes & Control, 2020)

Seeds of good anthropocenes: developing sustainability scenarios for Northern Europe - C. Raudsepp-Hearne; G. D. Peterson; E. M. Bennett; R. Biggs; A. V. Norström; L. Pereira; J. Vervoort; D. M. Iwaniec; T. McPhearson; P. Olsson; T. Hichert; M. Falardeau; et al. (Sustainability Science, 2020)

Non-native vascular flora of the Arctic: Taxonomic richness, distribution and pathways - Pawel Wasowicz; Alexander N. Sennikov; Kristine B. Westergaard; Katie Spellman; Matthew Carlson; Lynn J. Gillespie; Jeffery M. Saarela; Steven S. Seefeldt; Bruce Bennett; Christian Bay; Stefanie Ickert-Bond; Henry Väre (Ambio, 2020)

Ecological effects of non‐native species in marine ecosystems relate to co‐occurring anthropogenic pressures - Nathan R. Geraldi; Andrea Anton; Julia Santana‐Garcon; Scott Bennett; Nuria Marbà; Catherine E. Lovelock; Eugenia T. Apostolaki; Just Cebrian; Dorte Krause‐Jensen; Paulina Martinetto; John M. Pandolfi; Carlos M. Duarte (Global Change Biology, 2020)
Predictors for the ecological effects of non‐native species are lacking, even though such knowledge is fundamental to manage non‐native species and mitigate their impacts. Current theories suggest that the ecological effects of non‐native species may be related to other concomitant anthropogenic stressors, but this has not been tested at a global scale. We combine an exhaustive meta‐analysis of the ecological effects of marine non‐native species with human footprint proxies to determine whether the ecological changes due to non‐native species are modulated by co‐occurring anthropogenic impacts. We found that non‐native species had greater negative effects on native biodiversity where human population was high and caused reductions in individual performance where cumulative human impacts were large. On this basis we identified several marine ecoregions where non‐native species may have the greatest ecological effects, including areas in the Mediterranean Sea and along the northwest coast of the United States. In conclusion, our global assessment suggests coexisting anthropogenic impacts can intensify the ecological effects of non‐native species.

Effects of land use, cover, and protection on stream and riparian ecosystem services and biodiversity - Dalal E.L. Hanna; Ciara Raudsepp‐Hearne; Elena M. Bennett (Conservation Biology, 2020)
Protected areas are an important part of broader landscapes that are often used to preserve biodiversity or natural features. Some argue that protected areas may also help ensure provision of ecosystem services. However, the effect of protection on ecosystem services and whether protection affects the provision of ecosystem services is known only for a few services in a few types of landscapes. We sought to fill this gap by investigating the effect of watershed protection status and land use and land cover on biodiversity and the provision of ecosystem services. We compared the ecosystem services provided in and around streams in 4 watershed types: International Union for Conservation of Nature category II protected forests, unprotected forests, unprotected forests with recent timber harvesting, and unprotected areas with agriculture. We surveyed 28 streams distributed across these watershed types in Quebec, Canada, to quantify provisioning of clean water, carbon storage, recreation, wild foods, habitat quality, and terrestrial and aquatic biodiversity richness and abundance. The quantity and quality of ecosystem services and biodiversity were generally higher in sites with intact forest—whether protected or not—relative to those embedded in production landscapes with forestry or agriculture. Clean‐water provision, carbon storage, habitat quality, and tree diversity were significantly higher in and around streams surrounded by forest. Recreation, wild foods, and aquatic biodiversity did not vary among watershed types. Although some services can be provided by both protected and unprotected areas, protection status may help secure the continued supply of services sensitive to changes in land use or land cover. Our findings provide needed information about the ecosystem service and biodiversity trade‐offs and synergies that result from developing a watershed or from protecting it.

Resistance of soil biota and plant growth to disturbance increases with plant diversity - Jonathan A. Bennett; Alexander M. Koch; Jennifer Forsythe; Nancy C. Johnson; David Tilman; John Klironomos (Ecology Letters, 2020)
Plant diversity is critical to the functioning of ecosystems, potentially mediated in part by interactions with soil biota. Here, we characterised multiple groups of soil biota across a plant diversity gradient in a long‐term experiment. We then subjected soil samples taken along this gradient to drought, freezing and a mechanical disturbance to test how plant diversity affects the responses of soil biota and growth of a focal plant to these disturbances. High plant diversity resulted in soils that were dominated by fungi and associated soil biota, including increased arbuscular mycorrhizal fungi and reduced plant‐feeding nematodes. Disturbance effects on the soil biota were reduced when plant diversity was high, resulting in higher growth of the focal plant in all but the frozen soils. These results highlight the importance of plant diversity for soil communities and their resistance to disturbance, with potential feedback effects on plant productivity.

Homogenization of freshwater lakes: Recent compositional shifts in fish communities are explained by gamefish movement and not climate change - Kevin Cazelles; Timothy Bartley; Matthew M. Guzzo; Marie‐Hélène Brice; Andrew S. MacDougall; Joseph R. Bennett; Ellen H. Esch; Taku Kadoya; Jocelyn Kelly; Shin‐ichiro Matsuzaki; Karin A. Nilsson; Kevin S. McCann (Global Change Biology, 2019)
Globally, lake fish communities are being subjected to a range of scale‐dependent anthropogenic pressures, from climate change to eutrophication, and from overexploitation to species introductions. As a consequence, the composition of these communities is being reshuffled, in most cases leading to a surge in taxonomic similarity at the regional scale termed homogenization. The drivers of homogenization remain unclear, which may be a reflection of interactions between various environmental changes. In this study, we investigate two potential drivers of the recent changes in the composition of freshwater fish communities: recreational fishing and climate change. Our results, derived from 524 lakes of Ontario, Canada sampled in two periods (1965–1982 and 2008–2012), demonstrate that the main contributors to homogenization are the dispersal of gamefish species, most of which are large predators. Alternative explanations relating to lake habitat (e.g., area, phosphorus) or variations in climate have limited explanatory power. Our analysis suggests that human‐assisted migration is the primary driver of the observed compositional shifts, homogenizing freshwater fish community among Ontario lakes and generating food webs dominated by gamefish species.

Functional neuroanatomy of the human eye movement network: a review and atlas - Benjamin Coiner; Hong Pan; Monica L. Bennett; Yelena G. Bodien; Swathi Iyer; Therese M. O’Neil-Pirozzi; Lorene Leung; Joseph T. Giacino; Emily Stern (Brain Structure and Function, 2019)

National contributions to global ecosystem values - Laura E. Coristine; Sheila Colla; Nathan Bennett; Anja M. Carlsson; Christina Davy; Kimberley T.A. Davies; Brett Favaro; D.T. Tyler Flockhart; Kevin Fraser; Diane Orihel; Sarah P. Otto; Wendy Palen; et al. (Conservation Biology, 2019)
Current conservation templates prioritize biogeographic regions with high intensity ecosystem values, such as exceptional species richness or threat. Intensity‐based targets are an important consideration in global efforts, but they do not capture all available opportunities to conserve ecosystem values, including those that accrue in low intensity over large areas. We assess six globally‐significant ecosystem values—intact wilderness, freshwater availability, productive marine environments, breeding habitat for migratory wildlife, soil carbon storage, and latitudinal potential for range shift in the face of climate change—to highlight opportunities for high‐impact broadly‐distributed contributions to global conservation. Nations can serve as a cohesive block of policy that can profoundly influence conservation outcomes. Contributions to global ecosystem values that exceed what is predicted by a nation's area alone, can give rise to countries with the capacity to act as ‘conservation superpowers’, such as Canada and Russia. For these conservation superpowers, a relatively small number of national policies can have environmental repercussions for the rest of the world.

The provision and utility of earth science to decision-makers: synthesis and key findings - Mark C. Quigley; Luke G. Bennetts; Patricia Durance; Petra M. Kuhnert; Mark D. Lindsay; Keith G. Pembleton; Melanie E. Roberts; Christopher J. White (Environment Systems and Decisions, 2019)

The provision and utility of science and uncertainty to decision-makers: earth science case studies - Mark C. Quigley; Luke G. Bennetts; Patricia Durance; Petra M. Kuhnert; Mark D. Lindsay; Keith G. Pembleton; Melanie E. Roberts; Christopher J. White (Environment Systems and Decisions, 2019)

Integrating team science into interdisciplinary graduate education: an exploration of the SESYNC Graduate Pursuit - Kenneth E. Wallen; Karen Filbee-Dexter; Jeremy B. Pittman; Stephen M. Posner; Steven M. Alexander; Chelsie L. Romulo; Drew E. Bennett; Elizabeth C. Clark; Stella J.M. Cousins; Bradford A. Dubik; Margaret Garcia; Heather A. Haig; et al. (Journal of Environmental Studies and Sciences, 2019)

Polyphenol-associated oxidative stress and inflammation in a model of LPS-induced inflammation in glial cells: do we know enough for responsible compounding? - Guillermo Cásedas; Amber C. Bennett; E. González-Burgos; M. P. Gómez-Serranillos; Víctor López; Carine Smith (Inflammopharmacology, 2019)

The Decision Decoding ToolBOX (DDTBOX) – A Multivariate Pattern Analysis Toolbox for Event-Related Potentials - Stefan Bode; Daniel Feuerriegel; Daniel Bennett; Phillip M. Alday (Neuroinformatics, 2019)

Watershed Buffering of Legacy Phosphorus Pressure at a Regional Scale: A Comparison Across Space and Time - A. S. Kusmer; J.-O. Goyette; G. K. MacDonald; E. M. Bennett; R. Maranger; P. J. A. Withers (Ecosystems, 2019)

A novel approach for co-producing positive scenarios that explore agency: case study from the Canadian Arctic - Marianne Falardeau; Ciara Raudsepp-Hearne; Elena M. Bennett (Sustainability Science, 2019)

The Acute Effects of Age and Particulate Matter Exposure on Heart Rate and Heart Rate Variability in Mice - Blake A. Bennett; Ernst W. Spannhake; Ana M. Rule; Patrick N. Breysse; Clarke G. Tankersley (Cardiovascular Toxicology, 2018)

Comparative genomics of a quadripartite symbiosis in a planthopper host reveals the origins and rearranged nutritional responsibilities of anciently diverged bacterial lineages - Gordon M. Bennett; Meng Mao (Environmental Microbiology, 2018)
Summary Insects in the Auchenorrhyncha (Hemiptera: Suborder) established nutritional symbioses with bacteria approximately 300 million years ago (MYA). The suborder split early during its diversification (~ 250 MYA) into the Fulgoroidea (planthoppers) and Cicadomorpha (leafhoppers and cicadas). The two lineages share some symbionts, including Sulcia and possibly a Betaproteobacteria that collaboratively provide their hosts with 10 essential amino acids (EAA). Some hosts harbour three bacteria, as is common among planthoppers. However, genomic studies are currently restricted to the dual‐bacterial symbioses found in Cicadomorpha, leaving the origins and functions of these more complex symbioses unclear. To address these questions, we sequenced the genomes and performed phylogenomic analyses of ‘ Candidatus Sulcia muelleri’ ( Bacteroidetes ), ‘ Ca . Vidania fulgoroideae’ ( Betaproteobacteria ) and ‘ Ca . Purcelliella pentastirinorum’ ( Gammaproteobacteria ) from a planthopper (Cixiidae: Oliarus ). In contrast to the Cicadomorpha, nutritional synthesis responsibilities are rearranged between the cixiid symbionts. Although Sulcia has a highly conserved genome across the Auchenorrhyncha, in the cixiids it is greatly reduced and provides only three EAAs. Vidania contributes the remaining seven EAAs. Phylogenomic results suggest that it represents an ancient symbiont lineage paired with Sulcia throughout the Auchenorrhyncha. Finally, Purcelliella was recently acquired from plant‐insect associated bacteria ( Pantoea ‐ Erwinia ) to provide B vitamins and metabolic support to its degenerate partners.

Cropland patchiness strongest agricultural predictor of bird diversity for multiple guilds in landscapes of Ontario, Canada - Barbara Frei; Elena M. Bennett; Jeremy T. Kerr (Regional Environmental Change, 2018)

Rare loss of function variants in candidate genes and risk of colorectal cancer - Elisabeth A. Rosenthal; Brian H. Shirts; Laura M. Amendola; Martha Horike-Pyne; Peggy D. Robertson; Fuki M. Hisama; Robin L. Bennett; Michael O. Dorschner; Deborah A. Nickerson; Ian B. Stanaway; Rami Nassir; Kathy T. Vickers; et al. (Human Genetics, 2018)

Quantifying species recovery and conservation success to develop an IUCN Green List of Species - H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Molly K. Grace; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; David A. Keith; Barney Long; David P. Mallon; Erik Meijaard; et al. (Conservation Biology, 2018)
Stopping declines in biodiversity is critically important, but it is only a first step toward achieving more ambitious conservation goals. The absence of an objective and practical definition of species recovery that is applicable across taxonomic groups leads to inconsistent targets in recovery plans and frustrates reporting and maximization of conservation impact. We devised a framework for comprehensively assessing species recovery and conservation success. We propose a definition of a fully recovered species that emphasizes viability, ecological functionality, and representation; and use counterfactual approaches to quantify degree of recovery. This allowed us to calculate a set of 4 conservation metrics that demonstrate impacts of conservation efforts to date (conservation legacy); identify dependence of a species on conservation actions (conservation dependence); quantify expected gains resulting from conservation action in the medium term (conservation gain); and specify requirements to achieve maximum plausible recovery over the long term (recovery potential). These metrics can incentivize the establishment and achievement of ambitious conservation targets. We illustrate their use by applying the framework to a vertebrate, an invertebrate, and a woody and an herbaceous plant. Our approach is a preliminary framework for an International Union for Conservation of Nature (IUCN) Green List of Species, which was mandated by a resolution of IUCN members in 2012. Although there are several challenges in applying our proposed framework to a wide range of species, we believe its further development, implementation, and integration with the IUCN Red List of Threatened Species will help catalyze a positive and ambitious vision for conservation that will drive sustained conservation action.

Research Priorities to Support Effective Manta and Devil Ray Conservation - Joshua D. Stewart; Fabrice R. A. Jaine; Amelia J. Armstrong; Asia O. Armstrong; Michael B. Bennett; Katherine B. Burgess; Lydie I. E. Couturier; Donald A. Croll; Melissa R. Cronin; Mark H. Deakos; Christine L. Dudgeon; Daniel Fernando; et al. (Frontiers in Marine Science, 2018)

What are the Conditions of Riparian Ecosystems? Identifying Impaired Floodplain Ecosystems across the Western U.S. Using the Riparian Condition Assessment (RCA) Tool - William W. Macfarlane; Jordan T. Gilbert; Joshua D. Gilbert; William C. Saunders; Nate Hough-Snee; Chalese Hafen; Joseph M. Wheaton; Stephen N. Bennett (Environmental Management, 2018)

Climate change alterations to ecosystem dominance: how might sponge‐dominated reefs function? - James J. Bell; Alberto Rovellini; Simon K. Davy; Michael W. Taylor; Elizabeth A. Fulton; Matthew R. Dunn; Holly M. Bennett; Nora M. Kandler; Heidi M. Luter; Nicole S. Webster (Ecology, 2018)
Anthropogenic stressors are impacting ecological systems across the world. Of particular concern are the recent rapid changes occurring in coral reef systems. With ongoing degradation from both local and global stressors, future reefs are likely to function differently from current coral‐dominated ecosystems. Determining key attributes of future reef states is critical to reliably predict outcomes for ecosystem service provision. Here we explore the impacts of changing sponge dominance on coral reefs. Qualitative modelling of reef futures suggests that changing sponge dominance due to increased sponge abundance will have different outcomes for other trophic levels compared with increased sponge dominance as a result of declining coral abundance. By exploring uncertainty in the model outcomes we identify the need to (1) quantify changes in carbon flow through sponges, (2) determine the importance of food limitation for sponges, (3) assess the ubiquity of the recently described “sponge loop,” (4) determine the competitive relationships between sponges and other benthic taxa, particularly algae, and (5) understand how changing dominance of other organisms alters trophic pathways and energy flows through ecosystems. Addressing these knowledge gaps will facilitate development of more complex models that assess functional attributes of sponge‐dominated reef ecosystems.

Riding the waves of the intercalated disc of the heart - Pauline M. Bennett (Biophysical Reviews, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Misidentification of istiophorid billfishes by fisheries observers raises uncertainty over stock status - Samuel M. Williams; Julian G. Pepperell; Michael Bennett; Jennifer R. Ovenden (Journal of Fish Biology, 2018)
We investigated whether commercially landed black marlin Istiompax indica were being misidentified by fisheries observers operating throughout the Pacific Ocean. Of 83 samples reported by observers as I. indica , 77% were genetically identified to be blue marlin Makaira nigricans and 2% to be striped marlin Kajikia audax . The high rate of misidentification by observers places considerable uncertainty over historic catch ratios of Indo‐Pacific marlin and stock assessments relying on the validity of these data.

Reflections on, and visions for, the changing field of pollination ecology - T. M. Knight; T.‐L. Ashman; J. M. Bennett; J. H. Burns; S. Passonneau; J. A. Steets (Ecology Letters, 2018)
Since the launch of Ecology Letters in 1998, the field of Pollination Ecology has changed considerably in its focus. In this review, we discuss the major discoveries across the past two decades. We quantitatively synthesise the frequency by which different concepts and topics appeared in the peer‐reviewed literature, as well as the connections between these topics. We then look forward to identify pressing research frontiers and opportunities for additional integration in the future. We find that there has been a shift towards viewing plant–pollinator interactions as networks and towards understanding how global drivers influence the plants, pollinators and the ecosystem service of pollination. Future frontiers include moving towards a macroecological view of plant–pollinator interactions, understanding how ecological intensification and urbanisation will influence pollination, considering other interactions, such as plant–microbe–pollinator networks, and understanding the causes and consequences of extinctions. Pollination Ecology is poised to advance our basic understanding of the ecological and evolutionary factors that shape plant–animal interactions and to create applied knowledge that informs conservation decision making.

Fish Community Structure and Diet Responses to Newbury Weirs in a Low-Gradient River - Sophia M. Bonjour; Heidi M. Rantala; Micah G. Bennett; Matt R. Whiles (Environmental Management, 2018)

Temporal and spatial patterns in behavioral responses of marine predators to a sudden influx of abalone prey (Haliotis rufescens) - Jennifer K. K. Hofmeister; Shelby K. Kawana; Benjamin J. Walker; Cynthia A. Catton; Ian Taniguchi; Derek M. Stein; Kathleen Sowul; Laura Rogers-Bennett (Hydrobiologia, 2018)

Ichneumonid parasitoid wasps from the Early Eocene Green River Formation: five new species and a revision of the known fauna (Hymenoptera, Ichneumonidae) - Tamara Spasojevic; Gavin R. Broad; Andrew M. R. Bennett; Seraina Klopfstein (PalZ, 2018)

Exploring UAV in Indonesian cadastral boundary data acquisition - Sheilla Ayu Ramadhani; R. M. Bennett; F. C. Nex (Earth Science Informatics, 2018)

Montserrat Vilà and Philip E. Hulme (eds): Impact of biological invasions on ecosystem services - Elena M. Bennett (Biological Invasions, 2018)

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Mechanical perturbations can elicit triggered reactions in the absence of a startle response - Christopher J. Forgaard; Ian M. Franks; Kimberly Bennett; Dana Maslovat; Romeo Chua (Experimental Brain Research, 2018)

Evolution of biological control agents following introduction to new environments - Mark G. Wright; Gordon M. Bennett (BioControl, 2018)

Morphological comparison of the ampullae of Lorenzini of three sympatric benthic rays - A. R. G. Gauthier; D. L. Whitehead; I. R. Tibbetts; B. W. Cribb; M. B. Bennett (Journal of Fish Biology, 2018)
This study investigated and compared the morphology of the electrosensory system of three species of benthic rays . Neotrygon trigonoides , Hemitrygon fluviorum and Maculabatis toshi inhabit similar habitats within Moreton Bay, Queensland, Australia. Like all elasmobranchs, they possess the ability to detect weak electrical fields using their ampullae of Lorenzini. Macroscopically, the ampullary organs of all three species are aggregated in three bilaterally paired clusters: the mandibular, hyoid and superficial ophthalmic clusters. The hyoid and superficial ophthalmic clusters of ampullae arise from both dorsal and ventral ampullary pores. The dorsal pores are typically larger than the ventral pores in all three species, except for the posterior ventral pores of the hyoid grouping. Ampullary canals arising from the hyoid cluster possessed a quasi‐sinusoidal shape, but otherwise appeared similar to the canals described for other elasmobranchs. Ultrastructure of the ampullae of Lorenzini of the three species was studied using a combination of light, confocal and electron microscopy. All possess ampullae of the alveolar type. In N. trigonoides and M. toshi, each ampullary canal terminates in three to five sensory chambers, each comprising several alveoli lined with receptor and supportive cells and eight to 11 sensory chambers in H. fluviorum . Receptor cells of all three species possess a similar organization to those of other elasmobranchs and were enveloped by large, apically nucleated supportive cells protruding well into the alveolar sacs. The luminally extended chassis of supportive cells protruding dramatically into the ampullary lumen had not previously been documented for any elasmobranch species.

Phytopathogen-induced changes to plant methylomes - Tarek Hewezi; Vince Pantalone; Morgan Bennett; C. Neal Stewart; Tessa M. Burch-Smith (Plant Cell Reports, 2018)

Genome-Wide Association Analysis of the Sense of Smell in U.S. Older Adults: Identification of Novel Risk Loci in African-Americans and European-Americans - Jing Dong; Annah Wyss; Jingyun Yang; T. Ryan Price; Aude Nicolas; Michael Nalls; Greg Tranah; Nora Franceschini; Zongli Xu; Claudia Schulte; Alvaro Alonso; Steven R. Cummings; et al. (Molecular Neurobiology, 2017)

Using multitemporal night-time lights data to compare regional development in Russia and China, 1992–2012 - Mia M. Bennett; Laurence C. Smith (International Journal of Remote Sensing, 2017)

Reconstructing overfishing: Moving beyond Malthus for effective and equitable solutions - Elena M Finkbeiner; Nathan J Bennett; Timothy H Frawley; Julia G Mason; Dana K Briscoe; Cassandra M Brooks; Crystal A Ng; Rosana Ourens; Katherine Seto; Shannon Switzer Swanson; Jose Urteaga; Larry B Crowder (Fish and Fisheries, 2017)
Inaccurate or incomplete diagnosis of the root causes of overfishing can lead to misguided and ineffective fisheries policies and programmes. The “Malthusian overfishing narrative” suggests that overfishing is driven by too many fishers chasing too few fish and that fishing effort grows proportionately to human population growth, requiring policy interventions that reduce fisher access, the number of fishers, or the human population. By neglecting other drivers of overfishing that may be more directly related to fishing pressure and provide more tangible policy levers for achieving fisheries sustainability, Malthusian overfishing relegates blame to regions of the world with high population growth rates, while consumers, corporations and political systems responsible for these other mediating drivers remain unexamined. While social–ecological systems literature has provided alternatives to the Malthusian paradigm, its focus on institutions and organized social units often fails to address fundamental issues of power and politics that have inhibited the design and implementation of effective fisheries policy. Here, we apply a political ecology lens to unpack Malthusian overfishing and, relying upon insights derived from the social sciences, reconstruct the narrative incorporating four exemplar mediating drivers: technology and innovation, resource demand and distribution, marginalization and equity, and governance and management. We argue that a more nuanced understanding of such factors will lead to effective and equitable fisheries policies and programmes, by identifying a suite of policy levers designed to address the root causes of overfishing in diverse contexts.

Calycofera gen. nov., an estuarine sister taxon to Phytopythium, Peronosporaceae - Reuel M. Bennett; Arthur W. A. M. de Cock; C. André Lévesque; Marco Thines (Mycological Progress, 2017)

Four Biofuel Species’ Responses to Periodic Flooding and High Water Tables on a Florida Histosol - Stephen P. Jennewein; Robert A. Gilbert; Diane L. Rowland; Alan L. Wright; Barry Glaz; Jerry M. Bennett (BioEnergy Research, 2017)

Angling into the Future: Ten Commandments for Recreational Fisheries Science, Management, and Stewardship in a Good Anthropocene - Laura K. Elmer; Lisa A. Kelly; Stephanie Rivest; S. Clay Steell; William M. Twardek; Andy J. Danylchuk; Robert Arlinghaus; Joseph R. Bennett; Steven J. Cooke (Environmental Management, 2017)

Site Selection: a Case Study in the Identification of Optimal Cysteine Engineered Antibody Drug Conjugates - L. Nathan Tumey; Fengping Li; Brian Rago; Xiaogang Han; Frank Loganzo; Sylvia Musto; Edmund I. Graziani; Sujiet Puthenveetil; Jeffrey Casavant; Kimberly Marquette; Tracey Clark; Jack Bikker; et al. (The AAPS Journal, 2017)

Interactive effects of temperature and p CO 2 on sponges: from the cradle to the grave - Holly M. Bennett; Christine Altenrath; Lisa Woods; Simon K. Davy; Nicole S. Webster; James J. Bell (Global Change Biology, 2017)
As atmospheric CO 2 concentrations rise, associated ocean warming ( OW ) and ocean acidification ( OA ) are predicted to cause declines in reef‐building corals globally, shifting reefs from coral‐dominated systems to those dominated by less sensitive species. Sponges are important structural and functional components of coral reef ecosystems, but despite increasing field‐based evidence that sponges may be ‘winners’ in response to environmental degradation, our understanding of how they respond to the combined effects of OW and OA is limited. To determine the tolerance of adult sponges to climate change, four abundant Great Barrier Reef species were experimentally exposed to OW and OA levels predicted for 2100, under two CO 2 Representative Concentration Pathways ( RCP s). The impact of OW and OA on early life‐history stages was also assessed for one of these species to provide a more holistic view of species impacts. All species were generally unaffected by conditions predicted under RCP 6.0, although environmental conditions projected under RCP 8.5 caused significant adverse effects: with elevated temperature decreasing the survival of all species, increasing levels of tissue necrosis and bleaching, elevating respiration rates and decreasing photosynthetic rates. OA alone had little adverse effect, even under RCP 8.5 concentrations. Importantly, the interactive effect of OW and OA varied between species with different nutritional modes, with elevated p CO 2 exacerbating temperature stress in heterotrophic species but mitigating temperature stress in phototrophic species. This antagonistic interaction was reflected by reduced mortality, necrosis and bleaching of phototrophic species in the highest OW / OA treatment. Survival and settlement success of Carteriospongia foliascens larvae were unaffected by experimental treatments, and juvenile sponges exhibited greater tolerance to OW than their adult counterparts. With elevated p CO 2 providing phototrophic species with protection from elevated temperature, across different life stages, climate change may ultimately drive a shift in the composition of sponge assemblages towards a dominance of phototrophic species.

Balancing generality and specificity in ecological gradient analysis with species abundance distributions and individual size distributions - Jian D. L. Yen; James R. Thomson; Jonathan M. Keith; David M. Paganin; Erica Fleishman; David S. Dobkin; Joanne M. Bennett; Ralph Mac Nally (Global Ecology and Biogeography, 2017)
Aim Data on ecological communities are often condensed into single‐valued diversity indices, which support comparisons among ecosystems but may discard important information. At the other extreme, some studies retain full data on the identities of all species present, which retains maximum information on community structure but occludes comparisons among ecosystems. We sought to determine whether the analysis of species abundance distributions and individual size distributions could support more detailed inferences than diversity indices while remaining sufficiently general to identify fundamental ecological responses in multiple ecosystems. Location The United States and south‐eastern Australia. Methods We analysed changes in species abundance distributions and individual size distributions along environmental gradients. We compared analyses of distributions with analyses of five diversity indices and with a distance‐based multivariate analysis of species composition. We used data from 1438 fish communities in the United States and from 840 bird communities in the western United States and south‐eastern Australia. These communities were sampled over 10–20 years and included 298 species of birds and 488 species of fishes. Results Analyses of species abundance distributions and individual size distributions identified environmental associations that were not found in analyses of diversity indices, and revealed common associations with shrubs in bird communities on different continents and with temperature in communities of birds and fishes. Individual size distributions were associated more closely with environmental variables than were species abundance distributions. Main conclusions Our novel identification of ecological associations suggests that analyses of community distributions might reveal fundamental ecological processes common to multiple ecosystems. Close associations between individual sizes and environmental variables suggest that a greater focus on size in ecological analyses might assist in the development of general models of ecological communities.

Quiet eye facilitates sensorimotor preprograming and online control of precision aiming in golf putting - Joe Causer; Spencer J. Hayes; James M. Hooper; Simon J. Bennett (Cognitive Processing, 2017)

Mainstreaming the social sciences in conservation - Nathan J. Bennett; Robin Roth; Sarah C. Klain; Kai M. A. Chan; Douglas A. Clark; Georgina Cullman; Graham Epstein; Michael Paul Nelson; Richard Stedman; Tara L. Teel; Rebecca E. W. Thomas; Carina Wyborn; et al. (Conservation Biology, 2017)
Despite broad recognition of the value of social sciences and increasingly vocal calls for better engagement with the human element of conservation, the conservation social sciences remain misunderstood and underutilized in practice. The conservation social sciences can provide unique and important contributions to society's understanding of the relationships between humans and nature and to improving conservation practice and outcomes. There are 4 barriers—ideological, institutional, knowledge, and capacity—to meaningful integration of the social sciences into conservation. We provide practical guidance on overcoming these barriers to mainstream the social sciences in conservation science, practice, and policy. Broadly, we recommend fostering knowledge on the scope and contributions of the social sciences to conservation, including social scientists from the inception of interdisciplinary research projects, incorporating social science research and insights during all stages of conservation planning and implementation, building social science capacity at all scales in conservation organizations and agencies, and promoting engagement with the social sciences in and through global conservation policy‐influencing organizations. Conservation social scientists, too, need to be willing to engage with natural science knowledge and to communicate insights and recommendations clearly. We urge the conservation community to move beyond superficial engagement with the conservation social sciences. A more inclusive and integrative conservation science—one that includes the natural and social sciences—will enable more ecologically effective and socially just conservation. Better collaboration among social scientists, natural scientists, practitioners, and policy makers will facilitate a renewed and more robust conservation. Mainstreaming the conservation social sciences will facilitate the uptake of the full range of insights and contributions from these fields into conservation policy and practice.

Research Frontiers in Ecosystem Service Science - Elena M. Bennett (Ecosystems, 2017)

Effects of ethanol storage and lipid and urea extraction on δ 15 N and δ 13 C isotope ratios in a benthic elasmobranch, the bluespotted maskray Neotrygon kuhlii - K. B. Burgess; M. B. Bennett (Journal of Fish Biology, 2017)
Ethanol storage and lipid and urea extraction had no effect on bluespotted maskray Neotrygon kuhlii muscle δ 13 C values whereas urea‐removal and ethanol storage increased δ 15 N values. Results presented here show a significant δ 15 N increase post‐urea removal and provide additional support for this approach in future elasmobranch stable‐isotope analysis ( SIA ) studies. Further experimental work on other elasmobranch species is needed to assess extraction and preservation effects on stable‐isotope ( SI ) values.

Erratum to: Time to flowering of temperate pulses in vivo and generation turnover in vivo–in vitro of narrow-leaf lupin accelerated by low red to far-red ratio and high intensity in the far-red region - Janine S. Croser; Maria Pazos-Navarro; Richard G. Bennett; Sabrina Tschirren; Kylie Edwards; William Erskine; Robert Creasy; Federico M. Ribalta (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Time to flowering of temperate pulses in vivo and generation turnover in vivo–in vitro of narrow-leaf lupin accelerated by low red to far-red ratio and high intensity in the far-red region - Janine S. Croser; Maria Pazos-Navarro; Richard G. Bennett; Sabrina Tschirren; Kylie Edwards; William Erskine; Robert Creasy; Federico M. Ribalta (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Can estimates of genetic effective population size contribute to fisheries stock assessments? - J. R. Ovenden; G. M. Leigh; D. C. Blower; A. T. Jones; A. Moore; C. Bustamante; R. C. Buckworth; M. B. Bennett; C. L. Dudgeon (Journal of Fish Biology, 2016)
Sustainable exploitation of fisheries populations is challenging to achieve when the size of the population prior to exploitation and the actual numbers removed over time and across fishing zones are not clearly known. Quantitative fisheries' modeling is able to address this problem, but accurate and reliable model outcomes depend on high quality input data. Much of this information is obtained through the operation of the fishery under consideration, but while this seems appropriate, biases may occur. For example, poorly quantified changes in fishing methods that increase catch rates can erroneously suggest that the overall population size is increasing. Hence, the incorporation of estimates of abundance derived from independent data sources is preferable. We review and evaluate a fisheries‐independent method of indexing population size; inferring adult abundance from estimates of the genetic effective size of a population ( N e ). Recent studies of elasmobranch species have shown correspondence between N e and ecologically determined estimates of the population size ( N ). Simulation studies have flagged the possibility that the range of N e / N ratios across species may be more restricted than previously thought, and also show that declines in N e track declines in the abundance of model fisheries species. These key developments bring this new technology closer to implementation in fisheries science, particularly for data‐poor fisheries or species of conservation interest.

Multiple rare variants in high-risk pancreatic cancer-related genes may increase risk for pancreatic cancer in a subset of patients with and without germline CDKN2A mutations - Xiaohong R. Yang; Melissa Rotunno; Yanzi Xiao; Christian Ingvar; Hildur Helgadottir; Lorenza Pastorino; Remco van Doorn; Hunter Bennett; Cole Graham; Joshua N. Sampson; Michael Malasky; Aurelie Vogt; et al. (Human Genetics, 2016)

Living on the edge: latitudinal variations in the reproductive biology of two coastal species of sharks - S. M. Taylor; A. V. Harry; M. B. Bennett (Journal of Fish Biology, 2016)
Differences in the reproductive biology of both the Australian weasel shark Hemigaleus australiensis and the Australian sharpnose shark Rhizoprionodon taylori were apparent between individuals from the southern‐most extent of their range in eastern Australia (Moreton Bay) and those from northern Australia. For H. australiensis from Moreton Bay the total length ( L T ) at which 50% of individuals were mature ( L T50 ) was 759 mm for females and 756 mm for males, values that were respectively 17–26% larger than reported for the species in northern Australia. The relatively low percentage (63%) of pregnant mature females and presence of small, similar‐sized, embryos in utero in both May and November suggested a semi‐synchronous, annual reproductive cycle in Moreton Bay, whereas a synchronous, biannual reproductive cycle occurred in northern Australia. It is likely that H. australiensis has a resting phase between gestation cycles at the southern‐most extent of its range. For R. taylori from Moreton Bay the L T50 s were 588 and 579 mm for females and males, respectively, values 2–3% larger than for individuals from the mid‐Queensland coast and 31–35% larger than for individuals from northern Australia. The length at which 50% of the females were maternal (611 mm L T ) in Moreton Bay was greater than the L T50 , indicating that not all sharks mate immediately after maturing. Rhizoprionodon taylori in the south had an annual reproductive cycle incorporating a 7–8 month embryonic diapause, with pups probably born in February. A mean fecundity of 7·5 was almost double that reported from northern Australia. Regional variations in the reproductive characteristics of H. australiensis and R. taylori may influence their resilience to fishing and other anthropogenic pressures. The substantial differences reported here highlight the importance of region‐specific life‐history parameters to successful management and conservation.

The effect of age and microstructural white matter integrity on lap time variation and fast-paced walking speed - Qu Tian; Luigi Ferrucci; Susan M. Resnick; Eleanor M. Simonsick; Michelle D. Shardell; Bennett A. Landman; Vijay K. Venkatraman; Christopher E. Gonzalez; Stephanie A. Studenski (Brain Imaging and Behavior, 2016)

Design and Verification of Novel Low-Cost MR-Guided Small-Animal Stereotactic System - Jonathan D. Plasencia; Leland S. Hu; Gregory H. Turner; Kevin M. Bennett; David H. Frakes (Journal of Medical and Biological Engineering, 2016)

An evaluation of the use of individual grass species in retaining polluted soil and dust particulates in vegetated sustainable drainage devices - S. M. Charlesworth; J. Bennett; A. Waite (Environmental Geochemistry and Health, 2016)

Functional characterization of glucosamine-6-phosphate synthase (GlmS) in Salmonella enterica serovar Enteritidis - Alexis M. Bennett; Daniel C. Shippy; Nicholas Eakley; Ogi Okwumabua; Amin A. Fadl (Archives of Microbiology, 2016)

Reproductive parameters of rhinobatid and urolophid batoids taken as by‐catch in the Queensland (Australia) east coast otter‐trawl fishery - P. M. Kyne; A. J. Courtney; I. P. Jacobsen; M. B. Bennett (Journal of Fish Biology, 2016)
Reproductive variables are provided for batoids regularly taken as by‐catch in the east coast otter‐trawl fishery on the inner‐mid continental shelf off the south‐east and central coasts of Queensland, Australia. Total length at maturity ( L T50 and 95% c.i .) for the eastern shovelnose ray Aptychotrema rostrata was 639·5 mm (617·6–663·4 mm) for females and 597·3 mm (551·4–648·6 mm) for males. Litter size ( n = 9) ranged from nine to 20 (mean ± s.e. = 15·1 ± 1·2). This species exhibited a positive litter size–maternal size relationship. Disc width at maturity ( W D50 and 95% c.i .) for the common stingaree Trygonoptera testacea was 162·7 mm (155·8–168·5 mm) for females and 145·9 mm (140·2–150·2 mm) for males. Gravid T. testacea ( n = 6) each carried a single egg in the one functional (left) uterus. Disc width at maturity ( W D50 and 95% c.i .) for the Kapala stingaree Urolophus kapalensis was 153·7 mm (145·1–160·4 mm) for females and 155·2 mm (149·1–159·1 mm) for males. Gravid U. kapalensis ( n = 16) each carried a single egg or embryo in the one functional (left) uterus. A single female yellowback stingaree Urolophus sufflavus carried an embryo in each uterus. A global review of the litter sizes of shovelnose rays (Rhinobatidae) and stingarees (Urolophidae) is provided.

Community assembly on isolated islands: macroecology meets evolution - A. J. Rominger; K. R. Goodman; J. Y. Lim; E. E. Armstrong; L. E. Becking; G. M Bennett; M. S. Brewer; D. D. Cotoras; C. P. Ewing; J. Harte; N. D. Martinez; P. M. O'Grady; et al. (Global Ecology and Biogeography, 2016)
Aim Understanding how ecological and evolutionary processes together determine patterns of biodiversity remains a central aim in biology. Guided by ecological theory, we use data from multiple arthropod lineages across the Hawaiian archipelago to explore the interplay between ecological (population dynamics, dispersal, trophic interactions) and evolutionary (genetic structuring, adaptation, speciation, extinction) processes. Our goal is to show how communities develop from the dynamic feedbacks that operate at different temporal and spatial scales. Location The Hawaiian islands (19–22° N , 155–160° W ). Methods We synthesize genetic data from selected arthropods across the Hawaiian archipelago to determine the relative role of dispersal and in situ differentiation across the island chronosequence. From four sites on three high islands with geological ages ranging from Results From the perspective of the island chronosequence we show that species at lower trophic levels develop population genetic structure at smaller temporal and spatial scales than species at higher trophic levels. Network nestedness decreases while modularity increases with habitat age. Single‐island endemics exhibit more specialization than broadly distributed species, but both show the least specialization in communities on middle‐aged substrates. Plant–herbivore networks also show the least deviation from theoretical predictions in middle‐aged communities. Main conclusions The application of ecological theory to island chronosequences can illuminate feedbacks between ecological and evolutionary processes in community assembly. We show how patterns of population genetic structure, decreasing network nestedness, increasing network modularity and increased specialization shift from early assembly driven by immigration, to in situ diversification after > 1 Myr. Herbivore–plant communities only transiently achieve statistical steady state during assembly, presumably due to incomplete assembly from dispersal in the early stages, and the increasing influence of island ontogeny on older islands.

Groundwater flow, nutrient, and stable isotope dynamics in the parafluvial-hyporheic zone of the regulated Lower Colorado River (Texas, USA) over the course of a small flood - Alyse C. Briody; M. Bayani Cardenas; Pin Shuai; Peter S. K. Knappett; Philip C. Bennett (Hydrogeology Journal, 2016)

Unpacking Pandora’s Box: Understanding and Categorising Ecosystem Disservices for Environmental Management and Human Wellbeing - C. M. Shackleton; S. Ruwanza; G. K. Sinasson Sanni; S. Bennett; P. De Lacy; R. Modipa; N. Mtati; M. Sachikonye; G. Thondhlana (Ecosystems, 2016)

Cognitive activity, cognitive function, and brain diffusion characteristics in old age - Konstantinos Arfanakis; Robert S. Wilson; Christopher M. Barth; Ana W. Capuano; Anil Vasireddi; Shengwei Zhang; Debra A. Fleischman; David A. Bennett (Brain Imaging and Behavior, 2016)

Sarcoplasmic reticulum is an intermediary of mitochondrial and myofibrillar growth at the intercalated disc - Pauline M. Bennett; Elisabeth Ehler; Amanda J. Wilson (Journal of Muscle Research and Cell Motility, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Seasonal Variability in Stormwater Quality Treatment of Permeable Pavements Situated Over Heavy Clay and in a Cold Climate - Ryan J. Winston; Keely M. Davidson-Bennett; Kristen M. Buccier; William F. Hunt (Water, Air, & Soil Pollution, 2016)

Potentially inappropriate prescribing in two populations with differing socio-economic profiles: a cross-sectional database study using the PROMPT criteria - Janine A. Cooper; Frank Moriarty; Cristín Ryan; Susan M. Smith; Kathleen Bennett; Tom Fahey; Emma Wallace; Caitriona Cahir; David Williams; Mary Teeling; Carmel M. Hughes (European Journal of Clinical Pharmacology, 2016)

Engagement with indigenous peoples and honoring traditional knowledge systems - Julie Maldonado; T. M. Bull Bennett; Karletta Chief; Patricia Cochran; Karen Cozzetto; Bob Gough; Margaret Hiza Redsteer; Kathy Lynn; Nancy Maynard; Garrit Voggesser (Climatic Change, 2016)

Using DNA barcoding to improve bat carcass identification at wind farms in the United States - Jennifer M. Korstian; Amanda M. Hale; Victoria J. Bennett; Dean A. Williams (Conservation Genetics Resources, 2016)

Landscape and local factors influence water purification in the Monteregian agroecosystem in Québec, Canada - Marta Terrado; Romà Tauler; Elena M. Bennett (Regional Environmental Change, 2015)

A method for PCR-based identification of bat species from fecal samples - Jennifer M. Korstian; Alison J. Schildt; Victoria J. Bennett; Dean A. Williams; Amanda M. Hale (Conservation Genetics Resources, 2015)

Biofilm formation in an experimental water distribution system: the contamination of non-touch sensor taps and the implication for healthcare - Ginny Moore; David Stevenson; Katy-Anne Thompson; Simon Parks; Didier Ngabo; Allan M. Bennett; Jimmy T. Walker (Biofouling, 2015)

Emergence, persistence, and organization of rill networks on a soil-mantled experimental landscape - Sean J. Bennett; Lee M. Gordon; Vera Neroni; Robert R. Wells (Natural Hazards, 2015)

Distal leg epidermal nerve fiber density as a surrogate marker of HIV-associated sensory neuropathy risk: risk factors and change following initial antiretroviral therapy - Cecilia M. Shikuma; Kara Bennett; Jintanat Ananworanich; Mariana Gerschenson; Nipat Teeratakulpisarn; Tanate Jadwattanakul; Victor DeGruttola; Justin C. McArthur; Gigi Ebenezer; Nitiya Chomchey; Pairoa Praihirunkit; Piranun Hongchookiat; et al. (Journal of NeuroVirology, 2015)

Continental‐scale variation in seaweed host‐associated bacterial communities is a function of host condition, not geography - Ezequiel M. Marzinelli; Alexandra H. Campbell; Enrique Zozaya Valdes; Adriana Vergés; Shaun Nielsen; Thomas Wernberg; Thibaut de Bettignies; Scott Bennett; J. Gregory Caporaso; Torsten Thomas; Peter D. Steinberg (Environmental Microbiology, 2015)
Summary Interactions between hosts and associated microbial communities can fundamentally shape the development and ecology of ‘holobionts’, from humans to marine habitat‐forming organisms such as seaweeds. In marine systems, planktonic microbial community structure is mainly driven by geography and related environmental factors, but the large‐scale drivers of host‐associated microbial communities are largely unknown. Using 16S‐r RNA gene sequencing, we characterized 260 seaweed‐associated bacterial and archaeal communities on the kelp E cklonia radiata from three biogeographical provinces spanning 10° of latitude and 35° of longitude across the Australian continent. These phylogenetically and taxonomically diverse communities were more strongly and consistently associated with host condition than geographical location or environmental variables, and a ‘core’ microbial community characteristic of healthy kelps appears to be lost when hosts become stressed. Microbial communities on stressed individuals were more similar to each other among locations than those on healthy hosts. In contrast to biogeographical patterns of planktonic marine microbial communities, host traits emerge as critical determinants of associated microbial community structure of these holobionts, even at a continental scale.

Age and growth of the tiger shark Galeocerdo cuvier off the east coast of Australia - B. J. Holmes; V. M. Peddemors; A. N. Gutteridge; P. T. Geraghty; R. W. K. Chan; I. R. Tibbetts; M. B. Bennett (Journal of Fish Biology, 2015)
Total lengths ( L T ) at age and growth rates for south‐west Pacific Galeocerdo cuvier were estimated from vertebral growth‐band counts of 202 sagitally sectioned centra from 112 females (71–430 cm L T ), 79 males (72–351 cm L T ) and 11 of unknown sex. Captive growth data were also examined to complement vertebral age estimations. The sexes combined modelled growth coefficient ( k = 0·08) was smaller than previously reported for G. cuvier populations elsewhere. Split‐band and narrow banding patterns were identified as potential sources of age underestimation in this species.

Assessment of toxicity and coagulopathy of brodifacoum in Japanese quail and testing in wild owls - Kirstin H. Webster; Kendal E. Harr; Darin C. Bennett; Tony D. Williams; Kimberly M. Cheng; France Maisonneuve; John E. Elliott (Ecotoxicology, 2015)

In vitro co-cultures of Pinus pinaster with Bursaphelenchus xylophilus: a biotechnological approach to study pine wilt disease - Jorge M. S. Faria; Inês Sena; Inês Vieira da Silva; Bruno Ribeiro; Pedro Barbosa; Lia Ascensão; Richard N. Bennett; Manuel Mota; A. Cristina Figueiredo (Planta, 2015)

Effect of risk aversion on prioritizing conservation projects - Ayesha I.T. Tulloch; Richard F. Maloney; Liana N. Joseph; Joseph R. Bennett; Martina M.I. Di Fonzo; William J.M. Probert; Shaun M. O'Connor; Jodie P. Densem; Hugh P. Possingham (Conservation Biology, 2015)
Conservation outcomes are uncertain. Agencies making decisions about what threat mitigation actions to take to save which species frequently face the dilemma of whether to invest in actions with high probability of success and guaranteed benefits or to choose projects with a greater risk of failure that might provide higher benefits if they succeed. The answer to this dilemma lies in the decision maker's aversion to risk—their unwillingness to accept uncertain outcomes. Little guidance exists on how risk preferences affect conservation investment priorities. Using a prioritization approach based on cost effectiveness, we compared 2 approaches: a conservative probability threshold approach that excludes investment in projects with a risk of management failure greater than a fixed level, and a variance‐discounting heuristic used in economics that explicitly accounts for risk tolerance and the probabilities of management success and failure. We applied both approaches to prioritizing projects for 700 of New Zealand's threatened species across 8303 management actions. Both decision makers’ risk tolerance and our choice of approach to dealing with risk preferences drove the prioritization solution (i.e., the species selected for management). Use of a probability threshold minimized uncertainty, but more expensive projects were selected than with variance discounting, which maximized expected benefits by selecting the management of species with higher extinction risk and higher conservation value. Explicitly incorporating risk preferences within the decision making process reduced the number of species expected to be safe from extinction because lower risk tolerance resulted in more species being excluded from management, but the approach allowed decision makers to choose a level of acceptable risk that fit with their ability to accommodate failure. We argue for transparency in risk tolerance and recommend that decision makers accept risk in an adaptive management framework to maximize benefits and avoid potential extinctions due to inefficient allocation of limited resources. El Efecto de la Aversión de Riesgo sobre la Priorización de Proyectos de Conservación

Ecology of the invasive New Zealand mud snail, Potamopyrgus antipodarum (Hydrobiidae), in a mediterranean-climate stream system - Danuta M. Bennett; Tom L. Dudley; Scott D. Cooper; Samuel S. Sweet (Hydrobiologia, 2015)

Influence of sex on genetic regulation of “drinking in the dark” alcohol consumption - Lauren A. Vanderlinden; Laura M. Saba; Beth Bennett; Paula L. Hoffman; Boris Tabakoff (Mammalian Genome, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

In contrast to many other mammals, cetaceans have relatively small hippocampi that appear to lack adult neurogenesis - Nina Patzke; Muhammad A. Spocter; Karl Æ. Karlsson; Mads F. Bertelsen; Mark Haagensen; Richard Chawana; Sonja Streicher; Consolate Kaswera; Emmanuel Gilissen; Abdulaziz N. Alagaili; Osama B. Mohammed; Roger L. Reep; et al. (Brain Structure and Function, 2015)

Effects of Antibiotic Physicochemical Properties on Their Release Kinetics from Biodegradable Polymer Microparticles - Sarita R. Shah; Allan M. Henslee; Patrick P. Spicer; Shun Yokota; Sophia Petrichenko; Sachin Allahabadi; George N. Bennett; Mark E. Wong; F. Kurtis Kasper; Antonios G. Mikos (Pharmaceutical Research, 2014)

Mitochondrial Oxidative Phosphorylation Transcriptome Alterations in Human Amyotrophic Lateral Sclerosis Spinal Cord and Blood - Amy C. Ladd; Paula M. Keeney; Maria M. Govind; James P. Bennett (NeuroMolecular Medicine, 2014)

Responsiveness of cardiometabolic-related microbiota to diet is influenced by host genetics - Annalouise O’Connor; Pamela M. Quizon; Jody E. Albright; Fred T. Lin; Brian J. Bennett (Mammalian Genome, 2014)

Temperate forest fragments maintain aboveground carbon stocks out to the forest edge despite changes in community composition - Carly Ziter; Elena M. Bennett; Andrew Gonzalez (Oecologia, 2014)

Not all fish are equal: functional biodiversity of cartilaginous fishes (Elasmobranchii and Holocephali) in Chile - C. Bustamante; C. Vargas‐Caro; M. B. Bennett (Journal of Fish Biology, 2014)
A review of the primary literature on the cartilaginous fishes (sharks, skates, rays and chimaeras), together with new information suggests that 106 species occur in Chilean waters, comprising 58 sharks, 30 skates, 13 rays and five chimaeras. The presence of 93 species was confirmed, although 30 species were encountered rarely, through validated catch records and sightings made in artisanal and commercial fisheries and on specific research cruises. Overall, only 63 species appear to have a range distribution that normally includes Chilean waters. Actual reliable records of occurrence are lacking for 13 species. Chile has a cartilaginous fish fauna that is relatively impoverished compared with the global species inventory, but conservative compared with countries in South America with warm‐temperate waters. The region of highest species richness occurs in the mid‐Chilean latitudes of c. 30– 40° S . This region represents a transition zone with a mix of species related to both the warm‐temperate Peruvian province to the north and cold‐temperate Magellan province to the south. This study provides clarification of species occurrence and the functional biodiversity of Chile's cartilaginous fish fauna.

Small Molecule Specific Run Acceptance, Specific Assay Operation, and Chromatographic Run Quality Assessment: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Teams - Eric J. Woolf; Stuart McDougall; Douglas M. Fast; Maristela Andraus; Matthew Barfield; Michael Blackburn; Ben Gordon; David Hoffman; Noriko Inoue; Gabriel Marcelin-Jimenez; Amy Flynn; Richard LeLacheur; et al. (The AAPS Journal, 2014)

In vitro co-culture of Solanum tuberosum hairy roots with Meloidogyne chitwoodi: structure, growth and production of volatiles - Jorge M. S. Faria; Inês Sena; Carla M. Maleita; Inês Vieira da Silva; Lia Ascensão; Isabel Abrantes; Richard N. Bennett; Manuel Mota; A. Cristina Figueiredo (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Shifts in the seasonal distribution of deaths in Australia, 1968–2007 - Charmian M. Bennett; Keith B. G. Dear; Anthony J. McMichael (International Journal of Biometeorology, 2014)

Anthropogenic‐based regional‐scale factors most consistently explain plot‐level exotic diversity in grasslands - Andrew S. MacDougall; Joseph R. Bennett; Jennifer Firn; Eric W. Seabloom; Elizabeth T. Borer; Eric M. Lind; John L. Orrock; W. Stanley Harpole; Yann Hautier; Peter B. Adler; Elsa Cleland; Kendi Davies; et al. (Global Ecology and Biogeography, 2014)
Aim Evidence linking the accumulation of exotic species to the suppression of native diversity is equivocal, often relying on data from studies that have used different methods. Plot‐level studies often attribute inverse relationships between native and exotic diversity to competition, but regional abiotic filters, including anthropogenic influences, can produce similar patterns. We seek to test these alternatives using identical scale‐dependent sampling protocols in multiple grasslands on two continents. Location Thirty‐two grassland sites in N orth A merica and A ustralia. Methods We use multiscale observational data, collected identically in grain and extent at each site, to test the association of local and regional factors with the plot‐level richness and abundance of native and exotic plants. Sites captured environmental and anthropogenic gradients including land‐use intensity, human population density, light and soil resources, climate and elevation. Site selection occurred independently of exotic diversity, meaning that the numbers of exotic species varied randomly thereby reducing potential biases if only highly invaded sites were chosen. Results Regional factors associated directly or indirectly with human activity had the strongest associations with plot‐level diversity. These regional drivers had divergent effects: urban‐based economic activity was associated with high exotic : native diversity ratios; climate‐ and landscape‐based indicators of lower human population density were associated with low exotic : native ratios. Negative correlations between plot‐level native and exotic diversity, a potential signature of competitive interactions, were not prevalent; this result did not change along gradients of productivity or heterogeneity. Main conclusion We show that plot‐level diversity of native and exotic plants are more consistently associated with regional‐scale factors relating to urbanization and climate suitability than measures indicative of competition. These findings clarify the long‐standing difficulty in resolving drivers of exotic diversity using single‐factor mechanisms, suggesting that multiple interacting anthropogenic‐based processes best explain the accumulation of exotic diversity in modern landscapes.

Exome sequencing and arrayCGH detection of gene sequence and copy number variation between ILS and ISS mouse strains - Laura Dumas; C. Michael Dickens; Nathan Anderson; Jonathan Davis; Beth Bennett; Richard A. Radcliffe; James M. Sikela (Mammalian Genome, 2014)

Population dynamics of the reef manta ray Manta alfredi in eastern Australia - L. I. E. Couturier; C. L. Dudgeon; K. H. Pollock; F. R. A. Jaine; M. B. Bennett; K. A. Townsend; S. J. Weeks; A. J. Richardson (Coral Reefs, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Prevalence of potentially inappropriate prescribing and prescribing omissions in older Irish adults: findings from The Irish LongituDinal Study on Ageing study (TILDA) - Rose Galvin; Frank Moriarty; Gráinne Cousins; Caitriona Cahir; Nicola Motterlini; Marie Bradley; Carmel M. Hughes; Kathleen Bennett; Susan M. Smith; Tom Fahey; Rose-Anne Kenny (European Journal of Clinical Pharmacology, 2014)

Model invasions and the development of national concerns over invasive introduced trees: insights from South African history - Brett M. Bennett (Biological Invasions, 2014)

Conflicting values: ecosystem services and invasive tree management - Ian A. Dickie; Brett M. Bennett; Larry E. Burrows; Martin A. Nuñez; Duane A. Peltzer; Annabel Porté; David M. Richardson; Marcel Rejmánek; Philip W. Rundel; Brian W. van Wilgen (Biological Invasions, 2014)

Aerobic fitness and cognitive function in midlife: an association mediated by plasma insulin - Takashi Tarumi; Mitzi M. Gonzales; Bennett Fallow; Nantinee Nualnim; Jeongseok Lee; Hirofumi Tanaka; Andreana P. Haley (Metabolic Brain Disease, 2013)

Liver glucose-6-phosphatase proteins in suckling and weaned grey seal pups: structural similarities to other mammals and relationship to nutrition, insulin signalling and metabolite levels - K. A. Bennett; M. Hammill; S. Currie (Journal of Comparative Physiology B, 2013)

The interaction between a drying climate and land use affects forest structure and above‐ground carbon storage - Joanne M. Bennett; Shaun C. Cunningham; Christine A. Connelly; Rohan H. Clarke; James R. Thomson; Ralph Mac Nally (Global Ecology and Biogeography, 2013)
Aim Climate change has been linked to negative effects on vegetation, including drought‐induced dieback. Large‐scale dieback not only leads to considerable carbon emissions but often leads to loss of ecological resources. We investigated whether, and how, the structure, composition and carbon content changed over a period of extended drought (the ‘ B ig D ry’) in a much‐modified forest ecosystem. We explored whether landscape configuration, management practice or soil type influenced vegetation change. Location The B ox‐ I ronbark forests of south‐eastern A ustralia. Methods In 2010, we remeasured 120 forest transects that had first been measured in 1997 by using identical field methods. Vegetation structure and composition were quantified. We used allometric growth models to estimate the expected increase in above‐ground carbon ( AGC ) storage between 1997 and 2010; these estimates were compared with observed values. Results Forest structure was systematically different between the two periods. Canopy cover, shrub cover and litter decreased between the 1997 and 2010 surveys, whereas total basal area of dead trees, dead trees in all size classes and saplings increased between the two surveys. Climate, fragment size and their interaction were the major predictors of change in most of the measured vegetation characteristics. By comparing measured AGC in 2010 and estimates from growth models, we estimated that 5.6 ± 2.1 SE t C ha −1 may have been foregone over the B ig D ry. Main conclusions Our findings add to the evidence linking climate change to negative effects on vegetation, including mortality, canopy dieback and reduced carbon sequestration. These effects may be amplified in fragmented vegetation because of greater water and heat stress. If the carbon sequestration deficit of c. 5.6 t C ha −1 were to apply across the extant Box‐Ironbark forests of V ictoria ( c . 255,400 ha), then 1.43 M t of carbon sequestration may not have occurred during the B ig D ry.

Seasonal changes in burrow geometry of the common mole rat (Rodentia: Bathyergidae) - H. G. Thomas; M. Scantlebury; D. Swanepoel; P. W. Bateman; N. C. Bennett (The Science of Nature, 2013)

Sex-biased dispersal in a rare butterfly and the implications for its conservation - Victoria J. Bennett; Shalynn M. Pack; Winston P. Smith; Matthew G. Betts (Journal of Insect Conservation, 2013)

A standardised protocol for the validation of banking methodologies for arterial allografts - R. J. Lomas; P. D. F. Dodd; P. Rooney; D. E. Pegg; P. A. Hogg; M. E. Eagle; K. E. Bennett; A. Clarkson; J. N. Kearney (Cell and Tissue Banking, 2013)

Increased competition does not lead to increased phylogenetic overdispersion in a native grassland - Jonathan A. Bennett; Eric G. Lamb; Jocelyn C. Hall; Warren M. Cardinal‐McTeague; James F. Cahill (Ecology Letters, 2013)
That competition is stronger among closely related species and leads to phylogenetic overdispersion is a common assumption in community ecology. However, tests of this assumption are rare and field‐based experiments lacking. We tested the relationship between competition, the degree of relatedness, and overdispersion among plants experimentally and using a field survey in a native grassland. Relatedness did not affect competition, nor was competition associated with phylogenetic overdispersion. Further, there was only weak evidence for increased overdispersion at spatial scales where plants are likely to compete. These results challenge traditional theory, but are consistent with recent theories regarding the mechanisms of plant competition and its potential effect on phylogenetic structure. We suggest that specific conditions related to the form of competition and trait conservatism must be met for competition to cause phylogenetic overdispersion. Consequently, overdispersion as a result of competition is likely to be rare in natural communities.

Diatom-inference models for acid neutralizing capacity and nitrate based on 41 calibration lakes in the Sierra Nevada, California, USA - James O. Sickman; Danuta M. Bennett; Delores M. Lucero; Thomas J. Whitmore; William F. Kenney (Journal of Paleolimnology, 2013)

Linking Landscape Connectivity and Ecosystem Service Provision: Current Knowledge and Research Gaps - Matthew G. E. Mitchell; Elena M. Bennett; Andrew Gonzalez (Ecosystems, 2013)

Historical biogeography and ecological opportunity in the adaptive radiation of native Hawaiian leafhoppers (Cicadellidae: Nesophrosyne ) - Gordon M. Bennett; Patrick M. O'Grady (Journal of Biogeography, 2013)
Aim Our aims were to infer the roles of ecology and geology in the adaptive radiation, historical biogeography, and diversification dynamics of the native Hawaiian leafhoppers (Hemiptera: Cicadellidae: Nesophrosyne ). Location The Hawaiian Archipelago. Methods A six gene molecular data set for 191 Nesophrosyne species was used to reconstruct relationships in absolute time with relaxed Bayesian methods. Dated phylogenetic hypotheses were used to reconstruct historical biogeography and host plant associations. Phylogenetic clustering methods were implemented to examine the structuring of Nesophrosyne species according to island. Lineage diversification dynamics were inferred using the γ‐statistic and birth–death likelihood methods. Results Nesophrosyne split from a common ancestor with its sister genus 4.5 million years ago (Ma), with a basal divergence in Hawaii 3.2 Ma. Historical biogeographical reconstructions reveal a Kauai origin for the genus and complex island colonization patterns. Ancestral host plant associations reconstruct Urticaceae and Rubiaceae at the root, with host transitions resulting in host‐specific clades. Only species endemic to Kauai are significantly clustered with respect to the whole phylogeny; however, species show significant terminal level clustering for the four main high islands. Diversification rates in Nesophrosyne show an initial burst in net speciation rate with a subsequent decline. Main conclusions Nesophrosyne colonized the Hawaiian Islands after the formation of Kauai. Host plant arrival times and insect–insect competition may have been important in shaping diversification patterns. The plant families Urticaceae and Rubiaceae played critical roles in the early diversification of Nesophrosyne . Island geography imposed significant barriers to gene flow, leading to extensive allopatric speciation and intra‐island diversification. A high initial net speciation rate was associated with host plant transitions, and the formation and establishment of Nesophrosyne on multi‐volcano islands (e.g. Oahu and Maui Nui). Net diversification rates exhibit a diversity‐dependent decline, corresponding to the end phase of island formation.

Saw palmetto ethanol extract inhibits adipocyte differentiation - Nicole Villaverde; Adriana Galvis; Adriana Marcano; Horacio A. Priestap; Bradley C. Bennett; M. Alejandro Barbieri (Journal of Natural Medicines, 2013)

An analysis of displacement from wind turbines in a wintering grassland bird community - T. K. Stevens; A. M. Hale; K. B. Karsten; V. J. Bennett (Biodiversity and Conservation, 2013)

Comparative morphology of the egg cases of Asymbolus analis , Asymbolus rubiginosus and Figaro boardmani (Carcharhiniformes: Scyliorhinidae) from southern Queensland, Australia - C. Bustamante; P. M. Kyne; M. B. Bennett (Journal of Fish Biology, 2013)
Descriptions of the egg cases of three catsharks, Asymbolus analis , Asymbolus rubiginosus and Figaro boardmani , are provided from 65 egg cases obtained from fishing surveys carried out on the continental shelf of southern Queensland, Australia. Egg cases of A. analis , A. rubiginosus and F. boardmani have the same basic morphology; they are typically vase‐shaped, dorso‐ventrally flattened and yellow and brown‐tan in colour. The shape of the posterior border in terms of horn length and tendril thickness is the specific characteristic discriminating these three catsharks: enclosed horns in F. boardmani , short horns and tendrils in A . rubiginosus and long, coiled tendrils in A . analis . A non‐parametric statistical approach was used as an exploratory tool for egg case identification in which six proportional measurements were sufficient to discriminate between species. Three egg cases of F . boardmani were recovered from the stomachs of three A. rubiginosus , which provided the first evidence of catshark–catshark predator–prey interaction.

Evolutionary replacement of obligate symbionts in an ancient and diverse insect lineage - Ryuichi Koga; Gordon M. Bennett; Jason R. Cryan; Nancy A. Moran (Environmental Microbiology, 2013)
Summary Many insect groups depend on ancient obligate symbioses with bacteria that undergo long‐term genomic degradation due to inactivation and loss of ancestral genes. Sap‐feeding insects in the hemipteran suborder A uchenorrhyncha show complex symbioses with at least two obligate bacterial symbionts, inhabiting specialized host cells (bacteriocytes). We explored the symbiotic relationships of the spittlebugs ( A uchenorrhyncha: C ercopoidea) using phylogenetic and microscopy methods. Results show that most spittlebugs contain the symbionts S ulcia muelleri ( B acteroidetes ) and Z inderia insecticola ( B etaproteobacteria ) with each restricted to its own bacteriocyte type. However, the ancestral Z inderia symbiont has been replaced with a novel symbiont closely related to S odalis glossinidius ( E nterobacteriaceae ) in members of the ecologically successful spittlebug tribe P hilaenini. At least one spittlebug species retains S ulcia and Z inderia , but also has acquired a S odalis ‐like symbiont, possibly representing a transitional stage in the evolutionary succession of symbioses. Phylogenetic analyses including symbionts of other A uchenorrhyncha lineages suggest that Z inderia , like S ulcia , descends from an ancestral symbiont present in the common ancestor of A uchenorrhyncha. This betaproteobacterial symbiont has been repeatedly replaced by other symbionts, such as the S odalis ‐like symbiont of spittlebugs. Symbiont replacement may offer a route for hosts to escape dependence on an ancient, degraded and potentially inefficient symbiont.

Asset Management and Safety Assessment of Levees and Earthen Dams Through Comprehensive Real-Time Field Monitoring - T. Abdoun; V. Bennett; T. Desrosiers; J. Simm; M. Barendse (Geotechnical and Geological Engineering, 2013)

Evaluation of the sea anemone Anthothoe albocincta as an augmentative biocontrol agent for biofouling on artificial structures - Javier Atalah; Holly Bennett; Grant A. Hopkins; Barrie M. Forrest (Biofouling, 2013)

Fire Mosaics and Reptile Conservation in a Fire‐Prone Region - D. G. NIMMO; L. T. KELLY; L. M. SPENCE‐BAILEY; S. J. WATSON; R. S. TAYLOR; M. F. CLARKE; A. F. BENNETT (Conservation Biology, 2013)
Fire influences the distribution of fauna in terrestrial biomes throughout the world. Use of fire to achieve a mosaic of vegetation in different stages of succession after burning (i.e., patch‐mosaic burning) is a dominant conservation practice in many regions. Despite this, knowledge of how the spatial attributes of vegetation mosaics created by fire affect fauna is extremely scarce, and it is unclear what kind of mosaic land managers should aim to achieve. We selected 28 landscapes (each 12.6 km 2 ) that varied in the spatial extent and diversity of vegetation succession after fire in a 104,000 km 2 area in the semiarid region of southeastern Australia. We surveyed for reptiles at 280 sites nested within the 28 landscapes. The landscape‐level occurrence of 9 of the 22 species modeled was associated with the spatial extent of vegetation age classes created by fire. Biogeographic context and the extent of a vegetation type influenced 7 and 4 species, respectively. No species were associated with the diversity of vegetation ages within a landscape. Negative relations between reptile occurrence and both extent of recently burned vegetation (≤10 years postfire, n = 6) and long unburned vegetation (>35 years postfire, n = 4) suggested that a coarse‐grained mosaic of areas (e.g. >1000 ha) of midsuccessional vegetation (11–35 years postfire) may support the fire‐sensitive reptile species we modeled. This age class coincides with a peak in spinifex cover, a keystone structure for reptiles in semiarid and arid Australia. Maintaining over the long term a coarse‐grained mosaic of large areas of midsuccessional vegetation in mallee ecosystems will need to be balanced against the short‐term negative effects of large fires on many reptile species and a documented preference by species from other taxonomic groups, particularly birds, for older vegetation. Mosaicos de Fuego y la Conservación de Reptiles en una Región Propensa al Fuego

System for Integrated Neuroimaging Analysis and Processing of Structure - Bennett A. Landman; John A. Bogovic; Aaron Carass; Min Chen; Snehashis Roy; Navid Shiee; Zhen Yang; Bhaskar Kishore; Dzung Pham; Pierre-Louis Bazin; Susan M. Resnick; Jerry L. Prince (Neuroinformatics, 2013)

Perception of 3-D location based on vision, touch, and extended touch - Nicholas A. Giudice; Roberta L. Klatzky; Christopher R. Bennett; Jack M. Loomis (Experimental Brain Research, 2013)

Aerobic Fitness and the Brain: Increased N-Acetyl-Aspartate and Choline Concentrations in Endurance-Trained Middle-Aged Adults - Mitzi M. Gonzales; Takashi Tarumi; Sonya Kaur; Nantinee Nualnim; Bennett A. Fallow; Martha Pyron; Hirofumi Tanaka; Andreana P. Haley (Brain Topography, 2013)

Size, sex and seasonal patterns in the assemblage of Carcharhiniformes in a sub‐tropical bay - S. M. Taylor; M. B. Bennett (Journal of Fish Biology, 2013)
Size, sex and seasonal patterns among Carcharhiniformes were examined in shallow regions of Moreton Bay, Queensland, Australia. A total of 1259 sharks were caught, comprising 13 species. The Australian sharpnose shark Rhizoprionodon taylori and the blacktip complex Carcharhinus limbatus – Carcharhinus tilstoni comprised 55% of all shark individuals. Neonates were observed for five species including the dusky shark Carcharhinus obscurus , which contrary to previous reports was relatively abundant in shallow, predominantly estuarine waters. Three contrasting patterns of occurrence were observed: smaller species were abundant and present throughout much of their ontogeny, larger species were mainly caught as neonates or juveniles and vagrant species were only caught during the warmer months. The shark assemblage differed significantly among seasons. While many species were observed during the warmer months, species diversity was lower in winter when C. obscurus comprised 43% of the catch. Overall, the results indicated that spatial and temporal distribution patterns were not synchronous for all species. The capture of small numbers of neonate C. obscurus in late autumn and winter demonstrates that parturition among Carcharhiniformes is not confined to spring and summer in sub‐tropical waters.

Predicting the century‐long post‐fire responses of reptiles - Dale. G. Nimmo; Luke T. Kelly; Lisa M. Spence‐Bailey; Simon J. Watson; Angie Haslem; John G. White; Mike F. Clarke; Andrew F. Bennett (Global Ecology and Biogeography, 2012)
Aim We examined the century‐long post‐fire responses of reptiles to (1) determine the time‐scales over which fauna – fire relationships occur, (2) assess the capacity of a conceptual model to predict faunal response to fire, and (3) investigate the degree to which models of fauna – fire relationships can predict species occurrence and are transferable across space. Location A 104,000 km 2 area in the semi‐arid Murray Mallee region of south‐eastern Australia. Methods We surveyed reptiles at 280 sites across a century‐long post‐fire chronosequence. We developed generalized additive mixed models (GAMMs) of the relationship between time since fire and the occurrence of 17 species in two subregions, and compared modelled responses with predictions derived from the conceptual model. The predictive capacity of GAMMs was then assessed (1) within the subregion the model was developed and (2) when transferred into a novel subregion. Results Eleven species displayed a significant relationship with time‐since‐fire, with changes in species probability of occurrence continuing up to 100 years post‐fire. Predictions of the timing of species post‐fire peak in occurrence were accurate for 9 of 13 species models for which a significant fire response was detected, but little success was achieved in predicting the shape of a species' response. GAMMs predicted species occurrence more accurately when applied within the subregion in which they were developed than when transferred into a novel subregion, primarily due to some species responding to fire more strongly in one part of their geographic range. Main conclusions Fire influences the occurrence of reptiles in semi‐arid ecosystems over century‐long time frames. Habitat‐use conceptual models have value in predicting the peak occurrence of species following fire, particularly for species with distributions strongly shaped by fire. Species relationships with fire can differ across their geographic range, probably associated with variation in climatic influences on post‐fire succession and the consequent provision of habitat resources.

Differences in activity level between cownose rays (Rhinoptera bonasus) and Atlantic stingrays (Dasyatis sabina) are related to differences in heart mass, hemoglobin concentration, and gill surface area - Jeffrey M. Grim; A. Adam Ding; Wayne A. Bennett (Fish Physiology and Biochemistry, 2012)

Potentially inappropriate prescribing and cost outcomes for older people: a cross-sectional study using the Northern Ireland Enhanced Prescribing Database - Marie C. Bradley; Tom Fahey; Caitriona Cahir; Kathleen Bennett; Dermot O’Reilly; Carole Parsons; Carmel M. Hughes (European Journal of Clinical Pharmacology, 2012)

TOMM40 in Cerebral Amyloid Angiopathy Related Intracerebral Hemorrhage: Comparative Genetic Analysis with Alzheimer’s Disease - Valerie Valant; Brendan T. Keenan; Christopher D. Anderson; Joshua M. Shulman; William J. Devan; Alison M. Ayres; Kristin Schwab; Joshua N. Goldstein; Anand Viswanathan; Steven M. Greenberg; David A. Bennett; Philip L. De Jager; et al. (Translational Stroke Research, 2012)

Evaluating the traditional Chinese literature for herbal formulae and individual herbs used for age-related dementia and memory impairment - Brian H. May; Chuanjian Lu; Louise Bennett; Helmut M. Hügel; Charlie C. L. Xue (Biogerontology, 2012)

The influence of time, soil characteristics, and land‐use history on soil phosphorus legacies: a global meta‐analysis - Graham K. MacDonald; Elena M. Bennett; Zofia E. Taranu (Global Change Biology, 2012)
Agriculturally driven changes in soil phosphorus ( P ) are known to have persistent effects on local ecosystem structure and function, but regional patterns of soil P recovery following cessation of agriculture are less well understood. We synthesized data from 94 published studies to assess evidence of these land‐use legacies throughout the world by comparing soil labile and total P content in abandoned agricultural areas to that of reference ecosystems or sites remaining in agriculture. Our meta‐analysis shows that soil P content was typically elevated after abandonment compared to reference levels, but reduced compared to soils that remained under agriculture. There were more pronounced differences in the legacies of past agriculture on soil P across regions than between the types of land use practiced prior to abandonment (cropland, pasture, or forage grassland). However, consistent patterns of soil P enrichment or depletion according to soil order and types of post‐agricultural vegetation suggest that these factors may mediate agricultural legacies on soil P . We also used mixed effects models to examine the role of multiple variables on soil P recovery following agriculture. Time since cessation of agriculture was highly influential on soil P legacies, with clear reductions in the degree of labile and total P enrichment relative to reference ecosystems over time. Soil characteristics (clay content and pH ) were strongly related to changes in labile P compared to reference sites, but these were relatively unimportant for total P . The duration of past agricultural use and climate were weakly related to changes in total P only. Our finding of reductions in the degree of soil P alteration over time relative to reference conditions reveals the potential to mitigate these land‐use legacies in some soils. Better ability to predict dynamics of soil nutrient recovery after termination of agricultural use is essential to ecosystem management following land‐use change.

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Wildlife trade products available to U.S. military personnel serving abroad - Heidi E. Kretser; McKenzie F. Johnson; Lisa M. Hickey; Peter Zahler; Elizabeth L. Bennett (Biodiversity and Conservation, 2012)

Biology, ecology and conservation of the Mobulidae - L. I. E. Couturier; A. D. Marshall; F. R. A. Jaine; T. Kashiwagi; S. J. Pierce; K. A. Townsend; S. J. Weeks; M. B. Bennett; A. J. Richardson (Journal of Fish Biology, 2012)
The Mobulidae are zooplanktivorous elasmobranchs comprising two recognized species of manta rays ( Manta spp.) and nine recognized species of devil rays ( Mobula spp.). They are found circumglobally in tropical, subtropical and temperate coastal waters. Although mobulids have been recorded for over 400 years, critical knowledge gaps still compromise the ability to assess the status of these species. On the basis of a review of 263 publications, a comparative synthesis of the biology and ecology of mobulids was conducted to examine their evolution, taxonomy, distribution, population trends, movements and aggregation, reproduction, growth and longevity, feeding, natural mortality and direct and indirect anthropogenic threats. There has been a marked increase in the number of published studies on mobulids since c . 1990, particularly for the genus Manta , although the genus Mobula remains poorly understood. Mobulid species have many common biological characteristics although their ecologies appear to be species‐specific, and sometimes region‐specific. Movement studies suggest that mobulids are highly mobile and have the potential to rapidly travel large distances. Fishing pressure is the major threat to many mobulid populations, with current levels of exploitation in target fisheries unlikely to be sustainable. Advances in the fields of population genetics, acoustic and satellite tracking, and stable‐isotope and fatty‐acid analyses will provide new insights into the biology and ecology of these species. Future research should focus on the uncertain taxonomy of mobulid species, the degree of overlap between their large‐scale movement and human activities such as fisheries and pollution, and the need for management of inter‐jurisdictional fisheries in developing nations to ensure their long‐term sustainability. Closer collaboration among researchers worldwide is necessary to ensure standardized sampling and modelling methodologies to underpin global population estimates and status.

Reproductive biology of Zearaja chilensis (Chondrichthyes: Rajidae) in the south‐east Pacific Ocean - C. Bustamante; C. Vargas‐Caro; M. C. Oddone; F. Concha; H. Flores; J. Lamilla; M. B. Bennett (Journal of Fish Biology, 2012)
Between 2000 and 2002, three artisanal landing sites were sampled in southern Chile, with data on population structure and reproductive development collected from 5477 yellownose skates Zearaja chilensis . Total length ( L T ) ranged from 33 to 158 cm for females and 34 to 155 cm for males. No sexual dimorphism was evident in disc size (length or width) or in L T – mass relationships. The smallest mature female was 95 cm L T and the size at which 50% were mature ( L T50 ) was 109 cm. Males matured between 80 and 90 cm L T with a L T50 of 88 cm. Although the largest Z . chilensis captured by the artisanal fishery was 155 cm L T , 89% of landings comprised relatively small, immature fish. This situation may compromise the stock integrity if intrinsic vulnerability and probable long‐life span of Z . chilensis are considered. Consequences for the survival of the species and possible signs of a fishery collapse must be reviewed by management authorities by consideration of both artisanal and industrial landings in Chile.

Feeding ecology and dietary comparisons among three sympatric Neotrygon (Myliobatoidei: Dasyatidae) species - I. P. Jacobsen; M. B. Bennett (Journal of Fish Biology, 2012)
The diets of Neotrygon picta , Neotrygon kuhlii and Neotrygon annotata are described using trophic level analysis, index of relative importance ( I RI ) and non‐metric multidimensional scaling ordination (nMDS). They were secondary consumers with trophic levels of between 3·55 and 3·58. Carids were the most important prey category in the diets of N. picta (82·0% I RI ) and N. annotata (69·4% I RI ); Polychaeta (72·3% I RI ) was the most important prey category for N. kuhlii . A significant difference was detected between the volumetric dietary data of all three species (ANOSIM, global R ‐statistic = 0·742, P N. picta and N. kuhlii size classes (ANOSIM, global R ‐statistics = 0·367–0·403, P Neotrygon species, and the potential for resource partitioning to occur when these species coexist.

Developing X-ray Computed Tomography to non-invasively image 3-D root systems architecture in soil - S. J. Mooney; T. P. Pridmore; J. Helliwell; M. J. Bennett (Plant and Soil, 2012)

The Influence of Agricultural Trade and Livestock Production on the Global Phosphorus Cycle - Meagan E. Schipanski; Elena M. Bennett (Ecosystems, 2012)

The HPV vaccine impact monitoring project (HPV-IMPACT): assessing early evidence of vaccination impact on HPV-associated cervical cancer precursor lesions - Susan Hariri; Elizabeth R. Unger; Suzanne E. Powell; Heidi M. Bauer; Nancy M. Bennett; Karen C. Bloch; Linda M. Niccolai; Sean Schafer; Lauri E. Markowitz (Cancer Causes & Control, 2012)

Intermolt development reduces oxygen delivery capacity and jumping performance in the American locust (Schistocerca americana) - Scott D. Kirkton; Lauren E. Hennessey; Bridget Duffy; Meghan M. Bennett; Wah-Keat Lee; Kendra J. Greenlee (Journal of Comparative Physiology B, 2012)

Associations of whole-blood fatty acids and dietary intakes with prostate cancer in Jamaica - Maria D. Jackson; Susan P. Walker; Candace M. Simpson-Smith; Carole M. Lindsay; Garret Smith; Norma McFarlane-Anderson; Franklyn I. Bennett; Kathleen C. M. Coard; William D. Aiken; Trevor Tulloch; Tomlin J. Paul; Robert L. Wan (Cancer Causes & Control, 2012)

Environmental and social predictors of phosphorus in urban streams on the Island of Montréal, Québec - Laura R. Pfeifer; Elena M. Bennett (Urban Ecosystems, 2011)

The effectiveness of methicillin-resistant Staphylococcus aureus colonisation screening in asymptomatic healthcare workers in an Irish orthopaedic unit - S. P. Edmundson; K. M. Hirpara; D. Bennett (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Expression and analysis of two novel rat organic cation transporter homologs, SLC22A17 and SLC22A23 - Katie M. Bennett; Jun Liu; Courtney Hoelting; James Stoll (Molecular and Cellular Biochemistry, 2011)

Size and structure of a photographically identified population of manta rays Manta alfredi in southern Mozambique - A. D. Marshall; C. L. Dudgeon; M. B. Bennett (Marine Biology, 2011)

Assessing the overlap between the diet of a coastal shark and the surrounding prey communities in a sub‐tropical embayment - A. N. Gutteridge; M. B. Bennett; C. Huveneers; I. R. Tibbetts (Journal of Fish Biology, 2011)
An elasmobranch survey of sub‐tropical Hervey Bay, Australia, captured the slit‐eye shark Loxodon macrorhinus at only one of three sites sampled. The dietary composition of this small shark species was compared to the prey communities within Hervey Bay to test whether prey availability was driving this observation. Dietary analysis of prey groups revealed that teleosts dominated the diet, per cent index of relative importance, % I RI (79·5%) and per cent geometric index of importance, % G II (52·7%), with shrimp‐like invertebrates and cephalopods identified as the most important invertebrate prey groups. Baited remote underwater video (BRUV) used to sample prey communities at each site, demonstrated a highly diverse and significantly different community composition among the sites. There was no significant overlap between the diet of L. macrorhinus and any of the prey communities detected by BRUVs according to one‐way analysis of similarities and the simplified Morisita index. Habitat electivity analysis revealed affinity of L. macrorhinus for the site with the highest water clarity (Secchi disc depth), opposing that of three other shark species. Overall, the results suggest that the distribution of L. macrorhinus is not driven by prey availability but other factors such as water clarity, predator avoidance or a reduction in interspecies competition.

Primary-care prescribing of anti-osteoporotic-type medications following hospitalisation for fractures - Bernie M. McGowan; Kath Bennett; Joe Marry; J. B. Walsh; Miriam C. Casey (European Journal of Clinical Pharmacology, 2011)

Exploitation of the late flowering species Brassica oleracea L. for the improvement of earliness in B. napus L.: an untraditional approach - M. Habibur Rahman; Rick A. Bennett; Rong-Cai Yang; Berisso Kebede; Mohan R. Thiagarajah (Euphytica, 2011)

The control of marine biofouling on xerogel surfaces with nanometer-scale topography - Nikhil Gunari; Lenora H. Brewer; Stephanie M. Bennett; Anastasiya Sokolova; Nadine D. Kraut; John A. Finlay; Anne E. Meyer; Gilbert C. Walker; Dean E. Wendt; Maureen E. Callow; James A. Callow; Frank V. Bright; et al. (Biofouling, 2011)

Differences in NMDA Receptor Expression During Human Development Determine the Response of Neurons to HIV-Tat-mediated Neurotoxicity - E. A. Eugenin; J. E. King; J. E. Hazleton; E. O. Major; M. V. L. Bennett; R. S. Zukin; Joan W. Berman (Neurotoxicity Research, 2011)

Prioritisation of novel pasture species for use in water-limited agriculture: a case study of Cullen in the Western Australian wheatbelt - R. G. Bennett; M. H. Ryan; T. D. Colmer; D. Real (Genetic Resources and Crop Evolution, 2011)

The frequency and effect of shark-inflicted bite injuries to the reef manta ray Manta alfredi - A D Marshall; M B Bennett (African Journal of Marine Science, 2010)

Age and growth of Neotrygon picta, Neotrygon annotata and Neotrygon kuhlii from north‐east Australia, with notes on their reproductive biology - I. P. Jacobsen; M. B. Bennett (Journal of Fish Biology, 2010)
Vertebral band formations were used to define age and growth in three Neotrygon species caught regularly as by‐catch in prawn trawl fisheries in north‐east Australia. Centrum edge and marginal increment ratio analyses were used to validate annual band formations. Age estimates ranged from 1 to 18 years, with the von Bertalanffy growth function considered to have the best fit to Neotrygon picta (males, W D∞ = 271 mm, k = 0·12; females, W D∞ = 360·5 mm, k = 0·08) and Neotrygon kuhlii (males, W D∞ = 438·6 mm, k = 0·08; females, W D∞ = 440·6 mm, k = 0·08) disc width ( W D )‐at‐age data. The Gompertz growth function had the best fit to Neotrygon annotata W D ‐at‐age data (males, W D∞ = 230·4 mm, k = 0·20; females, W D∞ = 265·5 mm, k = 0·31). Age at sexual maturity ranged from 3 to 6 years, with N. picta having the smallest size at birth (100 mm W D ), smallest W D at 50% maturity ( W D50 : male, 172 mm, female, 180·7 mm) and lowest age at sexual maturity (3–4 years). This study helps redefine and improve the accuracy of fisheries‐based risk assessments for these small species with relatively conservative life‐history variables.

Inferring lake depth using diatom assemblages in the shallow, seasonally variable lakes of the Nebraska Sand Hills (USA): calibration, validation, and application of a 69-lake training set - Avery L. C. Shinneman; Danuta M. Bennett; Sherilyn C. Fritz; Jens Schmieder; Daniel R. Engstrom; Aris Efting; John Holz (Journal of Paleolimnology, 2010)

Structural features promoting dioxygen production by Dechloromonas aromatica chlorite dismutase - Brandon R. Goblirsch; Bennett R. Streit; Jennifer L. DuBois; Carrie M. Wilmot (JBIC Journal of Biological Inorganic Chemistry, 2010)

Barnacle settlement and the adhesion of protein and diatom microfouling to xerogel films with varying surface energy and water wettability - John A. Finlay; Stephanie M. Bennett; Lenora H. Brewer; Anastasiya Sokolova; Gemma Clay; Nikhil Gunari; Anne E. Meyer; Gilbert C. Walker; Dean E. Wendt; Maureen E. Callow; James A. Callow; Michael R. Detty (Biofouling, 2010)

Reproductive ecology of the reef manta ray Manta alfredi in southern Mozambique - A. D. Marshall; M. B. Bennett (Journal of Fish Biology, 2010)
The application of a photographic identification methodology using the unique ventral surface markings (natural spot patterns) of an observed population in southern Mozambique enabled many aspects of the reproductive ecology of reef manta rays Manta alfredi to be examined. The region encompassing the study site was identified as a mating ground for M. alfredi based on observations of mating events and fresh mating scars on females. The distribution of these pectoral fin scars was highly biased and indicated a strong lateralized behavioural trait, with 99% of these scars occurring only on the left pectoral fin. No other elasmobranch has been reported to display behavioural lateralization. The study region also acts as a birthing ground, with individuals typically giving birth in the austral summer period after a gestation of c . 1 year. Reproductive periodicity in M. alfredi was most commonly biennial, but a few individuals were pregnant in consecutive years, confirming an annual ovulatory cycle. The production of a single pup appears to be the normal situation, although observations in the wild as well as during opportunistic dissections of individuals killed by fisheries revealed that two pups are conceived on occasion. Many aspects of the study have contributed to the limited baseline data currently available for this species and have highlighted the potential need for more conservative conservation strategies.

Body size and risk of prostate cancer in Jamaican men - Maria D. Jackson; Susan P. Walker; Candace M. Simpson; Norma McFarlane-Anderson; Franklyn I. Bennett; Kathleen C. M. Coard; William D. Aiken; Trevor Tulloch; Tomlin J. Paul; Robert L. Wan (Cancer Causes & Control, 2010)

Rescue of Drosophila Melanogaster l(2)35Aa lethality is only mediated by polypeptide GalNAc-transferase pgant35A, but not by the evolutionary conserved human ortholog GalNAc-transferase-T11 - Eric P. Bennett; Ya-Wen Chen; Tilo Schwientek; Ulla Mandel; Katrine ter-Borch Gram Schjoldager; Stephen M. Cohen; Henrik Clausen (Glycoconjugate Journal, 2010)

Behavioral correlations across activity, mating, exploration, aggression, and antipredator contexts in the European house cricket, Acheta domesticus - Alexander D. M. Wilson; Emily M. Whattam; Rachel Bennett; Laksanavadee Visanuvimol; Chris Lauzon; Susan M. Bertram (Behavioral Ecology and Sociobiology, 2010)

Variable Vitellogenin Response of Japanese Medaka (Oryzias latipes) to Weekly Estrogen Exposure - K. Erica Marsh; Gordon Paterson; Christy M. Foran; Erin R. Bennett (Archives of Environmental Contamination and Toxicology, 2010)

The metal ion requirements of Arabidopsis thaliana Glx2-2 for catalytic activity - Pattraranee Limphong; Ross M. McKinney; Nicole E. Adams; Christopher A. Makaroff; Brian Bennett; Michael W. Crowder (JBIC Journal of Biological Inorganic Chemistry, 2010)

Density-dependence of functional development in spiking cortical networks grown in vitro - Michael I. Ham; Vadas Gintautas; Marko A. Rodriguez; Ryan A. Bennett; Cara L. Santa Maria; Luìs M. A. Bettencourt (Biological Cybernetics, 2010)

Ants as indicators for vertebrate fauna at a local scale: an assessment of cross-taxa surrogacy in a disturbed matrix - J. M. Bennett; A. S. Kutt; C. N. Johnson; S. K. A. Robson (Biodiversity and Conservation, 2009)

Validated annual band‐pair periodicity and growth parameters of blue‐spotted maskray Neotrygon kuhlii from south‐east Queensland, Australia - S. J. Pierce; M. B. Bennett (Journal of Fish Biology, 2009)
Age and growth parameters were derived for blue‐spotted maskray Neotrygon kuhlii from Moreton Bay in subtropical eastern Australia. Maximum age estimates of 13 and 10 years were obtained from female ( n = 76) and male ( n = 44) N. kuhlii , respectively. Estimated ages at maturity for 50% of females and males were 6·32 and 3·95 years, respectively. A three‐parameter power function provided the best statistical fit to size at age data in both sexes, providing parameter estimates of y 0 = 163·13, a = 58·52 and b = 0·58 for females and y 0 = 165·13, a = 59·02 and b = 0·54 in males. The two‐parameter von Bertalanffy growth function was used to estimate biological parameters based on disc width ( W D ) for both female ( W D∞ = 465·81 mm, K = 0·13 year −1 , b = 0·63) and male N. kuhlii ( W D∞ = 385·19 mm, K = 0·20 year −1 , b = 0·54). Annual band‐pair deposition was observed in three calcein‐injected N. kuhlii after periods of liberty ranging from 631 to 1081 days. Centrum edge analysis indicated that annual band‐pair formation was generally consistent within this population, with translucent bands formed over spring and summer and opaque bands formed in autumn and winter. Individual growth rates obtained from tagged specimens were similar to power function growth predictions. These results support previous characterizations of this common trawl by‐catch species as comparatively resilient to non‐targeted catches, although higher catch rates outside Australia infer a need for cautious management.

Diet and reproduction in the Australian butterfly ray Gymnura australis from northern and north‐eastern Australia - I. P. Jacobsen; J. W. Johnson; M. B. Bennett (Journal of Fish Biology, 2009)
The diet of Gymnura australis was dominated by teleosts (99·8% index of relative importance). A wide‐ranging species, females matured at 446 mm disc width ( W D ), had a single functional ovary and two functional uteri. Males matured at 377 mm W D and had a single functional testis.

Mitochondrial DNA divergence in the critically imperilled pygmy madtom, Noturus stanauli (Siluriformes: Ictaluridae) - M. G. Bennett; J. Heath Howell; B. R. Kuhajda; R. M. Wood (Journal of Fish Biology, 2009)
The mitochondrial cytochrome b gene was sequenced for six individuals of the pygmy madtom, Noturus stanauli , a globally imperilled catfish, from both known localities in Tennessee (U.S.A.) separated by over 1055 river km. Phylogenetic and population genetic analyses revealed little divergence between these populations for this locus.

Understanding relationships among multiple ecosystem services - Elena M. Bennett; Garry D. Peterson; Line J. Gordon (Ecology Letters, 2009)
Ecology Letters (2009) 12: 1394–1404 Abstract Ecosystem management that attempts to maximize the production of one ecosystem service often results in substantial declines in the provision of other ecosystem services. For this reason, recent studies have called for increased attention to development of a theoretical understanding behind the relationships among ecosystem services. Here, we review the literature on ecosystem services and propose a typology of relationships between ecosystem services based on the role of drivers and the interactions between services. We use this typology to develop three propositions to help drive ecological science towards a better understanding of the relationships among multiple ecosystem services. Research which aims to understand the relationships among multiple ecosystem services and the mechanisms behind these relationships will improve our ability to sustainably manage landscapes to provide multiple ecosystem services.

The role of surface energy and water wettability in aminoalkyl/fluorocarbon/hydrocarbon-modified xerogel surfaces in the control of marine biofouling - Stephanie M. Bennett; John A. Finlay; Nikhil Gunari; David D. Wells; Anne E. Meyer; Gilbert C. Walker; Maureen E. Callow; James A. Callow; Frank V. Bright; Michael R. Detty (Biofouling, 2009)

Molecular evolution of a Drosophila homolog of human BRCA2 - Sarah M. Bennett; Mohamed A. F. Noor (Genetica, 2009)

Likely Population-Level Effects of Contaminants on a Resident Estuarine Fish Species: Comparing Gillichthys mirabilis Population Static Measurements and Vital Rates in San Francisco and Tomales Bays - Catherine R. McGourty; James A. Hobbs; William A. Bennett; Peter G. Green; Hyun-Min Hwang; Naoaki Ikemiyagi; Levi Lewis; Jason M. Cope (Estuaries and Coasts, 2009)

Composition and location of simulated lake‐shore redds influence incubation success in kokanee, Oncorhynchus nerka - M. J. FINCEL; S. R. CHIPPS; D. H. BENNETT (Fisheries Management and Ecology, 2009)
Methods for improving spawning habitat for lakeshore spawning kokanee, Oncorhynchus nerka (Walbaum), were explored by quantifying incubation success of embryos exposed to three substrate treatments in Lake Pend Oreille, Idaho, USA. Substrate treatments included no modification that used existing gravels in the lake (EXISTING), a cleaned substrate treatment where existing gravels were sifted in the water column to remove silt (CLEANED) and the addition of new, silt‐free gravel (ADDED). Incubation success was evaluated using Whitlock–Vibert incubation boxes buried within each substrate treatment that contained recently fertilised embryos. Upon retrieval, live and dead sac fry and eyed eggs were enumerated to determine incubation success (sac fry and eyed eggs × 100/number of fertilised embryos). Incubation success varied significantly among locations and redd treatments. In general, incubation success among ADDED redds (0.0–13.0%) was significantly lower than that for EXISTING (1.4–61.0%) and CLEANED (0.4–62.5%) redds. Adding new gravel to spawning areas changed the morphometry of the gravel‐water interface and probably exposed embryos to disturbance from wave action and reduced embryo survival. Moreover, efforts to improve spawning habitat for lakeshore spawning kokanee should consider water depth and location (e.g. protected shorelines) as important variables. Adding clean gravel to existing spawning areas may provide little benefit if water depth or lake‐bottom morphometry are altered.

South Australian rainfall variability and climate extremes - Alexander D. Evans; John M. Bennett; Caecilia M. Ewenz (Climate Dynamics, 2009)

Arbuscular mycorrhizal fungal species suppress inducible plant responses and alter defensive strategies following herbivory - Alison Elizabeth Bennett; James D. Bever; M. Deane Bowers (Oecologia, 2009)

Phosphorus Accumulation in Saint Lawrence River Watershed Soils: A Century-Long Perspective - Graham K. MacDonald; Elena M. Bennett (Ecosystems, 2009)

Does productivity drive diversity or vice versa? A test of the multivariate productivity–diversity hypothesis in streams - Bradley J. Cardinale; Danuta M. Bennett; Craig E. Nelson; Kevin Gross (Ecology, 2009)
The idea that productivity regulates species diversity is deeply ingrained in the field of ecology. Yet, over the past few decades, an increasing number of experiments have shown that species diversity controls, rather than simply responds to, biomass production. These contrasting perspectives have led to a seeming paradox: Is diversity the cause or the consequence of biological production? Here we present empirical evidence for the multivariate productivity–diversity (MPD) hypothesis, which argues that differing perspectives on productivity–diversity relationships can be resolved by recognizing that historical research has focused on how resource supply regulates both the productivity and richness of local competitors, whereas more recent studies have focused on how the richness of a colonist pool regulates the efficiency by which resources are captured and converted into new tissue. The MPD hypothesis predicts that three pathways operate concurrently to generate productivity–diversity relationships in nature: (1) resource supply directly limits the standing biomass and/or rate of new production by primary producers, (2) producer biomass is directly influenced by the richness of species that locally compete for resources, and (3) resource supply rate indirectly affects producer biomass by influencing the fraction of species from a colonist pool that locally coexist. To examine whether this set of pathways explains covariation between productivity and diversity in natural streams, we used nutrient‐diffusing agar “patches” to manipulate resource supply rates in 20 streams throughout the Sierra Nevada mountain range, California, USA. We then measured the fraction of periphyton species from the stream colonist pool co‐occurring on each nutrient patch, as well as the standing biomass and rates of primary production. Natural patterns of covariation agreed with predictions of the MPD hypothesis. Algal biomass was an increasing function of nutrient supply, and an increasing function of local richness. The fraction of species from the colonist pool found co‐occurring on a patch was a concave‐down function of nutrient supply, causing nutrients to indirectly affect biomass via control over local richness. These results suggest that the MPD hypothesis is a viable explanation of patterns of diversity and productivity in natural stream ecosystems, and that it has potential to merge the historical view that productivity drives diversity with a parallel view that diversity drives productivity.

Reproduction of the blue‐spotted maskray Neotrygon kuhlii (Myliobatoidei: Dasyatidae) in south‐east Queensland, Australia - S. J. Pierce; S. A. Pardo; M. B. Bennett (Journal of Fish Biology, 2009)
This study examined the reproduction and population structure of the blue‐spotted maskray Neotrygon kuhlii within Moreton Bay, a subtropical embayment in south‐east Queensland, Australia. Mean sizes at maturity were 314 mm disc width ( W D ) in females ( n = 140, 115–465 mm W D ) and 294 mm W D in males ( n = 123, 129–381 mm W D ). Female N. kuhlii had a synchronous annual reproductive cycle, with one litter of one to three pups (mean ± s.d . 1·67 ± 0·71) produced per year. Mating behaviours were observed in October and November, and ovulation occurred early in the Austral summer, overlapping with the start of embryonic development. Gestation took c. 4 months with parturition occurring in late February and March. Size at birth was 115–170 mm W D . The population showed a significant female bias, particularly in larger size classes. Tagging studies produced a total recapture rate of 16·1% and indicated that N. kuhlii were site resident for up to 1081 days.

Global biogeography and ecology of body size in birds - Valérie A. Olson; Richard G. Davies; C. David L. Orme; Gavin H. Thomas; Shai Meiri; Tim M. Blackburn; Kevin J. Gaston; Ian P. F. Owens; Peter M. Bennett (Ecology Letters, 2009)
In 1847, Karl Bergmann proposed that temperature gradients are the key to understanding geographic variation in the body sizes of warm‐blooded animals. Yet both the geographic patterns of body‐size variation and their underlying mechanisms remain controversial. Here, we conduct the first assemblage‐level global examination of ‘Bergmann’s rule’ within an entire animal class. We generate global maps of avian body size and demonstrate a general pattern of larger body sizes at high latitudes, conforming to Bergmann’s rule. We also show, however, that median body size within assemblages is systematically large on islands and small in species‐rich areas. Similarly, while spatial models show that temperature is the single strongest environmental correlate of body size, there are secondary correlations with resource availability and a strong pattern of decreasing body size with increasing species richness. Finally, our results suggest that geographic patterns of body size are caused both by adaptation within lineages, as invoked by Bergmann, and by taxonomic turnover among lineages. Taken together, these results indicate that while Bergmann’s prediction based on physiological scaling is remarkably accurate, it is far from the full picture. Global patterns of body size in avian assemblages are driven by interactions between the physiological demands of the environment, resource availability, species richness and taxonomic turnover among lineages.

Antifouling character of ‘active’ hybrid xerogel coatings with sequestered catalysts for the activation of hydrogen peroxide - Danielle M. McMaster; Stephanie M. Bennett; Ying Tang; John A. Finlay; Gregory L. Kowalke; Brian Nedved; Frank V. Bright; Maureen E. Callow; James A. Callow; Dean E. Wendt; Michael G. Hadfield; Michael R. Detty (Biofouling, 2009)

The dapE-encoded N-succinyl-l,l-diaminopimelic acid desuccinylase from Haemophilus influenzae contains two active-site histidine residues - Danuta M. Gillner; David L. Bienvenue; Boguslaw P. Nocek; Andrzej Joachimiak; Vincentos Zachary; Brian Bennett; Richard C. Holz (JBIC Journal of Biological Inorganic Chemistry, 2009)

Spread of an introduced vector‐borne banana virus in Hawaii - RODRIGO P.P. ALMEIDA; GORDON M. BENNETT; MANDY D. ANHALT; CHI‐WEI TSAI; PATRICK O’GRADY (Molecular Ecology, 2009)
Emerging diseases are increasing in incidence; therefore, understanding how pathogens are introduced into new regions and cause epidemics is of importance for the development of strategies that may hinder their spread. We used molecular data to study how a vector‐borne banana virus, Banana bunchy top virus (BBTV), spread in Hawaii after it was first detected in 1989. Our analyses suggest that BBTV was introduced once into Hawaii, on the island of Oahu. All other islands were infected with isolates originating from Oahu, suggesting that movement of contaminated plant material was the main driving factor responsible for interisland spread of BBTV. The rate of mutation inferred by the phylogenetic analysis (1.4 × 10 −4 bp/year) was similar to that obtained in an experimental evolution study under greenhouse conditions (3.9 × 10 −4 bp/year). We used these values to estimate the number of infections occurring under field conditions per year. Our results suggest that strict and enforced regulations limiting the movement of banana plant material among Hawaiian islands could have reduced interisland spread of this pathogen.

Interspecific cross of Brassica oleracea var. alboglabra and B. napus: effects of growth condition and silique age on the efficiency of hybrid production, and inheritance of erucic acid in the self-pollinated backcross generation - Rick A. Bennett; Mohan R. Thiagarajah; Jane R. King; M. Habibur Rahman (Euphytica, 2008)

Hibernation and non-shivering thermogenesis in the Hottentot golden mole (Amblysomus hottentottus longiceps) - M. Scantlebury; B. G. Lovegrove; C. R. Jackson; N. C. Bennett; H. Lutermann (Journal of Comparative Physiology B, 2008)

Estimating the Risk of Exceeding Thresholds in Environmental Systems - Elena M. Bennett; Stephen R. Carpenter; Jeffrey A. Cardille (Water, Air, & Soil Pollution, 2008)

Regional variation in the historical components of global avian species richness - Gavin H. Thomas; C. David L. Orme; Richard G. Davies; Valerie A. Olson; Peter M. Bennett; Kevin J. Gaston; Ian P. F. Owens; Tim M. Blackburn (Global Ecology and Biogeography, 2008)
Aim Using a global data base of the distribution of extant bird species, we examine the evidence for spatial variation in the evolutionary origins of contemporary avian diversity. In particular, we assess the possible role of the timing of mountain uplift in promoting diversification in different regions. Location Global. Methods We mapped the distribution of avian richness at four taxonomic levels on an equal‐area 1° grid. We examined the relationships between richness at successive taxonomic levels (e.g. species richness vs. genus richness). We mapped the residuals from linear regressions of these relationships to identify areas that are exceptional in the number of lower taxa relative to the number of higher taxa. We use generalized least squares models to test the influence of elevation range and temperature on lower‐taxon richness relative to higher‐taxon richness. Results Peaks of species richness in the Neotropics were congruent with patterns of generic richness, whilst peaks in Australia and the Himalayas were congruent with patterns of both genus and family richness. Hotspots in the Afrotropics did not reflect higher‐taxon patterns. Regional differences in the relationship between richness at successive taxonomic levels revealed variation in patterns of taxon co‐occurrence. Species and genus co‐occurrence was positively associated with elevational range across much of the world. Taxon occurrence in the Neotropics was associated with a positive interaction between elevational range and temperature. Conclusions These results demonstrate that contemporary patterns of richness show different associations with higher‐taxon richness in different regions, which implies that the timing of historical effects on these contemporary patterns varies across regions. We suggest that this is due to dispersal limitation and phylogenetic constraints on physiological tolerance limits promoting diversification. We speculate that diversification rates respond to long‐term changes in the Earth's topography, and that the role of tropical mountain ranges is implicated as a correlate of contemporary diversity, and a source of diversification across avian evolutionary history.

Cephalopod dietary specialization and ontogenetic partitioning of the Australian weasel shark Hemigaleus australiensis White, Last & Compagno - S. M. Taylor; M. B. Bennett (Journal of Fish Biology, 2008)
The diet and ontogenetic partitioning of the Australian weasel shark Hemigaleus australiensis was examined in Moreton Bay, south‐east Queensland, Australia. The index of relative importance ( I RI ) revealed a highly specialized diet, consisting entirely of cephalopod molluscs (99·6% I RI ) and crustaceans (0·4% I RI ). Benthic octopus (Octopoda) dominated the diet, accounting for 96·7% I RI . A highly significant difference was found between the stomach contents of juvenile and sub‐adult and adult Australian weasel sharks. Dietary specialization increased with ontogeny and fish ≥1000 mm in total length ( L T ) fed almost exclusively on octopus (98% I RI ). A highly significant difference was found between the L T of Australian weasel sharks from coral and sand and seagrass sites. At the coral site 75·4% of fish were mature while at the sand and seagrass site only 16·1% were mature. This spatial segregation may be attributed to shifting energy requirements associated with ontogeny and the relative abundance of large octopus at the coral site. Hemigaleus australiensis resides in an area of high shark diversity and its specialized cephalopod diet may reduce competition for food with other Carcharhiniformes whose prey comprises predominantly teleosts.

Comparing the diet of two sympatric urolophid elasmobranchs ( Trygonoptera testacea Müller & Henle and Urolophus kapalensis Yearsley & Last): evidence of ontogenetic shifts and possible resource partitioning - A. D. Marshall; P. M. Kyne; M. B. Bennett (Journal of Fish Biology, 2008)
The diets of two urolophids, the common stingaree Trygonoptera testacea and the kapala stingaree Urolophus kapalensis were analysed and compared to examine resource partitioning between these two morphologically similar sympatric Australian batoids. The diet of T. testacea was polychaete‐based, while that of U. kapalensis was dominated by crustaceans (mostly carid shrimps and amphipods). Intraspecific dietary compositions were examined amongst size classes within each of the two species to identify ontogenetic shifts in diet. Differences in the dietary compositions of the smaller total‐length classes of T. testacea suggest that their diet shifts as they increase in size, from one dominated by carids to one almost entirely comprising polychaetes. Significant ontogenetic dietary shifts were not identified in U. kapalensis . Although the two species shared eight broad dietary categories, their overall dietary compositions were found to be significantly different. The limited overlap in the dietary compositions of these two sympatric stingarees suggests the possibility of resource partitioning, with interspecific competition being implicated as a possible cue. Possible mechanisms for the partitioning of resources within and between these two species are discussed.

Structure and metal binding properties of ZnuA, a periplasmic zinc transporter from Escherichia coli - Liliya A. Yatsunyk; J. Allen Easton; Lydia R. Kim; Stacy A. Sugarbaker; Brian Bennett; Robert M. Breece; Ivan I. Vorontsov; David L. Tierney; Michael W. Crowder; Amy C. Rosenzweig (JBIC Journal of Biological Inorganic Chemistry, 2008)

Seawater-like trace element signatures (REE + Y) of Eoarchaean chemical sedimentary rocks from southern West Greenland, and their corruption during high-grade metamorphism - C. R. L. Friend; A. P. Nutman; V. C. Bennett; M. D. Norman (Contributions to Mineralogy and Petrology, 2008)

Global diversity of hymenopterans (Hymenoptera; Insecta) in freshwater - Andrew M. R. Bennett (Hydrobiologia, 2008)

Aspects of reproduction and diet of the Australian endemic skate Dipturus polyommata (Ogilby) (Elasmobranchii: Rajidae), by‐catch of a commercial prawn trawl fishery - P. M. Kyne; A. J. Courtney; M. B. Bennett (Journal of Fish Biology, 2008)
The Australian endemic skate Dipturus polyommata collected from by‐catch of a benthic prawn fishery off southern Queensland was examined to provide information on reproduction and diet. Morphological relationships of total length ( L T ) to disc width and L T to mass were estimated. Size at birth was estimated at c. 100–110 mm and size at first feeding at c. 105–110 mm L T . Size at 50% maturity ( L T50 and 95% CI) was 321 (305–332) and 300 (285–306) mm L T for females and males, respectively. Size at first maturity corresponded to 87·7% of observed maximum size in females (366 mm L T ) and 87·5% in males (343 mm L T ). Two females, representing 18·2% of mature females sampled in the austral winter were each carrying two egg cases. Descriptions of egg cases are given. Diet described by the index of relative importance as a percentage (% I RI ) was predominantly crustacean based with carid shrimps (53·64%) and penaeoid prawns (23·30%) the most significant prey groups. Teleosts (11·72%), gammarid amphipods (5·31%) and mysids (4·72%) were also important to the diet of the species, while a further six prey groups made only a minor contribution to diet (1·31%). An ontogenetic change was evident between the diets of immature and mature skates. Immature animals fed more extensively on carids and amphipods and mature animals on penaeoids, teleosts and mysids.

Methods for conducting an economic opportunity survey in smallholder dairy farms - K. V. Nordlund; W. J. Goodger; T. B. Bennett; M. Shamsuddin; R. F. Klos (Tropical Animal Health and Production, 2007)

Evaluating climatic and non-climatic influences on ion chemistry in natural and man-made lakes of Nebraska, USA - D. M. Bennett; S. C. Fritz; J. C. Holz; A. A. Holz; V. A. Zlotnik (Hydrobiologia, 2007)

The role of platelet CD154 in the modulation in adaptive immunity - Daniel L. Sprague; Jennifer M. Sowa; Bennett D. Elzey; Timothy L. Ratliff (Immunologic Research, 2007)

Diazinon Mitigation in Constructed Wetlands: Influence of Vegetation - M. T. Moore; C. M. Cooper; S. Smith; R. F. Cullum; S. S. Knight; M. A. Locke; E. R. Bennett (Water, Air, & Soil Pollution, 2007)

The influence of thermal parameters on the acclimation responses of pinfish Lagodon rhomboides exposed to static and decreasing low temperatures - C. M. Reber; W. A. Bennett (Journal of Fish Biology, 2007)
Pinfish Lagodon rhomboides acclimation rates were determined by modelling changes in critical thermal minimum ( T crit min , ° C) estimates at set intervals following a temperature decrease of 3–4° C. The results showed that pinfish gained a total of 3·7° C of cold tolerance over a range of acclimation temperatures ( T acc , ° C) from (23–12° C), that cold tolerance increased with exposure time to the reduced temperature at all T acc , but that the rate of cold tolerance accruement (mean 0·14° C day −1 ) was independent of T acc . A highly significant ( P 10 T crit min = 0·41597 − 0·01704 T acc + 0·04320 T plunge − 0·08376[log 10 ( t + 1)], where T plunge is plunge temperature (° C) and t is the time (days). A comparison of the present data, with acclimation rate data for other species, suggests that factors such as latitude or geographic range may play a more important role than ambient temperature in determining cold acclimation rates in fishes.

Continuous measurement of oxygen tensions in the air-breathing organ of Pacific tarpon (Megalops cyprinoides) in relation to aquatic hypoxia and exercise - Roger S. Seymour; Anthony P. Farrell; Keith Christian; Timothy D. Clark; Michael B. Bennett; Rufus M. G. Wells; John Baldwin (Journal of Comparative Physiology B, 2007)

In situ detection of novel Acidobacteria in microbial mats from a chemolithoautotrophically based cave ecosystem (Lower Kane Cave, WY, USA) - Daniela B. Meisinger; Johannes Zimmermann; Wolfgang Ludwig; Karl‐Heinz Schleifer; Gerhard Wanner; Michael Schmid; Philip C. Bennett; Annette S. Engel; Natuschka M. Lee (Environmental Microbiology, 2007)
Summary Lower Kane Cave, Wyoming (USA), has hydrogen sulfide‐bearing springs that discharge into the cave passage. The springs and cave stream harbour white filamentous microbial mats dominated by Epsilonproteobacteria . Recently, novel 16S rRNA gene sequences from the phylum Acidobacteria , subgroup 7, were found in these cave mats. Although Acidobacteria are ubiquitously distributed in many terrestrial and marine habitats, little is known about their ecophysiology. To investigate this group in Lower Kane Cave in more detail, a full‐cycle rRNA approach was applied based on 16S and 23S rRNA gene clone libraries and the application of novel probes for fluorescence in situ hybridization . The 16S and 23S rRNA gene clone libraries yielded seven and six novel acidobacterial operational taxonomic units (OTUs) respectively. The majority of the OTUs were affiliated with subgroups 7 and 8. One OTU was affiliated with subgroup 6, and one OTU could not be assigned to any of the present acidobacterial subgroups. Fluorescence in situ hybridization distinguished two morphologically distinct, rod‐shaped cells of the acidobacterial subgroups 7 and 8. Although the ecophysiology of Acidobacteria from Lower Kane Cave will not be fully resolved until cultures are obtained, acidobacterial cells were always associated with the potentially chemolithoautotrophic epsilon‐ or gammaproteobacterial filaments, suggesting perhaps a lifestyle based on heterotrophy or chemoorganotrophy.

Hunting for Consensus: Reconciling Bushmeat Harvest, Conservation, and Development Policy in West and Central Africa - ELIZABETH L. BENNETT; ERIC BLENCOWE; KATRINA BRANDON; DAVID BROWN; ROBERT W. BURN; GUY COWLISHAW; GLYN DAVIES; HOLLY DUBLIN; JULIA E. FA; E. J. MILNER‐GULLAND; JOHN G. ROBINSON; J. MARCUS ROWCLIFFE; et al. (Conservation Biology, 2007)

Altered gill morphology in benthic macroinvertebrates from mercury enriched streams in the Neversink Reservoir Watershed, New York - Kathleen M. Skinner; Jessica D. Bennett (Ecotoxicology, 2007)

Size matters: genital allometry in an African mole-rat (Family: Bathyergidae) - A. A. Kinahan; N. C. Bennett; M. J. O’Riain; L. Hart; P. W. Bateman (Evolutionary Ecology, 2007)

Contaminants in tilapia (Oreochromis mossambicus) from the Salton Sea, California, in relation to human health, piscivorous birds and fish meal production - Marie F. Moreau; Janie Surico-Bennett; Marie Vicario-Fisher; David Crane; Russel Gerads; Richard M. Gersberg; Stuart H. Hurlbert (Hydrobiologia, 2007)

Microporated PEG Spheres for Fluorescent Analyte Detection - Rebecca M. Rounds; Bennett L. Ibey; Hope T. Beier; Michael V. Pishko; Gerard L. Coté (Journal of Fluorescence, 2006)

Energy, range dynamics and global species richness patterns: reconciling mid‐domain effects and environmental determinants of avian diversity - David Storch; Richard G. Davies; Samuel Zajíček; C. David L. Orme; Valerie Olson; Gavin H. Thomas; Tzung‐Su Ding; Pamela C. Rasmussen; Robert S. Ridgely; Peter M. Bennett; Tim M. Blackburn; Ian P. F. Owens; et al. (Ecology Letters, 2006)
Spatial patterns of species richness follow climatic and environmental variation, but could reflect random dynamics of species ranges (the mid‐domain effect, MDE). Using data on the global distribution of birds, we compared predictions based on energy availability (actual evapotranspiration, AET, the best single correlate of avian richness) with those of range dynamics models. MDE operating within the global terrestrial area provides a poor prediction of richness variation, but if it operates separately within traditional biogeographic realms, it explains more global variation in richness than AET. The best predictions, however, are given by a model of global range dynamics modulated by AET, such that the probability of a range spreading into an area is proportional to its AET. This model also accurately predicts the latitudinal variation in species richness and variation of species richness both within and between realms, thus representing a compelling mechanism for the major trends in global biodiversity.

The Arabidopsis thaliana/Myzus persicae model system demonstrates that a single gene can influence the interaction between a plant and a sap‐feeding insect - E. J. HUNT; J. PRITCHARD; M. J. BENNETT; X. ZHU; D. A. BARRETT; T. ALLEN; JS BALE; H. J. NEWBURY (Molecular Ecology, 2006)
We have developed an Arabidopsis thaliana / Myzus persicae model system to allow the dissection of plant/insect interactions at a molecular genetic level. This allows the examination of the role of single plant genes in the interaction between the plant and an aphid. Our initial studies have exploited an Arabidopsis genotype in which the function of the amino acid transporter ANT1 has been abolished. This mutation results in a change in the proportions of several amino acids within the phloem sieve elements (SEs) resulting in an increase in the proportion of essential amino acids. This has been measured using aphid stylectomy to collect SE samples, followed by a novel micellar electrokinetic chromatography method for amino acid analysis. The SE content represents the aphid's diet, and use of electrical penetration graph technology and honeydew clocks have demonstrated that this altered diet results in a change in the feeding rate of the aphid. Balance sheets can be produced to show the amount (nmoles/24 h) of each of 18 amino acids taken up and excreted by aphids feeding on wild type and ant1 mutant plants. The data show that aphids feeding on the ant1 mutant take up larger amounts of amino acids. However, we could not detect any effect on the reproductive rate of the aphids. The results show that, under experimental conditions, this model system can be used to identify plant genes that control the behaviour and fecundity of an insect pest.

Complex evolution of X and Y autosomal translocations in the giant mole-rat, Cryptomys mechowi (Bathyergidae) - J. L. Deuve; N. C. Bennett; P. C. M. O’Brien; M. A. Ferguson-Smith; C. G. Faulkes; J. Britton-Davidian; T. J. Robinson (Chromosome Research, 2006)

Effect of clinical trial publicity on HRT prescribing in Ireland - C. Usher; M. Teeling; K. Bennett; J. Feely (European Journal of Clinical Pharmacology, 2006)

Kinetic and spectroscopic characterization of the E134A- and E134D-altered dapE-encoded N-succinyl-l,l-diaminopimelic acid desuccinylase from Haemophilus influenzae - Ryan Davis; David Bienvenue; Sabina I. Swierczek; Danuta M. Gilner; Lakshman Rajagopal; Brian Bennett; Richard C. Holz (JBIC Journal of Biological Inorganic Chemistry, 2006)

A survey to identify economic opportunities for smallholder dairy farms in Bangladesh - M. Shamsuddin; W. J. Goodger; M. S. Hossein; Azizunnesa; T. Bennett; K. Nordlund (Tropical Animal Health and Production, 2006)

Expression profiling identifies novel candidate genes for ethanol sensitivity QTLs - Erik J. MacLaren; Beth Bennett; Thomas E. Johnson; James M. Sikela (Mammalian Genome, 2006)

Distribution of an asymmetrical copepod, Hatschekia plectropomi , on the gills of Plectropomus leopardus - T. B. Scott–Holland; S. M. Bennett; M. B. Bennett (Journal of Fish Biology, 2006)
Hatschekia plectropomi , an ectoparasitic copepod found on the gills, infected Plectropomus leopardus from Heron Island Reef with 100% prevalence ( n = 32) and a mean ± s . e . infection intensity of 131·9 ± 22·1. The distribution of 4222 adult female parasites across 32 individual host fish was investigated at several organizational levels ranging from the level of holobranch pairs to that of individual filaments. Parasites demonstrated a site preference for the two central holobranchs (2 and 3). Along the lengths of hemibranchs, filaments near the dorsal and ventral ends and those in the proximity of the bend region were rarely occupied. The probability of coming into contact with a suitable attachment site and the ability to withstand ventilation forces at that site were proposed as the major factors affecting distribution. Two H. plectropomi morphotypes were identified based on the direction of body curvature. Regardless of morphotype, 99·9% of individuals were attached such that the convex side of the body was oriented towards the oncoming ventilating water currents. Further, 93·3% of individuals attached to the posterior faces of filaments, leading to a predictable pattern of attachment for this species. It is suggested that the direction of body curvature develops in response to the direction of the ventilating water currents.

Tissue-Specific Expression and Drought Responsiveness of Cell-Wall Invertase Genes of Rice at Flowering - X. M. Ji; M. Raveendran; R. Oane; A. Ismail; R. Lafitte; R. Bruskiewich; S. H. Cheng; J. Bennett (Plant Molecular Biology, 2005)

A Systems Model Approach to Determining Resilience Surrogates for Case Studies - E. M. Bennett; G. S. Cumming; G. D. Peterson (Ecosystems, 2005)

QTL analysis of fruit antioxidants in tomato using Lycopersicon pennellii introgression lines - M. Cecilia Rousseaux; Carl M. Jones; Dawn Adams; Roger Chetelat; Alan Bennett; Ann Powell (Theoretical and Applied Genetics, 2005)

Case Study Part 2: Probabilistic Modelling of Long-term Effects of Pesticides on Individual Breeding Success in Birds and Mammals - W. ROELOFS; D.R. CROCKER; R.F. SHORE; D.R.J. MOORE; G.C. SMITH; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; et al. (Ecotoxicology, 2005)

Case Study Part 1: How to Calculate Appropriate Deterministic Long-Term Toxicity to Exposure Ratios (TERs) for Birds and Mammals - R.F. SHORE; D.R. CROCKER; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; A. FAIRBROTHER; S. FERSON; D. FISCHER; et al. (Ecotoxicology, 2005)

Effect of Combined Treatment of Pasteurisation and Coniothyrium minitans on Sclerotia of Sclerotinia sclerotiorum in Soil - Amanda J. Bennett; Carlo Leifert; John M. Whipps (European Journal of Plant Pathology, 2005)

Ancient DNA from pollen: a genetic record of population history in Scots pine - L. PARDUCCI; Y. SUYAMA; M. LASCOUX; K. D. BENNETT (Molecular Ecology, 2005)
Assessments of plant population dynamics in space and time have depended on dated records of fossil pollen synthesized on a subcontinental scale. Genetic analyses of extant populations have revealed spatial relationships that are indicative of past spatial dynamics, but lack an explicit timescale. Synthesis of these data requires genetic analyses from abundant dated fossil material, and this has hitherto been lacking. Fossil pollen is the most abundant material with which to fill this data gap. Here we report genetic analyses of fossil pollen retrieved from Holtjärnen postglacial lake sediment in Sweden and show that plastid DNA is recoverable from Scots Pine and Norway spruce pollen grains that are 100 and 10 000 years old. By sequencing clones from two short plastid PCR products and by using multiple controls we show that the ancient sequences were endogenous to the fossil grains. Comparison of ancient sequences and those obtained from an extant population of Scots pine establishes the first genetic link between extant and fossil samples in this species, providing genetic continuity through time. The finding of one common haplotype present in modern, 100‐year old and 10 000‐year old samples suggests that it may have persisted near Holtjärnen throughout the postglacial period. This retrieval of ancient DNA from pollen has major implications for plant palaeoecology in conifer species by allowing direct estimates of population dynamics in space and time.

Comparative pathologic changes in broiler chicks on feed amendedwith Fusarium proliferatum culture material or purified fumonisinB1 and moniliformin* - T. Javed; R. M. Bunte; M. A. Dombrink-Kurtzman; J. L. Richard; G. A. Bennett; L. M. Côté; W. B Buck (Mycopathologia, 2005)

Are Existing Global Scenarios Consistent with Ecological Feedbacks? - Graeme S. Cumming; Joseph Alcamo; Osvaldo Sala; Robert Swart; Elena M. Bennett; Monika Zurek (Ecosystems, 2005)

Looking to the Future of Ecosystem Services - E. M. Bennett; G. D. Peterson; E. A. Levitt (Ecosystems, 2005)

Characterization of the active site and insight into the binding mode of the anti-angiogenesis agent fumagillin to the manganese(II)-loaded methionyl aminopeptidase from Escherichia coli - Ventris M. D’souza; Robert S. Brown; Brian Bennett; Richard C. Holz (JBIC Journal of Biological Inorganic Chemistry, 2005)

Identification of flanking SSR markers for a major rice gall midge resistance gene Gm1 and their validation - S. K. Biradar; R. M. Sundaram; T. Thirumurugan; J. S. Bentur; S. Amudhan; V. V. Shenoy; B. Mishra; J. Bennett; N. P. Sarma (Theoretical and Applied Genetics, 2004)

Jean Hanson – a woman to emulate: leading research into the molecular basis of contractility in muscle - Pauline M. Bennett (Journal of Muscle Research and Cell Motility, 2004)

Colony structure and parentage in wild colonies of co‐operatively breeding Damaraland mole‐rats suggest incest avoidance alone may not maintain reproductive skew - TAMSIN M. BURLAND; NIGEL C. BENNETT; JENNIFER U. M. JARVIS; CHRISTOPHER G. FAULKES (Molecular Ecology, 2004)
Colonies of co‐operatively breeding African mole‐rats have traditionally been thought to be composed of a single breeding female, one or two breeding males, and their offspring. In the naked mole‐rat ( Heterocephalus glaber ), the occurrence of facultative inbreeding means incest avoidance cannot prevent reproduction in subordinate group members, and physiological suppression of reproductive function by the breeding female occurs in both sexes. In contrast, previous studies of captive colonies of the Damaraland mole‐rat ( Cryptomys damarensis ) suggest that breeding within a colony is restricted to a single breeding pair, simply because all other colony members are highly related (first‐ or second‐order relatives) and this species is an obligate outbreeder. Using microsatellite markers, we investigated parentage and colony composition in 18 wild Damaraland mole‐rat colonies to determine whether inbreeding avoidance alone can explain the high levels of reproductive skew in this species. Multiple and unidentified paternity was widespread within colonies and immigrants of both sexes were regularly identified. Unrelated, opposite‐sex nonbreeders were found coexisting in two colonies. These results suggest that, in the wild, conditions exist where nonreproductive females can come into contact with unrelated males, even when they do not disperse from their natal colony. Inbreeding avoidance alone is therefore insufficient to maintain the high levels of reproductive skew identified in this species suggesting that the breeding female somehow suppresses the reproductive function in nonbreeding females.

Molecular insight into patterns of colony composition and paternity in the common mole‐rat Cryptomys hottentotus hottentotus - J. M. Bishop; J. U. M. Jarvis; A. C. Spinks; N. C. Bennett; C. O'Ryan (Molecular Ecology, 2004)
We report the discovery of intraspecific variation in both colony composition and patterns of paternity in two populations of the social common mole‐rat Cryptomys hottentotus hottentotus . These two populations represent the mesic and arid habitat extremes of the species’ broad ecological range in South Africa. Until recently colonies of the common mole‐rat were thought to consist of familial groups whereby all colony members were the offspring of a monogamous reproductive pair. The remaining colony members were thought to forego reproduction until both social and ecological conditions favoured dispersal and opportunities for independent outbreeding. Results from genetic assignment tests using microsatellite markers indicate that while colony composition is dominated by familial groups, colonies within both populations included both adult and subadult foreign conspecifics. Analysis of parentage reveals that the social organization of C. h. hottentotus is not that of strict monogamy; paternity of offspring was not assigned consistently to the largest, most dominant male within the colony. Moreover, a number of significantly smaller males were found to sire offspring, suggesting a sneak‐mating strategy by subordinate within‐colony males. Extra‐colony extra‐pair paternity (ECP) was also found to characterize C. h. hottentotus colonies, occurring with similar frequencies in both habitats. Both dominant established breeding males and subordinate males were identified as siring young in nonsource colonies. Furthermore, established breeding males were found to sire extra‐colony young in the same season as siring young within their source colonies. We discuss the significance of these results within the context of the divergent ecological regimes characterizing the two sites and observe that our results revisit the accuracy of using behavioural and morphological characters, which have structured the basis of our understanding of the behavioural ecology of this species, as indicators of breeding status in mark–recapture studies.

Not Just a Plasma Membrane Protein: in Cardiac Muscle Cells Alpha-II Spectrin also Shows a Close Association with Myofibrils - Pauline M. Bennett; Anthony J. Baines; Marie-Christine Lecomte; Alison M. Maggs; Jennifer C. Pinder (Journal of Muscle Research and Cell Motility, 2004)

Voltage-gated Na + channels confer invasive properties on human prostate cancer cells - Eric S. Bennett; Beth A. Smith; Jean M. Harper (Pflügers Archiv - European Journal of Physiology, 2004)

Phylogeographical patterns of genetic divergence and speciation in African mole‐rats (Family: Bathyergidae) - C. G. Faulkes; E. Verheyen; W. Verheyen; J. U. M. Jarvis; N. C. Bennett (Molecular Ecology, 2004)
African mole‐rats are subterranean Hystricomorph rodents, distributed widely throughout sub‐Saharan Africa, and displaying a range of social and reproductive strategies from solitary dwelling to the ‘insect‐like’ sociality of the naked mole‐rat, Heterocephalus glaber . Both molecular systematic studies of Rodentia and the fossil record of bathyergids indicate an ancient origin for the family. This study uses an extensive molecular phylogeny and mitochondrial cytochrome b and 12s rRNA molecular clocks to examine in detail the divergence times, and patterns of speciation of the five extant genera in the context of rift valley formation in Africa. Based on a value of 40–48 million years ago (Myr) for the basal divergence of the family ( Heterocephalus ), we estimate divergence times of 32–40 Myr for Heliophobius , 20–26 Myr for Georychus / Bathyergus and 12–17 Myr for Cryptomys , the most speciose genus. While early divergences may have been independent of rifting, patterns of distribution of later lineages may have been influenced directly by physical barriers imposed by the formation of the Kenya and Western Rift, and indirectly by accompanying climatic and vegetative changes. Rates of chromosomal evolution and speciation appear to vary markedly within the family. In particular, the genus Cryptomys appears to have undergone an extensive radiation and shows the widest geographical distribution. Of the two distinct clades within this genus, one exhibits considerable karyotypic variation while the other does not, despite comparatively high levels of sequence divergence between some taxa. These different patterns of speciation observed both within the family and within the genus Cryptomys may have been a result of environmental changes associated with rifting.

Thermal tolerance and metabolic physiology among redband trout populations in south‐eastern Oregon - K. J. Rodnick; A. K. Gamperl; K. R. Lizars; M. T. Bennett; R. N. Rausch; E. R. Keeley (Journal of Fish Biology, 2004)
Streamside measurements of critical thermal maxima ( T crit ), swimming performance ( U crit ), and routine ( R r ) and maximum ( R max ) metabolic rates were performed on three populations of genetically distinct redband trout Oncorhynchus mykiss in the high‐desert region of south‐eastern Oregon. The T crit values (29·4 ± 0·1° C) for small (40–140 g) redband trout from the three streams, and large (400–1400 g) redband trout at Bridge Creek were not different, and were comparable to published values for other salmonids. At high water temperatures (24–28° C), large fish incurred higher metabolic costs and were more thermally sensitive than small fish. U crit (3·6 ± 0·1 L F s −1 ), R r (200 ± 13 mg O 2 kg −0·830 h −1 ) and metabolic power (533 ± 22 mg O 2 kg −0·882 h −1 ) were not significantly different between populations of small redband trout at 24° C. R max and metabolic power, however, were higher than previous measurements for rainbow trout at these temperatures. Fish from Bridge Creek had a 30% lower minimum total cost of transport ( C min ), exhibited a lower refusal rate, and had smaller hearts than fish at 12‐mile or Rock Creeks. In contrast, no differences in U crit or metabolism were observed between the two size classes of redband trout, although C min was significantly lower for large fish at all swimming speeds. Biochemical analyses revealed that fish from 12‐mile Creek, which had the highest refusal rate (36%), were moderately hyperkalemic and had substantially lower circulating levels of free fatty acids, triglycerides and albumin. Aerobic and anaerobic enzyme activities in axial white muscle, however, were not different between populations, and morphological features were similar. Results of this study: 1) suggest that the physiological mechanisms that determine T crit in salmonids are highly conserved; 2) show that adult (large) redband trout are more susceptible to the negative affects of elevated temperatures than small redband trout; 3) demonstrate that swimming efficiency can vary considerably between redband trout populations; 4) suggest that metabolic energy stores correlate positively with swimming behaviour of redband trout at high water temperatures; 5) question the use of T crit for assessing physiological function and defining thermal habitat requirements of stream‐dwelling salmonids like the redband trout.

Caste differentiation responses of two sympatric Reticulitermes termite species to juvenile hormone homologs and synthetic juvenoids in two laboratory assays - M. E. Scharf; C. R. Ratliff; J. T. Hoteling; B. R. Pittendrigh; G. W. Bennett (Insectes Sociaux, 2003)

Soil Phosphorus Concentrations in Dane County, Wisconsin, USA: An Evaluation of the Urban?Rural Gradient Paradigm - Elena M. Bennett (Environmental Management, 2003)

Constitutive and inducible levels of CYP1A1 and CYP1A2 in rat cerebral cortex and cerebellum - Michael M. Iba; Amijoy Storch; Anima Ghosal; Susan Bennett; Kenneth R. Reuhl; Herbert E. Lowndes (Archives of Toxicology, 2003)

Acute Toxicity of Methyl-Parathion in Wetland Mesocosms: Assessing the Influence of Aquatic Plants Using Laboratory Testing with Hyalella azteca - R. Schulz; M. T. Moore; E. R. Bennett; C. D. Milam; J. L. Bouldin; J. L. Farris; S. Smith; C. M. Cooper (Archives of Environmental Contamination and Toxicology, 2003)

Neuroscience data and tool sharing - Peter Eckersley; Gary F. Egan; Erik De Schutter; Tang Yiyuan; Mirko Novak; Vaclav Sebesta; Line Matthiessen; Irio P. Jaaskelainen; Ulla Ruotsalainen; Andreas V. M. Herz; Klaus-Peter Hoffmann; Raphael Ritz; et al. (Neuroinformatics, 2003)

Human infection by a swine influenza A (H1N1) virus in Switzerland - V. Gregory; M. Bennett; Y. Thomas; L. Kaiser; W. Wunderli; H. Matter; A. Hay; Y. P. Lin (Archives of Virology, 2003)

[3H]-thymidine labelling of DNA triggers apoptosis potentiated by E1A-adenoviral protein - S. N. Orlov; D. V. Pchejetski; S. Der Sarkissian; V. Adarichev; S. Taurin; A. V. Pshezhetsky; J. Tremblay; G. V. Maximov; D. deBlois; M. R. Bennett; P. Hamet (Apoptosis, 2003)

Effect of saline intake on water flux and osmotic homeostasis in Pekin ducks (Anas platyrhynchos) - D. Bennett; D. Gray; M. Hughes (Journal of Comparative Physiology B, 2003)

Effect of saline acclimation on body water and sodium compartmentalization in Pekin ducks (Anas platyrhynchos) - D. Bennett; D. Kojwang; T. Sullivan; D. Gray; M. Hughes (Journal of Comparative Physiology B, 2003)

CCL2 Transgene Expression in the Central Nervous System Directs Diffuse Infiltration of CD45 high CD11b + Monocytes and Enhanced Theiler's Murine Encephalomyelitis Virus–Induced Demyelinating Disease - Jami L Bennett; Adam Elhofy; Mauro C Dal Canto; Mari Tani; Richard M Ransohoff; William J Karpus (Journal of NeuroVirology, 2003)

Comment: Formation and reorientation of structure in the surge‐type glacier Kongsvegen, Svalbard J. Woodward, T. Murray and A. Mc Caig (2002) Journal of Quaternary Science 17 : 201–209 - N. F. Glasser; M. J. Hambrey; M. R. Bennett; D. Huddart (Journal of Quaternary Science, 2003)

Association of bovine neonatal Fc receptor a-chain gene (FCGRT) haplotypes with serum IgG concentration in newborn calves - William W. Laegreid; Michael P. Heaton; James E. Keen; William M. Grosse; Carol G. Chitko-McKown; Timothy P.L. Smith; John W. Keele; Gary L. Bennett; Thomas E. Besser (Mammalian Genome, 2002)

Influence of an extreme high water event on survival, reproduction, and distribution of Snail Kites in Florida, USA - Robert E. Bennetts; Wiley M. Kitchens; Victoria J. Dreitz (Wetlands, 2002)

Simple roost nests confer large energetic savings for sparrow-weavers - Ferguson J.; Nijland M.; Bennett N. (Journal of Comparative Physiology B, 2002)

Basis for Intracellular Retention of a Human Mutant of the Retinal Rod Channel a Subunit - N. Mallouk; M. Ildefonse; F. Pag s; M. Ragno; N. Bennett (The Journal of Membrane Biology, 2002)

Molecular systematics of Solanum section Lycopersicum (Lycopersicon) using the nuclear ITS rDNA region - J. A. Marshall; S. Knapp; M. R. Davey; J. B. Power; E. C. Cocking; M. D. Bennett; A. V. Cox (Theoretical and Applied Genetics, 2001)

Landscape Determinants of Nonindigenous Fish Invasions - Robert M. Ross; William A. Lellis; Randy M. Bennett; Connie S. Johnson (Biological Invasions, 2001)

Gill pathology caused by infestations of adult and preadult Dissonus manteri Kabata (Copepoda: Dissonidae) on coral trout, Plectropomus leopardus (Lacépède), (Serranidae) - S M Bennett; M B Bennett (Journal of Fish Diseases, 2001)
Adult and preadult Dissonus manteri attached to the gills of Plectropomus leopardus cause significant pathology in the form of large hyperplastic nodules on the afferent (leading) edges of gill filaments. Nodules result from the dual actions of parasite attachment and feeding. The host response is characterized by severe epithelial hyperplasia, supplemented by fibroplasia and inflammation. Parasites attach close to the gill arch near the base of filaments. They have little effect on gill vasculature as the maxillipeds penetrate the filament superficial to the efferent filament artery and do not interfere with the blood vessels of the secondary lamellae. Tissue proliferation is limited to the wide portion of filament ‘edge’ epithelium in the proximal third and also does not extend to the secondary lamellae. Nodules are most numerous towards the ends of hemibranchs and are generally absent from the central regions. Leading hemibranchs bear significantly more nodules than their trailing counterparts. Of the total number of nodules, 20.5% are located on the pseudobranchs. Distribution patterns are considered to be primarily the result of D. manteri avoiding strong water currents, although this cannot explain the difference between numbers on leading and trailing hemibranchs.

High-throughput sequence identification of gene coding variants within alcohol-related QTLs - Marissa A. Ehringer; Jessica Thompson; Otakuye Conroy; Yan Xu; Fan Yang; Jennifer Canniff; Mary Beeson; Lena Gordon; Beth Bennett; Thomas E. Johnson; James M. Sikela (Mammalian Genome, 2001)

Comparative mapping of BTA15 and HSA11 including a region containing a QTL for meat tenderness - Caird E. Rexroad III; Gary L. Bennett; Roger T. Stone; John W. Keele; Scott C. Fahrenkrug; Brad A. Freking; Steven M. Kappes; Timothy P.L. Smith (Mammalian Genome, 2001)

Reproductive suppression and inbreeding avoidance in wild populations of co-operatively breeding meerkats ( Suricata suricatta ) - M. J. O'Riain; N. C. Bennett; P. N. M. Brotherton; G. McIlrath; T. H. Clutton-Brock (Behavioral Ecology and Sociobiology, 2000)

Quantifying Biodiversity: a Phenotypic Perspective - Ian P.F. Owens; Peter M. Bennett (Conservation Biology, 2000)
With recently derived algorithms, it is possible to calculate the relative phylogenetic distinctiveness of taxa with respect to patterns of phylogenetic branching. We extended this approach by exploring the relative extent to which taxa represent phenotypic biodiversity. We devised a method, based on the use of independent contrasts, that measures the amount of phenotypic change that occurs when lineages diverge. We use this method to quantify the extent to which a taxon represents the phenotypic diversification that has occurred in the past. We applied our method to an analysis of variation in clutch size across 133 avian families. All families did not contribute equally to representing clutch size diversification. The top 10 avian families in terms of representing clutch size diversification were the mesites ( Mesitornithidae), cranes (Gruidae), bustards (Otidae), new world quail (Odontophoridae), seriemas (Cariamidae), finfoots ( Heliornithidae), swallows ( Hirundinidae), megapodes ( Megapodiae), and guans (Cracidae). The 217 species in these 10 families (2.3% of all bird species, 7.5% of families) represented 19.3% of diversification in clutch size. Seventeen percent of overall clutch size diversification was represented by taxa threatened with extinction. The 10 families that represent the greatest proportion of overall clutch size diversification threatened by extinction were the mesites ( Mesitornithidae), kagu ( Rhynochetidae), cranes (Gruidae), kiwis (Apterygidae), new world quail (Odontophoridae), megapodes ( Megapodiae), cassowaries (Casuariidae), finfoots ( Heliornithidae), guans (Cracidae), and logrunners (Orthonychidae). The 42 threatened species (0.5% of all bird species, 3.8% of all threatened bird species) in these 10 families encompassed 53% of the clutch size diversification whose representation was threatened with extinction. Our results suggest that this type of analysis could potentially help prioritize species‐based conservation efforts by identifying those taxa that contribute most toward representing the evolutionary processes that lead to current phenotypic biodiversity.

Improvement of nutritional site quality 13 years after single application of fertiliser N and P on regenerating cedar-hemlock cutovers on northern Vancouver Island, B.C. - Robert L. Bradley; Brian D. Titus; Caroline M. Preston; Jennifer Bennett (Plant and Soil, 2000)

Comparative map alignment of BTA27 and HSA4 and 8 to identify conserved segments of genome containing fat deposition QTL - Tad S. Sonstegard; Wes M. Garrett; Melissa S. Ashwell; Gary L. Bennett; Steven M. Kappes; Curtis P. Van Tassell (Mammalian Genome, 2000)

Method for the Simultaneous Extraction and Analysis of Two Current Use Pesticides, Atrazine and Lambda-Cyhalothrin, in Sediment and Aquatic Plants - E. R. Bennett; M. T. Moore; C. M. Cooper; S. Smith Jr. (Bulletin of Environmental Contamination and Toxicology, 2000)

Method for the Simultaneous Extraction and Analysis of Two Current Use Pesticides, Atrazine and Lambda-Cyhalothrin, in Sediment and Aquatic Plants - E. R. Bennett; M. T. Moore; C. M. Cooper; S. Smith (Bulletin of Environmental Contamination and Toxicology, 2000)

Molecular cloning of transmembrane and soluble forms of a novel rat natural killer cell receptor related to 2B4 - P. R. Kumaresan; S. E. Stepp; M. Bennett; V. Kumar; P. A. Mathew (Immunogenetics, 2000)

Isolation of RNA and Protein from Guard Cells of Nicotiana glauca - Lawrence B. Smart; Nicole M. Nall; Alan B. Bennett (Plant Molecular Biology Reporter, 1999)

Discordant patterns of morphological and molecular change in broadtail madtoms (genus Noturus ) - R. Q. Bennetts; J. M. Grady; F. C. Rohde; J. M. Quattro (Molecular Ecology, 1999)
Two morphologically distinct forms of an undescribed madtom catfish ( Noturus sp.) occur in the rivers and lakes of southeastern USA. ‘Lake’ broadtail madtoms are endemic to Lake Waccamaw and are probably related to nearby ‘river’ broadtail populations. To investigate phylogenetic relationships, we surveyed mitochondrial DNA (mtDNA) sequence variation in ‘lake’ and ‘river’ broadtails and other members of the genus Noturus . Mitochondrial rDNA data suggest a sister group relationship between broadtail madtoms and N. insignis , not N. leptacanthus as posited previously. Population‐level analyses using additional mtDNA characters (NADH dehydrogenase subunit 2 (ND2) and cytochrome b (Cyt b )) identified two highly divergent genetic lineages within broadtail madtoms that do not correspond to the morphological designations ‘river’ and ‘lake’.

Interactive effects of subanesthetic ketamine and haloperidol in healthy humans - John H. Krystal; D. Cyril D'Souza; Laurence P. Karper; Alexandre Bennett; Anissa Abi-Dargham; Danielle Abi-Saab; Karyn Cassello; M. B. Bowers Jr.; Sally Vegso; George R. Heninger; Dennis S. Charney; M. B. Bowers (Psychopharmacology, 1999)

Self-administration of cocaine analogs by rats - D. C. S. Roberts; Rachel Phelan; L. Mark Hodges; Melinda M. Hodges; Barbara Bennett; Steve Childers; Huw Davies (Psychopharmacology, 1999)

Skeletal deformities in elasmobranchs from Australian waters - M. R. Heupel; C. A. Simpfendorfer; M. B. Bennett (Journal of Fish Biology, 1999)
Four shark species in Australian waters were found with skeletal deformities. Deformities were similar across three species with large scoliotic, lordotic and kyphotic bends of the vertebral columns. The cause of these deformities is currently unknown.

Electrophoretic differentiation in isolated populations of Lolium rigidum Gaud. - S. J. Bennett; M. D. Hayward (Molecular Ecology, 1999)
Sixteen wild populations of Lolium rigidum Gaud. were collected from island and mainland locations in Mediterranean Europe and western Asia. Five loci, controlling isozymes at four enzyme systems, were assayed on 60 plants per population using starch gel electrophoresis. Gene diversity measures and Nei’s genetic distance were calculated, and the relationships between the populations were analysed using principal component (PCA) and cluster analyses. All populations were found to show a gene diversity index that is consistent with that expected in a cross‐fertilising species. The highest gene diversity measures were recorded in some of the island populations. Both PCA and cluster analysis grouped the Balearic Island populations together and separated the Spanish and Sardinian populations from any of the others. The results are discussed with respect to a number of theories of migration between populations, and in relation to the colonization history of each island. It is suggested that the preservation of these island populations in gene banks is important as part of a core collection of the species.

A Phosphorus Budget for the Lake Mendota Watershed - Elena M. Bennett; Tara Reed-Andersen; Jeffrey N. Houser; John R. Gabriel; Stephen R. Carpenter (Ecosystems, 1999)

Tetrachromacy, oil droplets and bird plumage colours - M. Vorobyev; D. Osorio; A. T. D. Bennett; N. J. Marshall; I. C. Cuthill (Journal of Comparative Physiology A, 1998)

Influence of Gravity on Cardiac Performance - George M. Pantalos; M. Keith Sharp; Stewart J. Woodruff; D. Sean O’Leary; Richard Lorange; Scott D. Everett; Thomas E. Bennett; Thomas Shurfranz (Annals of Biomedical Engineering, 1998)

Infection of the epaulette shark, Hemiscyllium ocellatum (Bonnaterre), by the nematode parasite Proleptus australis Bayliss (Spirurida: Physalopteridae) - M. R. Heupel; M. B. Bennett (Journal of Fish Diseases, 1998)
Seventy‐two epaulette sharks, Hemiscyllium ocellatum (Bonnaterre), were infected with the nematode parasite Proleptus australis Bayliss, 1933. The parasite population was overdispersed. Infection intensity ranged from 3 to 1002 worms per fish stomach, and there was a positive correlation between shark length and number of parasites present. The majority of worms were attached to the stomach wall, and scanning electron microscopy and histological examination showed that worms penetrated the stomach lining. Worms were observed within the lamina propria of the stomach and occasionally penetrated the muscularis mucosa. Little to no inflammatory or cellular immune reaction to the presence of the parasites was observed, except in one case where a worm was being degraded by a host tissue response. There was a large amount of connective tissue proliferation as a result of nematode attachment, but no obvious effects on the overall health of the sharks were seen. Three sharks were also found to be infected by the cestode Callitetrarhynchus sp.

High-resolution paleoecological analysis of recent disturbance in a southern Chilean Nothofagus forest - Julian M. Szeicz; Barbara A. Zeeb; K.D. Bennett; John P. Smol (Journal of Paleolimnology, 1998)

Subacute and Reproductive Effects in Mink from Exposure to Fusarium fujikuroi Culture Material (M-1214) Containing Known Concentrations of Moniliformin - M. K. Morgan; S. J. Bursian; G. E. Rottinghaus; G. A. Bennett; J. A. Render; R. J. Aulerich (Archives of Environmental Contamination and Toxicology, 1998)

Detection of Bacteraemia in Patients with Fever and Neutropenia Using 16S rRNA Gene Amplification by Polymerase Chain Reaction - B. E. Ley; C. J. Linton; D. M. C. Bennett; H. Jalal; A. B. M. Foot; M. R. Millar (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Sequence Comparison of Avian Infectious Bronchitis Virus S1 Glycoproteins of the Florida Serotype and Five Variant Isolates from Georgia and California - Kristi M. Moore; Joyce D. Bennett; Bruce S. Seal; Mark W. Jackwood (Virus Genes, 1998)

Novel Chitinolytic Enzymes with Biological Activity Against Herbivorous Insects - Roxanne M. Broadway; Carmenza Gongora; Wendy C. Kain; John P. Sanderson; Jose A. Monroy; K. C. Bennett; Jason B. Warner; Michael P. Hoffmann (Journal of Chemical Ecology, 1998)

Detection of bacteraemia in patients with fever and neutropenia using 16S rRNA gene amplification by polymerase chain reaction - B. E. Ley; C. J. Linton; D. M. C. Bennett; H. Jalal; A. B. M. Foot; M. R. Millar (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Mercury Accumulation in Transplanted Hypogymnia Physodes Lichens Downwind of Wisconsin Chlor-Alkali Plant - M. M. Makholm; J. P. Bennett (Water, Air, & Soil Pollution, 1998)

Analysis of tissue responses to fin tagging in Australian carcharhinids - M. R. Heupel; C. A. Simpfendorfer; M. B. Bennett (Journal of Fish Biology, 1998)
Tissue responses to the application of Rototags and Jumbo Rototags in the first dorsal fin of Carcharhinus melanopterus, C. obscurus and C. plumbeus were examined. The acute response included tissue tearing and haemorrhage and was present by 5 days post‐tagging. The intermediate response had begun by 20 days post‐tagging and continued beyond 207 days. This response involved decreased red blood cell activity as the inflammatory response commenced. The chronic response had begun by 301 days and was complete by 553 days with a layer of fibrous connective tissue walling off the tag. External damage to the fin was caused by continued abrasion by the tag. Repair scales were observed at 242 days using scanning electron microscopy and were confirmed histologically in 61‐ and 553‐day samples. Repair scales were not seen in areas of continuous abrasion. No infection was observed in tissues surrounding the wound. Disruption of the fin surface was observed due to abrasion by the tag, but did not appear to cause a severe tissue reaction. The tissue responses observed were consistent with a normal, but relatively slow, healing in the vicinity of the tag wound. Use of Rototags or Jumbo Rototags appears to be an efficient way of marking elasmobranchs with minimal damage to the shark.

Interactive effects of subanesthetic ketamine and subhypnotic lorazepam in humans - John H. Krystal; Laurence P. Karper; Alexandre Bennett; D. Cyril D'Souza; Anissa Abi-Dargham; Kristen Morrissey; Danielle Abi-Saab; J. Douglas Bremner; M. B. Bowers Jr.; Raymond F. Suckow; Philip Stetson; George R. Heninger; et al. (Psychopharmacology, 1998)

Food availability and foraging by wild colonies of Damaraland mole-rats ( Cryptomys damarensis ): implications for sociality - Jennifer U. M. Jarvis; Nigel C. Bennett; Andrew C. Spinks (Oecologia, 1998)

The Cystatin S gene maps to rat Chromosome 3, to which Dlmgh18 is re-assigned from Chromosome 1 - M. Beatriz Duran Alonso; Paul Shiels; Andrew S. McCallion; Neil K. Bennett; Anthony P. Payne; Josiane Szpirer; Claude Szpirer; Martin J. Brodie; R. Wayne Davies; Roger G. Sutciffe (Mammalian Genome, 1997)

Sequences of the Ribonucleotide Reductase-Encoding Genes of Felid Herpesvirus 1 and Molecular Phylogenetic Analysis - Kim Willoughby; Malcolm Bennett; Russell A. Williams; Christine McCracken; Rosalind M. Gaskell (Virus Genes, 1997)

Performance of maize, beans and ginger as intercrops in Paulownia plantations in China - S. M. Newman; K. Bennett; Y. Wu (Agroforestry Systems, 1997)

Announcement - P. D. Markel; B. Bennett; M. A. Besson; L. Gordon; V. J. Simpson; T. E. Johnson (Mammalian Genome, 1997)

Erratum - P. D. Markel; B. Bennett; M. A. Besson; L. Gordon; V. J. Simpson; T. E. Johnson (Mammalian Genome, 1997)

Loss of cell surface microvilli on rat basophilic leukaemia cells precedes secretion and can be mimicked using the calmodulin antagonist trifluoperazine - A. J. Edgar; G. R. Davies; M. A. Anwar; J. P. Bennett (Inflammation Research, 1997)

Homoeologous pairing and recombination in backcross derivatives of tomato somatic hybrids [Lycopersicon esculentum (+) L. peruvianum] - A. S. Parokonny; J. A. Marshall; M. D. Bennett; E. C. Cocking; M. R. Davey; J. Brian Power (Theoretical and Applied Genetics, 1997)

Histology of dart tag insertion sites in the epaulette shark - M. R. Heupel; M. B. Bennett (Journal of Fish Biology, 1997)
Samples of dermal and epidermal tissues of epaulette sharks Hemiscyllium ocellatum were examined histologically to assess damage caused by tagging. Tissues from around tag sites were removed at time intervals ranging from 100 min to 284 days post‐tagging. These samples showed acute and chronic responses to tagging. Acute responses consisted of localized tissue breakdown and haemorrhaging, and occurred within the first few hours after tag insertion. At 10 h post‐tagging, an intermediate response was apparent. This phase was characterized by further haemorrhaging and red and white blood cell movement into the wound area. The chronic response observed in the 10–284‐day post‐tagging samples was characterized by fibrous tissue formation to sequester the tag. This tissue presumably protects the adjacent musculature from further trauma produced by movement of the tag and provides a continuous barrier between the internal and external milieu. Tissue repair appeared to progress consistently in all specimens and no secondary infections at the tag site were seen. Tagging produced only localized tissue disruption and did not appear to be detrimental to the long term health of individual sharks. Our findings show that spaghetti style dart tagging is an acceptable method for marking individuals (40–75+ cm total length) of this species.

Perceptions of Species Abundance, Distribution, and Diversity: Lessons from Four Decades of Sampling on a Government-Managed Reserve - J. Whitfield Gibbons; Vincent J. Burke; Jeffrey E. Lovich; Raymond D. Semlitsch; Tracey D. Tuberville; J. Russell Bodie; Judith L. Greene; Peter H. Niewiarowski; Howard H. Whiteman; David E. Scott; Joseph H. K. Pechmann; Christopher R. Harrison; et al. (Environmental Management, 1997)

Generalized inversion of a global numerical weather prediction model, II: Analysis and implementation - A. F. Bennett; B. S. Chua; L. M. Leslie (Meteorology and Atmospheric Physics, 1997)

MUC1 gene polymorphism and gastric cancer–an epidemiological study - F Carvalho; R Seruca; L David; A Amorim; M Seixas; E Bennett; H Clausen; M Sobrinho-Simoes (Glycoconjugate Journal, 1997)

Influence of autoregressive model parameter uncertainty on spectral estimates of heart rate dynamics - David J. Christini; Abhijit Kulkarni; Srikar Rao; Eric R. Stutman; Frederick M. Bennett; Jeffrey M. Hausdorff; Nancy Oriol; Kenneth R. Lutchen (Annals of Biomedical Engineering, 1995)

An interpretation of toxicity response of bobwhite quail with respect to duration of exposure - M. A. Shirazi; R. S. Bennett; R. K. Ringer (Archives of Environmental Contamination and Toxicology, 1994)

Eusociality has evolved independently in two genera of bathyergid mole-rats — but occurs in no other subterranean mammal - J. U. M. Jarvis; N. C. Bennett (Behavioral Ecology and Sociobiology, 1993)

Regulation of PaCO2 during rest and exercise: A modeling study - Frederick M. Bennett; Wayne E. Fordyce (Annals of Biomedical Engineering, 1993)

Introduction: In honor of Fred S. Grodins - Frederick M. Bennett (Annals of Biomedical Engineering, 1993)

Polymerase chain reaction for detection of herpesvirus simiae (B virus) in clinical specimens - M. J. Slomka; D. W. G. Brown; J. P. Clewley; A. M. Bennett; L. Harrington; D. C. Kelly (Archives of Virology, 1993)

Identification and sequence determination of the capsid protein gene of feline calicivirus - M. J. Carter; I. D. Milton; P. C. Turner; J. Meanger; M. Bennett; R. M. Gaskell (Archives of Virology, 1992)

Utilization of potatoes for life support in space v. evaluation of cultivars in response to continuous light and high temperature - T. W. Tibbitts; W. Cao; S. M. Bennett (American Journal of Potato Research, 1992)

Characterization of orthopoxviruses isolated from feline infections in Britain - J. Naidoo; D. Baxby; M. Bennett; R. M. Gaskell; C. J. Gaskell (Archives of Virology, 1992)

Latency and reactivation of infectious laryngotracheitis vaccine virus - C. S. Hughes; R. A. Williams; R. M. Gaskell; F. T. W. Jordan; J. M. Bradbury; M. Bennett; R. C. Jones (Archives of Virology, 1991)

Diurnal temperature fluctuation effects on potatoes grown with 12 hr photoperiods - S. M. Bennett; T. W. Tibbitts; W. Cao (American Journal of Potato Research, 1991)

Limitations of the open loop gain concept in studies of respiratory control - Frederick M. Bennett (Annals of Biomedical Engineering, 1990)

Studies on poxvirus infection in cats - M. Bennett; R. M. Gaskell; C. J. Gaskell; D. Baxby; D. F. Kelly (Archives of Virology, 1989)

The computation of structure from fixed-axis motion: Rigid structures - D. D. Hoffman; B. M. Bennett (Biological Cybernetics, 1988)

Genetic variation in natural and laboratory populations of the marsupial Sminthopsis crassicaudata - R. M. Hope; J. H. Bennett; C. M. Chesson (Biochemical Genetics, 1986)

The computation of structure from fixed-axis motion: rigid structures - D. D. Hoffman; B. M. Bennett (Biological Cybernetics, 1986)

The computation of structure from fixed-axis motion: Nonrigid structures - B. M. Bennett; D. D. Hoffman (Biological Cybernetics, 1985)

Genetic variation in red-cell adenosine deaminase and glucosephosphate isomerase in a laboratory colony of the marsupial Sminthopsis crassicaudata (Gould) - R. M. Hope; J. H. Bennett; C. M. Chesson; M. Adams (Biochemical Genetics, 1984)

The effect of pyruvate on nitrogenase activity in the blue-green alga Anabaena cyclindrica - K. J. Bennett; W. B. Silvester; J. M. A. Brown (Archives of Microbiology, 1975)

Genome size and the proportion of repeated nucleotide sequence DNA in plants - R. B. Flavell; M. D. Bennett; J. B. Smith; D. B. Smith (Biochemical Genetics, 1974)

Plagiprospherysa trinitatis [Dipt.: Tachinidae], A parasite ofElasmopalpus lignosellus [Lep.: Phycitidae] in Trinidad, W. I. - M. N. Beg; F. D. Bennett (BioControl, 1974)

Biological control ofDiatraea saccharalis (F.) in Barbados byApanteles flavipes Cam. andLixophaga Diatraeae T. T. - M. M. Alam; F. D. Bennett; K. P. Carl (BioControl, 1971)

Sectional notes - L. M. Ware; E. Marx; M. A. Lindsay; C. H. Metzger; H. L. Cochran; E. R. Bennett; A. C. Moreau; Frank W. Hussey; H. A. Reiley; Marx Koehnke; J. C. Campbell; M. E. Gardner; et al. (American Journal of Potato Research, 1943)

Sectional notes - M. A. Lindsay; E. Marx; E. R. Bennett; C. L. Fitch; A. A. Henderson; Mitchell Jenkins; G. S. Ralston (American Journal of Potato Research, 1941)

Sectional notes - C. H. Metzger; E. R. Bennett; W. B. Ward; J. G. Richard; Ralph W. Donaldson; T. M. Patterson; L. Harris; Marx Koehnke; J. M. Jenkins; W. H. Martin; Robert Schmidt; E. M. Gillig; et al. (American Journal of Potato Research, 1937)

Sectional notes - H. W. Poulsen; W. B. Ward; E. R. Bennett; C. L. Fitch; E. L. Nedwick; Ralph W. Donaldson; A. G. Tolaas; E. E. Isaac; H. O. Werner; E. V. Hardenburg; G. K. Middlenton; E. M. Gillig; et al. (American Journal of Potato Research, 1935)

Seed potato certification notes - E. L. Newdick; E. R. Bennett; K. W. Lauer; A. W. Palm; E. R. Jackman; C. H. Metzger; Karl H. Fernow; A. G. Tolaas; E. M Gillig; J. G. Milward (American Journal of Potato Research, 1930)

Notes - H. C. Moore; N. J. Thomas; C. W. Metzger; E. R. Bennett; C. W. Hungerford; W M. Stuart; W M. H. Martin; E. B. Tussing; H. H. Zimmerley; H. O. Werner (American Journal of Potato Research, 1928)

Preliminary seed potato certification notes - C. Tice; E. P. Sandsten; E. R. Bennett; F. M. Harrington; H. O. Werner; J. A. Hill (American Journal of Potato Research, 1923)